Bisphenol S causes deficits in social behaviour by disrupting serotonergic and BDNF-CREB1 signaling pathways - A K M Munzurul Hasan; Mahesh Rachamalla; Som Niyogi; Douglas P. Chivers (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Relative Effects of Time-Restricted Eating, Energy-Restricted Eating, and Unrestricted Eating on Eating Patterns and Dietary Intake: Results From a Randomized Controlled Trial - Lisa J. Harnack; Niki Oldenburg; Qi Wang; Erika Helgeson; Abdisa Taddese; Nicole LaPage; Alison Alvear; Alison Wong; Michelle Hanson; Julie D. Anderson; Brad P. Yentzer; Douglas G. Mashek; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

A multi-platform validation of biomass burning emissions: Integrating ground, airborne, and satellite data to quantify regional haze health impacts in Thailand - Ratchaphon Samphutthanont; James H. Crawford; Ittipol Pawarmart; Armin Wisthaler; Stefan J. Swift; Felix Piel; Wojciech Wojnowski; Jose L. Jimenez; Pedro Campuzano-Jost; Seonsik Yun; Guy Symonds; Douglas A. Day; et al. (Environmental Pollution, 2026)

Regional oceanographic controls on water column nitrogen fixation in northern Australian waters - Douglas G. Capone; Ajit Subramaniam; Yubin Raut; Joseph P. Montoya; Margaret R. Mulholland; Rachel Ann Foster; Miles Furnas; Edward J. Carpenter (Frontiers in Marine Science, 2026)
Large blooms of the diazotrophic cyanobacteria, Trichodesmium , have been reported along the north coast of Australia and are readily evident in remote sensing images. During a research cruise in November 1999, we sampled from Townsville to Broome, examined Trichodesmium population densities and their rates of carbon and N 2 fixation alongside microscopy-based cell counts of them and other cyanobacterial diazotrophs. Additionally, we also enumerated the picophytoplankton community using flow-cytometry, measured bulk chlorophyll concentrations, carbon and N 2 fixation rates, and water column hydrography, enabling comparison of diazotrophic and picophytoplankton functional groups across the system. Agglomerative hierarchical clustering analysis of physicochemical oceanographic variables identified four distinct clusters that generally corresponded to the five geographic regions traversed and were supported by principal component analysis. In some cases, cluster analysis of physical parameters revealed close similarity of water masses in different, distal regions. High surface densities (up to 10,000 trichomes per L) and visible surface slicks of Trichodesmium were encountered at many of the stations where N 2 fixation could be directly measured in unconcentrated surface samples. Areal rates of N 2 fixation in excess of 1 mmol N m −2 d −1 were noted at several stations, with the highest average N 2 fixation rates found in the Timor Sea. Although spatial relationships between bulk phytoplankton biomass and carbon fixation rates versus contributions from Trichodesmium were complex, Trichodesmium contributed as much as 25% of total primary production and accounted for more than 50% of surface phytoplankton biomass in the Coral Sea. Lastly, Trichodesmium dominance was observed alongside diatom-diazotroph associations, the unicellular cyanobacteria Crocosphaera sp., and picophytoplankton assemblages, which collectively indicated that nitrogen fixation and primary production were partitioned among distinct phytoplankton and diazotrophic functional groups across hydrographic gradients.

Dune Russet: A French-Fry Potato Cultivar with High Specific Gravity under High-Temperature Growing Conditions and Excellent Processing Quality after Long-Term Cold Storage - M. Isabel Vales; Douglas C. Scheuring; Jeffrey W. Koym; Jeewan Pandey; Stephany E. Toinga-Villafuerte; Joshua R. Johnson; Caroline P. Gray; David G. Holm; Mohamad Chikh-Ali; Robert G. Wilson; Richard G. Novy; Jonathan L. Whitworth; et al. (American Journal of Potato Research, 2026)
Dune Russet (COTX08063-2Ru) is the first French fry russet potato cultivar released by the Texas A&M Potato Breeding Program. It derives from a cross made by the Colorado State University Potato Program between Premier Russet and A99073-1 and was subsequently selected and advanced by the Texas Program. Dune Russet has oblong potato tubers with light russet skin texture and white flesh. It is characterized by having excellent French fry quality and cold-induced sweetening resistance, producing light-colored fries directly from the field and even after several months (three to eight) in cold storage at 4.4 °C. Dune Russet is especially recommended for areas that experience high-temperature stress during the growing season, as it can retain high specific gravity near 1.090 and produce light French fries despite heat stress. Across multi-location trials, Dune Russet outperformed the reference cultivar, Russet Burbank, and other processing cultivars in French fry quality, while offering some field-based PVY tolerance and good agronomic performance, including competitive marketable yields and a high proportion of US No. 1 tubers.

Assessing the ecosystem health of tropical mangroves using biliary, urinary and hemolymph fluids from organisms of the Brazilian Equatorial Margin (Jaguaribe River, Ceará, Brazil) - Gladston R.C. Junior; Melissa L. Paiva; Vinícius P. Albuquerque; Vitória B. Silva; Maria I.S. Dutra; Lucas B. Batista; Douglas M. Lima; Milena C.M. Santos; Antônia D.F. Lima; Rivelino M. Cavalcante (Marine Pollution Bulletin, 2026)

Integrating detrital magnetite geochemistry and (U–Th)/He chronometry as a sediment provenance tool in geologic and metallogenic terranes - Robert G. McDermott; Douglas C. Kreiner; James V. Jones; Sean P. Regan; James R. Metcalf; Rebecca M. Flowers (Chemical Geology, 2026)

Embryonic exposure to Bisphenol S causes long-term social behavioural alterations in adult zebrafish (Danio rerio) - A K M Munzurul Hasan; Mahesh Rachamalla; Douglas P. Chivers; Som Niyogi (Aquatic Toxicology, 2026)

When Scientific Reassessment Fails Citizen Science. Comment on Soldo, A. When Citizen Science Becomes Speculation: Evaluating the Reliability of Lamnid Shark Identification from Photographic Records in the Mediterranean. J. Mar. Sci. Eng. 2026, 14, 173 - Patrick L. Jambura; Julia Türtscher; Joshua K. Moyer; Kenshu Shimada; Ilija Ćetković; Branko Dragičević; Pero Ugarković; Mišo Pavičić; Phillip C. Sternes; Simone Niedermüller; Jacopo Bernardi; Matteo Barbato; et al. (Journal of Marine Science and Engineering, 2026)
Soldo [...]

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A perfluoro-functionalised fluorescent maleimide probe for imaging of per- and polyfluoroalkyl substances - Jake E. Barker; Stephen D. P. Fielden; Richard H. Kempton; Calum T. J. Ferguson; Rachel K. O’Reilly; Grant B. Douglas (Environmental Chemistry Letters, 2026)
The persistence of per- and polyfluoroalkyl substances in the environment is becoming a major health concern, yet studying their fate and behaviour in complex media is limited due to the lack of suitable analytical methods. Here we proposed that a fluorescent polyfluoroalkyl probe could enable rapid tracing and negate drawbacks associated with current techniques. We synthesised a fluorescent probe containing a maleimide motif grafted to perfluorooctanoic acid. Using a conductivity assay, the critical micelle concentration was determined, and cryogenic transmission electron microscopy was further utilised to verify the presence of multilamellar vesicles. Titration of the fluorescent probe with a base enabled the determination of the acid dissociation constant, an important property of perfluorooctanoic acid. Results show that this fluorescent probe exhibits similar properties to perfluorooctanoic acid, and thus could reasonably act as an environmental proxy, with the benefit of strong, concentration-dependent and environmentally responsive fluorescence. This fluorescence offers a facile entry point for real-time tracing in various media. Further exploration of this tracer through plant, concrete, or soil studies could enable a better understanding of per- and polyfluoroalkyl substance behaviour in range of natural and artificial media.

Organelle genomes as universal standard for phylogenetics: a sociotechnical perspective - Seunghyun Lee; Douglas Chesters; Alfried P. Vogler (Trends in Ecology & Evolution, 2026)

A sea-to-soil solution for the green tides threatening shellfish aquaculture: conceptual model and lessons learned from a pilot project - Sarah M. Collier; Emily Buckner; Nicole J. Capizzi; Meg Chadsey; Douglas P. Collins; Jonathan P. Davis; Erick Dowell; Alan Ismach; Brittany G. Johnson; Sergey Rabotyagov; Rob Smith; Katie R. Webb; et al. (Journal of Environmental Management, 2026)

Mothers’ perceptions, acceptability, and feeding practices of rice bran for children: A study of household and stakeholder perspectives - Aastha Dahal; Rubina Karki; Ram Shrestha; Elizabeth P. Ryan; Douglas Taren (Food and Humanity, 2026)

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Formulation and characterization of dextran sulfate-polyethyleneimine complexes for lithium recovery from oilfield and enhanced geothermal system brines - David Kwaku Danso; Jozef Bicerano; Douglas P. Heller; Reza Barati Ghahfarokhi (Journal of Environmental Chemical Engineering, 2026)

Bisphenol S toxicity in zebrafish: Endocrine, neurobehavioural, and metabolic disruptions - A K M Munzurul Hasan; Som Niyogi; Douglas P. Chivers (Environmental Toxicology and Pharmacology, 2026)

Multigenerational effects of selected environmental contaminants in fishes: A comprehensive review - Md Helal Uddin; Jinnath Rehana Ritu; Som Niyogi; Douglas P. Chivers (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Immobilization of thermophilic GH11 xylanase (XylHb) of Humicola brevis var. thermoidea on MANAE-agarose enhances catalytic performance and operational stability for XOS production - Aline P. Almeida; Thayssa V.C. Oliveira; Robson C. Alnoch; Jose C.S. Salgado; Diandra de Andrades; Benevides C. Pessela; Gloria Fernández-Lorente; Douglas C. Masui; Roberto Ruller; Maria de Lourdes T.M. Polizeli (Biocatalysis and Agricultural Biotechnology, 2026)

Short-term responses of Peromyscus maniculatus and Neotamias amoenus populations to large-scale supplemental feeding - Thomas P. Sullivan; Chris M. Kohler; Douglas B. Ransome (European Journal of Wildlife Research, 2026)

Assembling the Neotropical Tree Flora: Andean Uplift and the Historical Biogeography of the Brazil Nut Family (Lecythidaceae) - Diana Medellín‐Zabala; Joseph L. M. Charboneau; Oscar M. Vargas; Stephen A. Smith; Deise J. P. Gonçalves; Andre S. Chanderbali; Douglas E. Soltis; Pamela S. Soltis; Christopher W. Dick (Journal of Biogeography, 2026)
Aim The assembly of tropical tree floras is complex, involving many lineage‐specific histories; however, focusing on the biogeographic history of diverse clades can reveal general patterns. We investigated the historical biogeography of the ecologically important Brazil nut clade (Lecythidoideae) to: (1) expand prior phylogenies with greater sampling of the early branching Andean‐centered subclades; (2) infer the ages and dispersal histories of the major subclades; and (3) document instances of niche evolution within Lecythidoideae, with an emphasis on elevational range shifts. Location Tropical America. Taxon The Neotropical subfamily Lecythidoideae (Lecythidaceae). Methods We expanded phylogenetic taxon sampling to 371 samples representing 197 species across bioregions, emphasizing the Andean‐centered genera Grias and Gustavia . A maximum likelihood phylogeny was inferred using 665 nuclear loci, and divergence times were estimated with four fossil constraints. Ancestral ranges were reconstructed across bioregions and ecoregions using three biogeographic models. Results The crown age of Lecythidaceae is placed in the mid‐Cretaceous (~94 Ma) and the Neotropical clade Lecythidoideae in the Eocene (~51.5 Ma). Grias likely originated in Central America or the Pacific coastal forests of South America (~35.5 Ma), Gustavia in the Amazonian moist forests (~36 Ma) and the Bertholletia clade in Western‐Central Amazonia (~20 Ma). Following geographic dispersal from eastern and western sources, Grias , Gustavia and Lecythis diversified along the Andean slopes; Scottmoria in Central America, and Imbiriba in the Atlantic Forest. Main Conclusions Most Lecythidoideae subclades diversified during the Miocene, a period of major landscape change associated with the tectonic activities that generated the Northern Andes, the formation of the Amazon drainage system and the closure of the Isthmus of Panama. While most species retained lowland rainforest niches, several lineages shifted into Andean montane forests, highlighting how geological change and ecological transitions shaped the assembly of Neotropical tree floras.

IFN-β as a therapeutic agent for influenza A virus infection in old mice - Wenxin Wu; Jeremy S. Alexander; Yang Song; J. Leland Booth; Alexandra K. Ford; Jordan P. Metcalf; Douglas A. Drevets (GeroScience, 2026)

Reproductive biology characterization of violinha Loricariichthys anus - Douglas C. Selle; Raquel S. dos Santos; Thaiza R. de Freitas; Jhony L. Benato; Thales de S. França; Renata V. Dantas; Marco A. Rotta; Marcelle F.O. Barbosa; Vanessa Coimbra; Diógenes H. Siqueira-Silva; Danilo P. Streit (Reproductive Biology, 2026)

Chronic exposure to selenium through a natural diet (Lumbriculus variegatus) resulted in endocrine disruption, and reproductive impairment in zebrafish (Danio rerio) - Md Helal Uddin; Jinnath Rehana Ritu; Mahesh Rachamalla; Som Niyogi; Douglas P. Chivers (Environmental Research, 2026)

Developmental and neurobehavioural toxicity of per- and polyfluoroalkyl substances in aquatic organisms: mechanistic insights from molecular disruption to behavioural dysfunction - Mohamed Hamed; Mohamed Abbas; A K M Munzurul Hasan; Shimaa M. Kteeba; Hesham Taher; Mohammed Abdel-Wahab; Rashad E.M. Said; Zeinab Bakr; Douglas P. Chivers; Jae-Seong Lee; Alaa El-Din H. Sayed (Aquatic Toxicology, 2026)

Rehydrated ground corn silage as alternative to feedlot lambs: feeding behavior and performance - Leandro A. S. da Silva; Cláudia L. S. Lima; Gleidson G. P. de Carvalho; Henry D. R. Alba; Maria L. G. M. L. de Araújo; Cláudia H. da Cruz; Carlindo S. Rodrigues; Dalton H. Pereira; José E. de Freitas Júnior; Manuela S. L. Tosto; Douglas dos S. Pina (Tropical Animal Health and Production, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Design and qualification of timber buckling restrained brace for mass timber-braced frames - Rupesh Uprety; Chris P. Pantelides; Hans-Erick Blomgren; Douglas Rammer (Engineering Structures, 2026)

Wholesale price prediction: The role of information and transparency - David P. Brown; Andrew Eckert; Douglas Silveira (Energy Policy, 2026)

Developmental exposure to Bisphenol S causes neurobehavioural deficits in larval zebrafish (Danio rerio) - A.K.M. Munzurul Hasan; Mahesh Rachamalla; Md Helal Uddin; Sravan Kumar Putnala; Ed S. Krol; Som Niyogi; Douglas P. Chivers (Aquatic Toxicology, 2026)

Occurrence and Ecotoxicological Risks of Pharmaceuticals and Illicit Drugs in Effluent and Unsheltered Homelessness-Impacted River Systems - Douglas B. Sims; Joshua R. Monk; Desta Woldetsadik; Andressa C. Buch; Amanda C. Hudson; Mark C. Garner; Joseph Piacentini; Christopher Cohu; Chris S. Duvall; Jasmine Krause; Meaghan E. Hickey; Matthew Glazewski; et al. (Archives of Environmental Contamination and Toxicology, 2026)

Associations between per- and polyfluoroalkyl substances and metabolic dysfunction-associated steatotic liver disease in adolescents and young adults: modifying roles of age, lifestyle factors, and PNPLA3 genotype - Shiwen Li; Jiawen Carmen Chen; Elizabeth Costello; Douglas I. Walker; Jesse A. Goodrich; Lily Dara; Lucy Golden-Mason; Ana C. Maretti-Mira; Scott M. Bartell; Veronica M. Vieira; Tanya L. Alderete; Michael I. Goran; et al. (Environmental Research, 2026)

The impacts of the Ultra Low Emission Zone (ULEZ) and COVID-19 restrictions on air quality in central London – evidence for an increase in small particles - Douglas J. Gregg; Jordan Tompkins; Rebecca L. Cordell; Andrew S. Brown; Kirsty L. Smallbone; Joshua D. Vande Hey; Kevin P. Wyche; Paul S. Monks (Atmospheric Environment, 2026)

Reduction of non-lunar phases in JSC-1A lunar regolith simulant by different heat treatment methods - Mihail P. Petkov; Douglas L. Rickman; Gerald E. Voecks; Daniel O’Brien (Advances in Space Research, 2026)

Mesenchymal cell-derived extracellular vesicles ameliorate age-related deficits in working memory and in vivo MRI measures of white matter structure and function in rhesus monkeys - Evan C. Mackie; Chia-Hsin Cheng; Maya N. Alibrio; Christine Rutledge; Hongqi Xin; Michael Chopp; Ryan P. McCann; Douglas L. Rosene; Qiong Yang; Ella Zeldich; Maria Medalla; Bang-Bon Koo; et al. (GeroScience, 2025)
Aging humans and non-human primates both exhibit a similar pattern of cognitive decline beginning in middle age that is characterized by progressive impairments in rule learning, executive function, and working and recognition memory—functions often associated with dysfunction of prefrontal and medial temporal lobe regions. The heterogeneity and inter-subject variability in aging and age-related cognitive impairments present challenges for developing effective therapeutics and can be attributed to differing degrees of cortical white matter (WM) damage and alterations to local and long-range prefrontal and temporal networks. A promising therapeutic that has been shown to be efficacious in mitigating WM damage and improving cognitive function in rodent models is mesenchymal cell-derived extracellular vesicles (MSC-EVs). In the present study, late middle-aged rhesus monkeys were systemically administered monkey-derived MSC-EVs every 2 weeks for 18 months. We demonstrate that MSC-EV treatment improves spatial working memory and decreases the frequency of perseverative responses with largely no effects on recognition memory. These cognitive improvements were associated with increases in MRI diffusion measures of WM structural integrity over time as well as preservation of inter-network functional connectivity as measured by resting-state functional MRI. These findings suggest that MSC-EV treatment can slow or reverse age-related cognitive decline while strengthening WM integrity and improving functional connectivity in late middle-aged rhesus monkeys.

Thermosensitivity of the Microvasculature: Molecular and physiological mechanisms in skeletal muscle – A narrative review - Sean P. Langan; Douglas J. Casa; Oh Sung Kwon (Journal of Thermal Biology, 2025)

Decoupling the effects of additives and particle size on hydrothermal dechlorination kinetics of polyvinyl chloride - Douglas Hungwe; Satomi Hosokawa; Alexander Mosqueda; Mannix P. Balanay; Hao Xu; Lu Ding; Yuki Yamasaki (Journal of Environmental Chemical Engineering, 2025)

Mediating role of proteomics in the association between per- and polyfluoroalkyl substance exposure and blood pressure in youth - Jiawen Carmen Chen; Jesse A. Goodrich; Jiawen Liao; Shiwen Li; Qiran Jia; Douglas I. Walker; Elizabeth Costello; Tanya L. Alderete; Michael I. Goran; Damaskini Valvi; Shudi Pan; Brittney O. Baumert; et al. (Environmental Pollution, 2025)

Rare earth elements (REE) as indicators of geochemical processes in permafrost systems of the Arctic Foothills, Northern Alaska - W. Brad Baxter; Joseph P. Smith; Thomas A. Douglas; Robyn A. Barbato; Shawn Gallaher; Amanda J. Barker (Chemical Geology, 2025)

Keratin Scaffold Formulation Impacts rhBMP-2 Biodistribution and Bone Regeneration in a Rat Femur Defect Model - Justin M. Saul; Judy S. Bohnert; Molly O’Brien; Saif Alnuaimi; Troy P. Carnwath; Quinn Dunivan; Douglas W. Coffin; Thomas L. Smith (Tissue Engineering and Regenerative Medicine, 2025)
Background: Treatment for nonunion in long bones remains a clinical need. Collagen sponges loaded with recombinant human bone morphogenetic protein 2 (rhBMP-2) are potential grafts but have limited FDA-approved applications due to safety concerns associated with rapid collagen resorption and burst release of rhBMP-2 in vivo . This work investigates keratin proteins obtained from human hair as a potential rhBMP-2 biomaterial carrier. Keratins are an appealing carrier because the extent of disulfide crosslinking can be modulated by the form of keratin present, thus allowing control over the rate of scaffold degradation. Methods: The two forms of keratin used to formulate carriers were reductively extracted keratin called kerateine (KTN) that can form disulfide crosslinks and oxidatively extracted keratin called keratose (KOS) that does not form disulfide crosslinks. Five formulations of freeze-dried keratin scaffolds containing variable amounts of KOS and KTN were fabricated and implanted into a critically-sized rat femur defect model. Results: A 50:50 KOS:KTN formulation with rhBMP-2 showed the same level of bone bridging, bone mineral density, and bone volume as collagen with rhBMP-2 by 8 weeks as determined by μ-CT. Scaffolds with the 50:50 KOS:KTN or 100% KTN showed approximately fourfold higher retention of fluorescently-labeled rhBMP-2 at the implant site 1, 3, or 7 days post-implant compared to collagen or 100% KOS scaffolds. The increased retention with 50:50 KOS:KTN or 100% KTN correlated with decreased levels of fluorescent rhBMP-2 in distal organs. Conclusions: Keratin scaffolds could provide comparable levels of bone regeneration as collagen carriers with improved safety profiles suitable for use in long bone nonunions.

Confounding factors affect hemocyte responses of mussels Mytilus galloprovincialis upon foodborne exposure to polystyrene nanoplastics of three sizes - Nagore González-Soto; Tamer Hafez; Marisa Sárria Pereira de Passos; Gabriella Schirinzi; Eider Bilbao; Amaia Orbea; Douglas Gilliland; Miguel-Ángel Serra; Miren P. Cajaraville (Science of The Total Environment, 2025)

A comprehensive review on the neurobehavioural effects of bisphenol compounds and the underlying molecular mechanisms in zebrafish (Danio rerio) - A K M Munzurul Hasan; Christopher J. Martyniuk; Som Niyogi; Douglas P. Chivers (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Ammonia tolerant alkaline oxygen reduction reaction on bimetallic cobalt spinels - Karuppasamy Dharmaraj; Rania Hanna; Florian Ruske; Danielle Douglas-Henry; Iver Lauermann; Sateesh Prathapani; Pablo Reyes-Figueroa; Yael Rodriguez-Ayllon; Yan Lu; Valeria Nicolosi; Rutger Schlatmann; Michelle P. Browne; et al. (Chemical Engineering Journal, 2025)

Near-infrared induced photothermal lateral-flow immunoassay utilizing plasmonics-active gold nanostars - Supriya Atta; Yuanhao Zhao; Sebastian Sanchez; Sabina V. Yampolsky; Vanessa K. Berner; Marcellene A. Gates-Hollingsworth; Jasmine Pramila Devadhasan; Alexander Jarrett Summers; Jian Gu; Douglas C. Montgomery; David P. AuCoin; Frederic Zenhausern; et al. (Analytica Chimica Acta, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Impaired early type I interferon responses to influenza virus infection in aged mice are associated with subsequent increased pulmonary inflammation - Wenxin Wu; Jeremy S. Alexander; J. Leland Booth; Chaoqun Huang; Lin Liu; Craig A. Miller; Douglas A. Drevets; Jordan P. Metcalf (GeroScience, 2025)

Variation in patterns of production and water-use efficiency among agroecosystems - Olivia L. Hajek; Nicole E. Kaplan; Shefali Azad; Philip A. Fay; Makki Khorchani; Amanda M. Nelson; Adam P. Schreiner-McGraw; Lori J. Abendroth; Claire Baffaut; John Baker; Brandon T. Bestelmeyer; Elizabeth H. Boughton; et al. (Science of The Total Environment, 2025)

Migration of oceanic fronts in the Pacific Southern Ocean during the Mid-Pleistocene transition - Maria Julia de Castro; Igor M. Venancio; Thiago P. Santos; Douglas V.O. Lessa; João M. Ballalai; Ana Luiza S. Albuquerque (Marine Micropaleontology, 2025)

Preservation and detection of carotenoid pigments of Deinococcus radiodurans on mineral substrates under UV irradiation - Tamires Gallo; Fabio Rodrigues; Evelyn A.M. Sanchez; Fabio S. de Vicente; Veronica C. Teixeira; Evandro P. Silva; Marcia Rizzuto; Gabriel S. Teofilo-Guedes; Douglas Galante (Icarus, 2025)

Mechanistic insights into microplastic-induced reproductive toxicity in aquatic organisms: A comprehensive review - A K M Munzurul Hasan; Md. Foysul Hossain; Minhaz Uddin; Muhammad Tariq Khan; Uddin Md Saif; Mohamed Hamed; Christopher J. Martyniuk; Douglas P. Chivers (Aquatic Toxicology, 2025)

Temporal analyses of germ cell mutations using the MutaMouse model support the recommended design in OECD test guideline 488 - Gu Zhou; Andrew Williams; Danielle P. M. LeBlanc; George R. Douglas; Carole L. Yauk; Francesco Marchetti (Archives of Toxicology, 2025)
The Organisation for Economic Co-operation and Development test guideline (TG) 488 uses transgenic rodent models to assess in vivo mutagenesis. TG 488 recommends 28 consecutive days of exposure with sampling of germ cells from seminiferous tubules 28 days post-exposure (i.e., 28 + 28d). We analyzed mutant frequencies (MF) in male germ cells up to 70 days post-exposure to determine whether designs other than 28 + 28d are necessary for assessing germ cell mutagenicity. Adult MutaMouse males received various doses of benzo(a)pyrene (BaP), N -ethyl- N -nitrosourea (ENU), isopropyl methanesulfonate (iPMS), or procarbazine (PRC) alongside vehicle controls for 28 days orally. Germ cells were collected from seminiferous tubules at + 3d, + 28d, + 42d, or + 70d post-exposure and MF quantified using the lacZ assay. Significant increases in lacZ MF were observed for all four chemicals at 28 + 28d. No further increases occurred at later sampling times. There was no significant effect with BaP at 28 + 3d, and a significantly stronger response with ENU and BaP at 28 + 28d compared to 28 + 3d. PRC produced the strongest response at 28 + 3d, while there was no impact of different sampling times for iPMS. Both these chemicals significantly reduced testis weight at 28 + 3d and 28 + 28d. Finally, benchmark dose modeling generated overlapping confidence intervals among the four sampling times for ENU, iPMS, and PRC. However, for BaP, the confidence interval was significantly greater at 28 + 3d than at the other sampling times. These results support the use of the 28 + 28d design as the recommended experimental design for germ cells in TG 488 and that later sampling times are not necessary.

Austral Autumn Precipitation Anomalies Across the Amazon Basin Under the Combined Influences of the Equatorial Pacific and Tropical Atlantic - Antônio V. Nogueira Neto; Everaldo B. de Souza; Fernanda C. Vasconcellos; Douglas Silva Ferreira; Vania S. Franco; Claudia P. W. da Costa; Edmir S. Jesus; Renata G. Tedeschi (International Journal of Climatology, 2025)
Under normal conditions, the austral autumn (March–April–May [MAM]) season represents the onset, peak or end of the rainy season, depending on the Amazon sector. In this study, the relative influences of the equatorial Pacific (EqP) and tropical Atlantic (TA) on precipitation anomalies over northern South America were revisited, focusing on the Amazon Basin and the MAM season. We systematically analysed the combined and isolated influences of the EqP and TA to identify the regions of the Amazon that are most sensitive to the atmospheric and oceanic patterns during MAM and described the main related mechanisms responsible for anomalous precipitation. The main features of the El Niño‐Southern Oscillation (ENSO) and the TA meridional sea surface temperature gradient (tropical Atlantic gradient—TAG) were described for each scenario. Our results indicate that a positive (negative) TAG alone increases (decreases) precipitation over the northern and central‐eastern regions. On the other hand, the isolated influence of ENSO depends on its persistence during the season, affecting mainly the northern and north‐eastern regions, with a stronger impact on La Niña occurrence. Under the occurrence of ENSO events and TAGs of the same sign, the whole equatorial Amazon is affected by the sum of circulation effects. In this context, the driest scenario was observed under the combined influence of an El Niño and a positive TAG, which strongly impacted the northern and central‐eastern sectors of Amazon. Finally, TAGs and ENSO events of opposite signs resulted in anomalous precipitation mainly in the northern, north‐eastern and western Amazon, where the TAG‐related circulation prevailed against the influence of ENSO events. This study improves the current understanding of austral autumn spatial rainfall variability in the Amazon under the influence of ENSO and tropical Atlantic patterns.

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Reducing UVR Exposure in Pregnant Women and Infants: A Pilot Study - William J. Tanguy; Kenneth P. Tercyak; Yizhe Xu; Jonathan Chipman; Nathan Shen; Caroline Joung; Hannah L. Brady; Marcelo M. Sleiman; Douglas Grossman; Lauren H. Theilen; Yelena P. Wu (Journal of Cancer Education, 2025)

Thirty-year responses of ecosystem components to stand thinning in lodgepole pine forest: Old-forest attributes, stand structure, and forest-floor small mammals - Thomas P. Sullivan; Druscilla S. Sullivan; Pontus M.F. Lindgren; Douglas B. Ransome; J. Hazel-rah Sullivan (Forest Ecology and Management, 2025)

Quantification of alcohol content and identification of fraud in traditional cachaças using NIR spectroscopy - Valber Elias de Almeida; José Félix de B. Neto; Taliana Kênia A. Bezerra; Vanessa P. da Silva; Germano Veras; Railson de Oliveira Ramos; David Douglas de Sousa Fernandes (Food Chemistry, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Corrigendum to ‘Neurodevelopmental and behavioural effects of waterborne selenite in larval zebrafish (Danio rerio)’ [Environ. Res. 273 (2025) 121240] - Md Helal Uddin; Jinnath Rehana Ritu; Douglas P. Chivers; Som Niyogi (Environmental Research, 2025)

Prenatal PFAS exposures and cardiometabolic health in middle childhood in the MIREC cohort - Alan J. Fossa; Amber M. Hall; George D. Papandonatos; Tye E. Arbuckle; Jillian Ashley-Martin; Michael M. Borghese; Jenny Bruin; Aimin Chen; Mandy Fisher; John E. Krzeczkowski; Bruce P. Lanphear; Amanda J. MacFarlane; et al. (Environmental Research, 2025)

Revealing Yukon’s hidden treasure: an atomic-scale investigation of Carlin-type gold mineralization in the Nadaleen Trend, Canada - Phillip Gopon; Patrick Sack; Nicolas Pinet; James O. Douglas; Benjamin M. Jenkins; Brooke Johnson; Ella Penny; Michael P. Moody; Laurence Robb (Mineralium Deposita, 2025)
The invisible-gold deposits known as Carlin-type are becoming more important as easier to find deposits are progressively depleted. The combination of the invisible nature of the Au in these deposits, as well as the limited surface indicators of these deposits, makes exploration to find new Carlin-type deposits extremely difficult. Comprehensive mineralization models are essential to find new Carlin-type deposits in similar geologic settings. The Nadaleen Trend of Yukon, Canada, is one such district where an improved understanding of this deposit type has led to new discoveries. Previous studies compared and contrasted the tectonic setting, host rock depositional setting, structural preparation, and mineralization style of the Nadaleen Trend with those in Carlin-type localities, Nevada. However, the comparisons at an atomic scale, between Carlin-type Au deposits in the Nadaleen Trend and those in Nevada, has yet to be investigated. This study fills this knowledge gap by combining high resolution microanalytical techniques with atom probe tomography to examine the distribution of Au and other trace elements in the Nadaleen Trend, compare them to a representative Carlin-type deposit in Nevada (Turquoise Ridge), and determine how widespread the mineralization model is. Our findings show that in the Nadaleen Trend, as in Nevada, Au is generally directly linked with As at the macro to atomic scale, and is incorporated into As/Au rich overgrowths on sedimentary/diagenetic pyrite. Gold-rich pyrite rims in the Nadaleen Trend are generally smaller than those found in Nevada (0.5–2 µm vs > 10 µm), although the ore grades appear comparable. We find that the Au in the pyrite of the Nadaleen Trend is homogenously distributed (i.e. lattice bound) at the atomic scale, but that there is a notable enrichment of As surrounding individual Au atoms. These findings are in agreement with those from previous work on a representative deposit in Nevada, and support the assertation that As is the key ingredient in facilitating the incorporation of Au into the pyrite lattice. Arsenic as an essential component in the trapping mechanisms of Au in CTG deposits, is something that has been as to yet underappreciated in the current models of CTG deposit formation.

Neurodevelopmental and behavioural effects of waterborne selenite in larval zebrafish (Denio rerio) - Md Helal Uddin; Jinnath Rehana Ritu; Douglas P. Chivers; Som Niyogi (Environmental Research, 2025)

Neurobehavioral effects of gestational exposure to mixtures of non-persistent endocrine disruptors in preschool-aged children: The environmental influences on child health outcomes (ECHO) program - Dorothy Nakiwala; John L. Adgate; Greta Wilkening; Emily S. Barrett; Akhgar Ghassabian; Douglas M. Ruden; Susan L. Schantz; Anne L. Dunlop; Patricia A. Brennan; John D. Meeker; Dana Dabelea; Anne P. Starling (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Effects of aerobic exercise of different intensities on the social, emotional, and financial functioning of healthy older adults: results from a 16-week exercise randomized control trial - Charleen J. Gust; Renée Martin-Willett; Laurel P. Gibson; Gregory Giordano; Douglas R. Seals; Angela D. Bryan (GeroScience, 2025)
Better social, emotional, and financial functioning are associated with improved health outcomes in older adults. While the literature supports a positive relationship between physical activity and increased functional ability in older adulthood, the intensity of physical activity necessary to achieve these gains remains uncertain. To address this gap, the current analysis uses data collected as part of a larger randomized controlled trial to examine the effects of a supervised exercise intervention on measures of social, emotional, and financial functioning. Healthy older adults ( n = 211) completed baseline assessments including cardiovascular fitness and health and functioning measures and were randomly assigned to 16 weeks of either: (1) low intensity continuous training (LICT); or (2) moderate intensity continuous training + interval training (MICT + IT). Participants across exercise conditions reported a significant decrease from baseline to post-intervention in depression [ F (1, 158) = 22.17, p < .001] and instrumental risk taking [ F (1, 157) = 6.72, p < .05]. Further, participants assigned to the MICT + IT condition showed significantly greater improvements in loneliness relative to those in the LICT condition [ F (1, 157) = 5.99, p < .05]. By and large, healthy older adults experienced some improvements in functional ability after 16 weeks of exercise. Though most changes were not related to the intensity of exercise condition, associations between increased cardiovascular fitness and both depression and anxiety suggest that exercising at an intensity that improves fitness may confer greater benefits in some domains. Trial registration: ClinicalTrials.gov, NCT02068612.

Nutritional monitoring of rangeland beef cattle in the Edwards Plateau of Texas using region-specific fecal near-infrared spectroscopy predictions of diet quality - Douglas R. Tolleson; William E. Fox; William E. Pinchak; Jay P. Angerer (Rangelands, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Investigating the neural network correlates of apathy, disinhibition, and executive dysfunction in active-duty United States Special Operations Forces - Natalie Gilmore; Isabella R. McKinney; Chieh-En J. Tseng; Douglas N. Greve; Chiara Maffei; Brian C. Healy; Nicole R. Zürcher; Jacob M. Hooker; Samantha L. Tromly; Daniel P. Perl; Kristen Dams-O’Connor; Christine L. Mac Donald; et al. (Brain Imaging and Behavior, 2025)

Oxidative gaseous air pollutant exposure interacts with PNPLA3-I148M genotype to influence liver fat fraction and multi-omics profiles in young adults - William B. Patterson; Nathan D. Young; Elizabeth A. Holzhausen; Frederick Lurmann; Donghai Liang; Douglas I. Walker; Dean P. Jones; Jiawen Liao; Zhanghua Chen; David V. Conti; Lida Chatzi; Jesse A. Goodrich; et al. (Environmental Pollution, 2025)

Consistent Individual Differences and Plasticity in Migration Behaviour of Three North American Ungulates - Michel P. Laforge; Eric Vander Wal; Quinn M. R. Webber; Chris Geremia; Matthew J. Kauffman; Douglas E. McWhirter; Arthur Middleton; Tony W. Mong; Kevin L. Monteith; Anna C. Ortega; Hall Sawyer; Jerod A. Merkle (Ecology Letters, 2025)
Migratory herbivores often time spring migration to coincide with the green‐up of plants. When the timing of green‐up changes across years, herbivores can respond directly and be plastic to changing conditions or populations may adapt via inherent differences among individuals that may allow for an evolutionary response. We quantified plasticity and individual variation in the timing of spring migration and selection for high‐quality forage as a function of the timing of spring green‐up using behavioural reaction norms for three North American ungulate species. The timing of arrival to summer range (but not departure from winter range) was plastic to the timing of green‐up, and both arrival and departure timing were repeatable. Our results suggest that herbivores synchronise migration with the timing of green‐up by adjusting the pace of migration and may be buffered against change via individual differences. Quantifying plasticity and differences in responses represents a crucial step to elucidating the fate of species in a changing world.

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

The quest for scientific objectivity: comment on Luke Glowacki's (2024) “The controversial origins of war and peace: Apes, foragers, and human evolution” - Douglas P. Fry (Evolution and Human Behavior, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Evaluation of real-time fluorescence sensors and benchtop fluorescence for tracking and predicting sewage contamination in the Tijuana River Estuary at the US-Mexico border - Natalie Mladenov; Trent Biggs; Keyshawn Ford; Stephany Garcia; Yongping Yuan; Alexandra Grant; Elise Piazza; Elisa Rivera; Federick Pinongcos; Scott P. Keely; Callie Summerlin; Jeffrey A. Crooks; et al. (Science of The Total Environment, 2024)

Comparison of volatiles evolving from selected highland and mare lunar regolith simulants during vacuum sintering - Mihail P. Petkov; Ryan P. Wilkerson; Gerald E. Voecks; Douglas L. Rickman; Jennifer E. Edmunson; Michael R. Effinger (Planetary and Space Science, 2024)

Thyroid lesions in a population of domestic cats submitted to necropsy without clinical suspicion of thyroid disease - Alana P. Herbichi; Douglas M. Lorenzetti; Matheus Y. dos Santos; Gabriela Hartmann; Rafael A. Fighera; Mariana M. Flores (Journal of Comparative Pathology, 2024)

Residual benefits of alum, gypsum, and magnesium sulfate amendments in reducing phosphorus losses to snowmelt runoff - Madelynn M. Perry; Darshani Kumaragamage; Douglas Goltz; Nora J. Casson; Inoka Amarakoon; Srimathie P. Indraratne (CATENA, 2024)

Multi‐Taxa Responses to Climate Change in the Amazon Forest - Carlos A. S. Rodrigues‐Filho; Flávia R. C. Costa; Juliana Schietti; Anselmo Nogueira; Rafael Pereira Leitão; Juliana Menger; Gabriel Borba; Caian Souza Gerolamo; Stefano S. Avilla; Thaise Emilio; Carolina Volkmer de Castilho; Douglas Aviz Bastos; et al. (Global Change Biology, 2024)
Tropical biodiversity is undergoing unprecedented changes due to the hydrological cycle intensification, characterized by more intense droughts and wet seasons. This raises concerns about the resilience of animal and plant communities to such extremes and the existence of potential refugia—areas theorized to safeguard biological communities from adverse climate impacts. Over 20 years of monitoring in Central Amazonia, we investigated the short‐term and long‐term effects of hydrological cycle intensification on bird, fish, ant, and palm communities. We explored whether the ‘insurance effect’ of climate trends (droughts buffered by preceded wet seasons) or ‘environmental refugia’ (droughts or floods buffered by topographic features) could lessen the impact of climate events on community composition, richness, evenness, and species rank. Pronounced abundance changes were observed among animal species, whereas palm species showed relative temporal stability. Birds and fish were more affected by the immediate and long‐term severity of droughts and wet periods, while ants responded primarily to short‐term drought impacts. Conversely, palm communities exhibited delayed responses to climate extremes, primarily in long‐term comparisons. As expected, the proposed ‘insurance effect’ mitigates the long‐term impacts of extreme climate events on animal and plant community trends. However, less extreme hydrological conditions linked to topographic features did not provide effective ‘environmental refugia’ for animals or plants during adverse climate conditions. These outcomes underscore the complex and varied biological responses to ongoing climate change, challenging the prevailing assumptions about the efficacy of environmental refugia and highlighting the nuanced resilience of biodiversity in Central Amazonia.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Integrative genome-centric metagenomics for surface water surveillance: Elucidating microbiomes, antimicrobial resistance, and their associations - Xinyang Huang; Magaly Toro; Angélica Reyes-Jara; Andrea I Moreno-Switt; Aiko D Adell; Celso J․B Oliveira; Raquel R Bonelli; Sebastián Gutiérrez; Francisca P Álvarez; Alan Douglas de Lima Rocha; Gabriela B Kraychete; Zhao Chen; et al. (Water Research, 2024)

Stable hydrogen isotope evidence of late-Holocene precipitation variability on the Caribbean slope of the Cordillera Central, Costa Rica - Phyllis Y.Y. Kho; Chad S. Lane; Sally P. Horn; John C. Rodgers; Douglas W. Gamble (Quaternary International, 2024)

Climatic niche evolution and speciation modes in the transisthmian Alpheus shrimps (Caridea: Alpheidae) - Douglas Fernandes Rodrigues Alves; Pablo Ariel Martinez; Samara de P. de Barros‐Alves; Ariádine Cristine de Almeida; Marco Aurélio Mendes Elias; Carla Hurt; Kristin M. Hultgren (Journal of Biogeography, 2024)
Aim We studied the niche evolution and diversification modes in transisthmian Alpheus shrimps by examining the interplay between environmental niche divergence and conservatism in allopatric sister species. In a broader perspective, the current study analysed the evolution of climatic niche and the role of the environment in species diversification of Alpheus transisthmian shrimp. Location Atlantic and Eastern‐Pacific oceans. Taxon Alpheus shrimps (Caridea: Alpheidae). Methods We assembled georeferenced occurrences for 33 species of Alpheus (with 24 sister species) from a time‐calibrated molecular phylogeny. We modelled their ecological niches and assessed niche overlap through pairwise comparisons. Additionally, we performed phylogenetic reconstructions of the ancestral environmental niche, for each niche axis. Results Our results demonstrate that thermal tolerances, food availability and hydrodynamic forces were relevant environmental axes in evolutionary processes in transisthmian species of Alpheus . Among the 528 paired comparisons, we found that most niches were divergent, including in 12 clades formed by pairs of sister species (in only two of these clades were the niches fully equivalent). Phylogenetic reconstructions of ancestral niches showed an initial niche conservatism in all axes, with divergences intensifying in the last 12 million years. Main Conclusions We found evidence that confirms the relevance of the environmental changes that occurred in the West Atlantic and East Pacific for niche evolution in transisthmian Alpheus species, as well as for the emergence of some lineages. Our findings provide evidence for different modes of Alpheus species speciation in a period consistent with the closure of the Isthmus of Panama.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Interaction Between Climate Change Scenarios and Biological Invasion Reveals Complex Cascading Effects in Freshwater Ecosystems - Tauany Rodrigues; Pavel Kratina; Rayanne B. Setubal; Joseph L. S. Ferro; Douglas Hideki Abe; Luiza O. Costa; Clarice Casa Nova; Vinicius F. Farjalla; Aliny P. F. Pires (Global Change Biology, 2024)
Climate change often facilitates biological invasions, leading to potential interactive impacts of these global drivers on freshwater ecosystems. Although climatic mitigation efforts may reduce the magnitude of these interactive impacts, we are still missing experimental evidence for such effects under multiple climate change scenarios within a multi‐trophic framework. To address this knowledge gap, we experimentally compared the independent and interactive effects of two climate change scenarios (mitigation and business‐as‐usual) and biological invasion on the biomass of major freshwater trophic groups (phytoplankton, zooplankton, periphyton, macroinvertebrates, and a native macrophyte) and the decomposition rate of allochthonous material. Among the independent effects, we found that the business‐as‐usual climate treatment resulted in lower native macrophyte biomass and higher periphyton biomass compared to the climatic baseline and mitigation treatments. This indicates the potential of climate change to alter the relative dominance of different freshwater producers and demonstrates that climate mitigation efforts can counteract these effects. Biological invasion alone increased the biomass of chironomids, a dominant macroinvertebrate group in tropical freshwater ecosystems, demonstrating a compensatory effect on climate change. Climate change and biological invasion interactively reduced the decomposition rate of allochthonous detritus, likely mediated by the feeding preference of abundant chironomids for periphytic algae associated with the presence of non‐native macrophytes. We concluded that (i) climatic mitigation can maintain climate baseline conditions in freshwater ecosystems, and (ii) the interactive effects between future climate scenarios and biological invasion are related to complex cascading interactions among trophic groups on ecosystem processes.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Selenium toxicity in fishes: A current perspective - Md Helal Uddin; Jinnath Rehana Ritu; Sravan Kumar Putnala; Mahesh Rachamalla; Douglas P. Chivers; Som Niyogi (Chemosphere, 2024)

Building collaborative monitoring programs to manage for ecological sustainability in multi-use marine protected areas: Parks Canada’s national marine conservation areas - Chantal Vis; Karla Abbott; Niisii Guujaaw; Cavan Harpur; Lynn Lee; Pippa Shepherd; Douglas P. Tate; Samuel Turgeon; Blythe Beynon (Marine Policy, 2024)

Corrigendum to “Effects of architectural interventions on psychological, cognitive, social, and pro-environmental aspects of occupant well-being: Results from an immersive online study” [Build. Environ. 253 (2024) 111293] - Eva Bianchi; Lucy Zhang Bencharit; Elizabeth L. Murnane; Basma Altaf; Isabella P. Douglas; James A. Landay; Sarah L. Billington (Building and Environment, 2024)

Corrigendum to “Physical workplaces and human well-being: A mixed-methods study to quantify the effects of materials, windows, and representation on biobehavioral outcomes” [Building and Environment 224 (2022) 109516] - Isabella P. Douglas; Elizabeth L. Murnane; Lucy Zhang Bencharit; Basma Altaf; Jean Marcel dos Reis Costa; Jackie Yang; Meg Ackerson; Charu Srivastava; Michael Cooper; Kyle Douglas; Jennifer King; Pablo E. Paredes; et al. (Building and Environment, 2024)

Quantifying the relative importance of biotic and abiotic factors in landscape-based models of stream fish distributions - Christopher A. Custer; Douglas P. Fischer; Geoffrey Smith; Aaron Henning; Megan Kepler Schall; Matthew K. Shank; Timothy A. Wertz; Tyler Wagner (Community Ecology, 2024)
Lotic fish species distributions are frequently predicted using remotely sensed habitat variables that characterize the adjacent landscape and serve as proxies for instream habitat. Recent advancements in statistical methodology, however, allow for leveraging fish assemblage data when predicting distributions. This is important because assemblage composition likely provides better information about instream habitat compared to landscape-derived metrics and therefore may improve predictions. To better understand the value of using multi-species fish data in species distribution modeling, we fit two conditional random fields (CRF) models to quantify the relative importance of fish assemblage co-occurrence, landscape-derived habitat variables, and interactions between these two predictor groups (i.e., effects of co-occurrence could be context-dependent) at over 1200 stream catchments in Pennsylvania, USA. We first compared predictive performance of CRF models against traditionally used single-species logistic regressions (generalized linear models; GLMs) and found that inclusion of fish assemblage data often improved predictive performance. The multi-species CRF models performed significantly better at predicting occurrence for 63% of species with an average percent increase in AUC of 25% compared to GLMs. Furthermore, the CRF identified species co-occurrences as more informative, and thus relatively more important, at predicting occurrence than the other effect types. The CRF also suggested that allowing these biotic effects to be context-dependent was important for predicting occurrence of many species. These findings illustrate the value of fish assemblage data for landscape-scale species distribution modeling and leveraging this information can improve predictions and inferences to help inform the management and conservation of freshwater fishes.

The Development of a Feature-Driven Analytical Approach for Gamma-Ray Spectral Analysis - Aaron P. Fjeldsted; Jarek Glodo; Darren E. Holland; George V. Landon; Clayton Scott; Yilun Zhu; Azaree T. Lintereur; Douglas E. Wolfe (Annals of Nuclear Energy, 2024)

Changes in plasma concentrations of per- and Polyfluoroalkyl substances after bariatric surgery in adolescents from the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study - Brittney O. Baumert; Sandrah P. Eckel; Jesse A. Goodrich; Zhenjiang Li; Nikos Stratakis; Douglas I. Walker; Yinqi Zhao; Fabian Christoph Fischer; Scott Bartell; Damaskini Valvi; Xiangping Lin; Zoe Coates Fuentes; et al. (Science of The Total Environment, 2024)

Sub-lethal effects of the insecticide, imidacloprid, on the responses of damselfly larvae to chemosensory cues indicating predation risk - Prashani D. Wickramasingha; Christy A. Morrissey; Iain D. Phillips; Adam L. Crane; Douglas P. Chivers; Maud C.O. Ferrari (Chemosphere, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

On the measurement of shape: With applications to lunar regolith - Ryan P. Wilkerson; Douglas L. Rickman; Justin R. McElderry; Sarah R. Walker; Kevin M. Cannon (Icarus, 2024)

The microbial lipid signature in sediments and chimneys within a back-arc basin hydrothermal system south of the Antarctic Polar Front - Maria T. Hernández-Sánchez; Laura Hepburn; Michael J. Stock; Douglas P. Connelly; Richard D. Pancost (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Effects of architectural interventions on psychological, cognitive, social, and pro-environmental aspects of occupant well-being: Results from an immersive online study - Eva Bianchi; Lucy Zhang Bencharit; Elizabeth L. Murnane; Basma Altaf; Isabella P. Douglas; James A. Landay; Sarah L. Billington (Building and Environment, 2024)

Relationships Between Muskrat Density and Avian and Anuran Richness in Great Lakes Coastal Wetlands - Jennifer E. Baici; Kayla D. Martin; Sasha L. Newar; Thomas Burgess; Janet E. Greenhorn; Spencer R. Kielar; Laurelie Menelon; Gregory P. Melvin; Rebekah Persad; Carrie Sadowski; Kirsten Solmundson; Douglas C. Tozer; et al. (Wetlands, 2024)

Does SW China have Carlin-type gold deposits? A micro- to atomic-scale perspective - Zhuojun Xie; Phillip Gopon; Yong Xia; James O. Douglas; Jean Cline; Jianzhong Liu; Qinping Tan; Jingdan Xiao; Yuanyun Wen; Youwei Chen; Pan Li; Michael P. Moody (Mineralium Deposita, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Sibling aggression is surprisingly common and sexually egalitarian - Amanda P. Kirsch; Douglas T. Kenrick; Ahra Ko; Cari M. Pick; Michael E.W. Varnum (Evolution and Human Behavior, 2024)

Exposure to perfluoroalkyl substances and longitudinal changes in bone mineral density in adolescents and young adults: A multi-cohort study - Emily Beglarian; Elizabeth Costello; Douglas I. Walker; Hongxu Wang; Tanya L. Alderete; Zhanghua Chen; Damaskini Valvi; Brittney O. Baumert; Sarah Rock; Bruna Rubbo; Max T. Aung; Frank D. Gilliland; et al. (Environmental Research, 2024)

Per- and polyfluoroalkyl substances, polychlorinated biphenyls, organochlorine pesticides, and polybrominated diphenyl ethers and dysregulation of MicroRNA expression in humans and animals—A systematic review - Yijie Li; Brittney O. Baumert; Elizabeth Costello; Jiawen Carmen Chen; Sarah Rock; Nikos Stratakis; Jesse A. Goodrich; Yinqi Zhao; Sandrah P. Eckel; Douglas I. Walker; Damaskini Valvi; Michele A. La Merrill; et al. (Environmental Research, 2024)

Sustainability assessment of peri-urban organic horticulture — A case study in the United Kingdom - Mustafa Ali; Lenny Koh; Adolf Acquaye; Jonathan Leake; Jacob Nickles; Toby P. Evans; Gareth Roberts; Douglas Kemp (The International Journal of Life Cycle Assessment, 2024)
Purpose There is a growing concern about the resilience and sustainability of horticultural production in the United Kingdom (UK) as a result of high energy costs and insufficient local labour, causing over-reliance on imports. In this study, we present an integrated environmental and economic assessment of organic peri-urban horticulture using primary data from a farm in Sheffield. Methods This study includes a farm-to-gate hybrid life cycle assessment (LCA) using the ReCIPE (H) approach for the functional unit of 1-kg tomatoes produced in an unheated polytunnel without supplementary lighting, and 1 kg of field-grown courgettes. All analyses were conducted in SimaPro software using environmental data from the ecoinvent database. Results were compared with those from a systematic literature review of similar studies. Results We found that the production of organic tomatoes and courgettes resulted in a global warming potential (GWP) of 0.61 kg CO 2 -eq and 0.11 kg CO 2 -eq respectively using a process-based LCA approach. Using a hybrid LCA approach, however, yielded a GWP of 3.53 kg CO 2 -eq and 1.70 kg CO 2 -eq for the production of organic tomatoes and courgettes respectively. An additional scenario included farmgate-to-warehouse transportation for both domestic and imported produce from Spain, but found that the GWP of tomatoes in the case study was 1.87 times higher than those from Spain. Economic analysis showed that the marginal increase in the prices of tomatoes and courgettes from the case study farm was 4.6 and 5.15 times less than the market prices. Conclusion We conclude that the studied production system is both economically and environmentally sustainable as compared to the existing scenario. Other potential benefits of peri-urban organic horticulture include employment, mental health, community cohesion, which remain to be explored in a future qualitative study. The present study is novel as it appears to be the first application of hybrid LCA to UK horticulture. The findings are highly topical given the recent horticultural supply constraints in the UK.

Exposure to the insecticide, imidacloprid, impairs predator-recognition learning in damselfly larvae - Prashani D. Wickramasingha; Christy A. Morrissey; Iain D. Phillips; Adam L. Crane; Maud C.O. Ferrari; Douglas P. Chivers (Environmental Pollution, 2024)

Maternal exposure to bisphenol S reduces anxiety and impairs collective antipredator behavior of male zebrafish (Danio rerio) offspring through dysregulation of their serotonergic system - Arash Salahinejad; Denis Meuthen; Anoosha Attaran; Som Niyogi; Douglas P. Chivers; Maud C.O. Ferrari (Aquatic Toxicology, 2024)

Historical control histopathology data from amphibian metamorphosis assays and fathead minnow fish short term reproductive assays: A tool for data interpretation - Jeffrey C. Wolf; John W. Green; Valentin Mingo; Joseph P. Marini; Suzanne Z. Schneider; Douglas J. Fort; James R. Wheeler (Aquatic Toxicology, 2024)

Spontaneous Behavioural Recovery Following Stroke Relates to the Integrity of Parietal and Temporal Regions - Joseph Y. Nashed; Kaden T. Shearer; Justin Z. Wang; Yining Chen; Elise E. Cook; Allen A. Champagne; Nicole S. Coverdale; Juan Fernandez-Ruiz; Shirley I. Striver; J. Randal Flanagan; Jason P. Gallivan; Douglas J. Cook (Translational Stroke Research, 2024)

Recommended water immersion duration for the field treatment of exertional heat stroke when rectal temperature is unavailable - Andreas D. Flouris; Sean R. Notley; Rebecca L. Stearns; Douglas J. Casa; Glen P. Kenny (European Journal of Applied Physiology, 2024)

Persistence of heterologous Flavobacterium psychrophilum genetic variants in microcosms simulating fish farm and hatchery environments - Christopher Knupp; Esteban Soto; Douglas R. Call; Thomas P. Loch (Environmental Microbiology, 2024)
Flavobacterium psychrophilum , the causative agent of bacterial coldwater disease, causes substantial economic losses in salmonid farms and hatcheries. Some multilocus sequence types (ST) of F. psychrophilum are more likely to be associated with fish farms and hatcheries, but it is unclear if these patterns of association represent genetic lineages that are more adapted to aquaculture environments. Towards elucidating the disease ecology of F. psychrophilum , the culturability of 10 distinct F. psychrophilum STs was evaluated for 13 weeks in three microcosms including sterilized well water, sterilized well water with commercial trout feed, or sterilized well water with raceway detritus. All STs remained culturable in each of the microcosms for at least 8 weeks, with bacterial concentrations often highest in the presence of raceway detritus. In addition, most (e.g., 90%) STs remained culturable for at least 13‐weeks. Significant differences in log 10 cfus were observed among STs, both within and between microcosms, suggesting potential variability in environmental persistence capacity among specific variants. Collectively, results highlight the ability of F. psychrophilum to not only persist for weeks under nutrient‐limited conditions but also thrive in the presence of organic substrates common in fish farms and hatchery‐rearing units.

Enhancing Tree Performance Through Species Mixing: Review of a Quarter-Century of TreeDivNet Experiments Reveals Research Gaps and Practical Insights - Leen Depauw; Emiel De Lombaerde; Els Dhiedt; Haben Blondeel; Luis Abdala-Roberts; Harald Auge; Nadia Barsoum; Jürgen Bauhus; Chengjin Chu; Abebe Damtew; Nico Eisenhauer; Marina V. Fagundes; et al. (Current Forestry Reports, 2024)

Evaluation of two beef cow fixed-time AI protocols that utilize presynchronization - Jaclyn N. Ketchum; Lacey K. Quail; Kaitlin M. Epperson; Chloey P. Guy; Jerica J.J. Rich; Saulo Menegatti Zoca; Adalaide C. Kline; Taylor N. Andrews; Julie A. Walker; Pedro Levy Piza Fontes; Sandy K. Johnson; Megan P.T. Owen; et al. (Theriogenology, 2024)

Profile of lactic acid bacteria (MALDI-TOF-MS) and physico-chemical and microbiological characteristics of the raw milk and fresh artisanal cheese from Serra Geral, Minas Gerais, Brazil - Luciana A. Caldeira; Gustavo L.C. Valente; Cosme D. Barbosa; Douglas E. Braga; Flavio P. Monção; Leorges M. Fonseca; Marcelo R. Souza; Maria Beatriz A. Gloria (Food Research International, 2024)

Plant growth forms influence sandhill longleaf pine regeneration - Seth W. Bigelow; J. Kevin Hiers; Scott Pokswinski; Douglas P. Aubrey; E. Louise Loudermilk; Joseph J. O'Brien (Forest Ecology and Management, 2024)

Neonatal per- and polyfluoroalkyl substance exposure in relation to retinoblastoma - Yixin Chen; Kimberly C. Paul; Douglas I. Walker; Dean P. Jones; Xuexia Wang; Beate R. Ritz; Julia E. Heck (Environmental Research, 2024)

Michael F. Tillman 1943–2023 - Robert L. Brownell; Linda L. Jones; Douglas P. DeMaster; Greg P. Donovan; Stephen B. Reilly; Rolland A. Schmitten; Jeffrey M. Breiwick; Robert Suydam; Daryl J. Boness; William W. Fox (Marine Mammal Science, 2024)

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

Screening for collusion in wholesale electricity markets: A literature review - David P. Brown; Andrew Eckert; Douglas Silveira (Utilities Policy, 2023)

Phylogenetic diversity only weakly mitigates climate‐change‐driven biodiversity loss in insect communities - Zongxu Li; Benjamin Linard; Alfried P. Vogler; Douglas W. Yu; Zhengyang Wang (Molecular Ecology, 2023)
To help address the underrepresentation of arthropods and Asian biodiversity from climate‐change assessments, we carried out year‐long, weekly sampling campaigns with Malaise traps at different elevations and latitudes in Gaoligongshan National Park in southwestern China. From these 623 samples, we barcoded 10,524 beetles and compared scenarios of climate‐change‐induced biodiversity loss, by designating seasonal, elevational, and latitudinal subsets of beetles as communities that plausibly could go extinct as a group, which we call “loss sets”. The availability of a published mitochondrial‐genome‐based phylogeny of the Coleoptera allowed us to compare the loss of species diversity with and without accounting for phylogenetic relatedness. We hypothesised that phylogenetic relatedness would mitigate extinction, since the extinction of any loss set would result in the disappearance of all its species but only part of its evolutionary history, which is still extant in the remaining loss sets. We found different patterns of community clustering by season and latitude, depending on whether phylogenetic information was incorporated. However, accounting for phylogeny only slightly mitigated the amount of biodiversity loss under climate change scenarios, against our expectations: there is no phylogenetic “escape clause” for biodiversity conservation. We achieve the same results whether phylogenetic information was derived from the mitogenome phylogeny or from a de novo barcode‐gene tree. We encourage interested researchers to use this data set to study lineage‐specific community assembly patterns in conjunction with life‐history traits and environmental covariates.

Cyclical prey shortages for a marine polar predator driven by the interaction of climate change and natural climate variability - Amanda C. Lohmann; Joseph P. Morton; Oscar M. Schofield; Douglas P. Nowacek (Limnology and Oceanography, 2023)
Between 1992 and 2018, the breeding population of Adélie penguins around Anvers Island, Antarctica declined by 98%. In this region, natural climate variability drives five‐year cycling in marine phytoplankton productivity, leading to phase‐offset five‐year cycling in the size of the krill population. We demonstrate that the rate of change of the Adélie breeding population also shows five‐year cycling. We link this population response to cyclical krill scarcity, a phenomenon which appears to have arisen from the interaction between climate variability and climate change trends. Modeling suggests that, since at least 1980, natural climate variability has driven cycling in this marine system. However, anthropogenic climate change has shifted conditions so that fewer years in each cycle now prompt strong krill recruitment, triggering intervals of krill scarcity that result in drastic declines in Adélie penguins. Our results imply that climate change can amplify the impacts of natural climate oscillations across trophic levels, driving cycling across species and disrupting food webs. The findings indicate that climate variability plays an integral role in driving ecosystem dynamics under climate change.

Data collection and analysis methods to evaluate potential impacts of seismic surveys and other marine industrial activities on baleen whales - Brandon L. Southall; Gregory P. Donovan; Roberto Racca; Randall R. Reeves; Alexander I. Vedenev; David W. Weller; Douglas P. Nowacek (Ocean & Coastal Management, 2023)

Detection of winter tick, Dermacentor albipictus, infestations using near infrared reflectance spectroscopy of bovine feces - Samantha R. Hays; Brian T. Rich; Michael T. Longnecker; Jay P. Angerer; Douglas R. Tolleson; Pete D. Teel (Veterinary Parasitology, 2023)

Postfire hydrologic response along the Central California (USA) coast: insights for the emergency assessment of postfire debris-flow hazards - Matthew A. Thomas; Jason W. Kean; Scott W. McCoy; Donald N. Lindsay; Jaime Kostelnik; David B. Cavagnaro; Francis K. Rengers; Amy E. East; Jonathan Y. Schwartz; Douglas P. Smith; Brian D. Collins (Landslides, 2023)
The steep, tectonically active terrain along the Central California (USA) coast is well known to produce deadly and destructive debris flows. However, the extent to which fire affects debris-flow susceptibility in this region is an open question. We documented the occurrence of postfire debris floods and flows following the landfall of a storm that delivered intense rainfall across multiple burn areas. We used this inventory to evaluate the predictive performance of the US Geological Survey M1 likelihood model, a tool that presently underlies the emergency assessment of postfire debris-flow hazards in the western USA. To test model performance, we used the threat score skill statistic and found that the rainfall thresholds estimated by the M1 model for the Central California coast performed similarly to training (Southern California) and testing (Intermountain West) data associated with the original model calibration. Model performance decreased when differentiating between “minor” and “major” postfire hydrologic response types, which weigh effects on human life and infrastructure. Our results underscore that the problem of false positives is a major challenge for developing accurate rainfall thresholds for the occurrence of postfire debris flows. As wildfire activity increases throughout the western USA, so too will the demand for the assessment of postfire debris-flow hazards. We conclude that additional collection of field-verified inventories of postfire hydrologic response will be critical to prioritize which model variables may be suitable candidates for regional calibration or replacement.

Retrospective chart analysis to determine the impact of a patient-facing digital risk stratification tool combined with a clinical screener for hereditary cancer genetic risk assessment triage in a community oncology clinic - Kate P. Shane-Carson; Douglas Smith; Angie Smith; Caroline Seeley (Journal of Community Genetics, 2023)

The spatial and temporal dynamics of sediment phosphorus attenuation and release in impacted stream catchments - S. Li; J. Arnscheidt; R. Cassidy; R.W. Douglas; H.J. McGrogan; P. Jordan (Water Research, 2023)

Microplastics in marine mammal blubber, melon, & other tissues: Evidence of translocation - Greg B. Merrill; Ludovic Hermabessiere; Chelsea M. Rochman; Douglas P. Nowacek (Environmental Pollution, 2023)

Sediment-water fluxes of inorganic carbon and nutrients in the Pacific Arctic during the sea ice melt season - Lauren J. Barrett; Penny Vlahos; Douglas E. Hammond; Robert P. Mason (Continental Shelf Research, 2023)

Doing the Same Thing Over and Over Again and Getting the Same Result: Assessing Variance in Wetland Invertebrate Assemblages - Sophie Reindl; Kyle I. McLean; Jamie M. Kneitel; Douglas A. Bell; Darold P. Batzer (Wetlands, 2023)

Unusual phenotypes in patients with a pathogenic germline variant in DICER1 - Kateryna Venger; Miriam Elbracht; Julia Carlens; Peter Deutz; Felix Zeppernick; Lisa Lassay; Christian Kratz; Martin Zenker; Jung Kim; Douglas R. Stewart; Ilse Wieland; Kris Ann P. Schultz; et al. (Familial Cancer, 2023)
Pathogenic germline DICER1 variants are associated with pleuropulmonary blastoma, multinodular goiter, embryonal rhabdomyosarcoma and other tumour types, while mosaic missense DICER1 variants in the RNase IIIb domain are linked to cause GLOW (global developmental delay, lung cysts, overgrowth, and Wilms’ tumor) syndrome. Here, we report four families with germline DICER1 pathogenic variants in which one member in each family had a more complex phenotype, including skeletal findings, facial dysmorphism and developmental abnormalities. The developmental features occur with a variable expressivity and incomplete penetrance as also described for the neoplastic and dysplastic lesions associated with DICER1 variants. Whole exome sequencing (WES) was performed on all four cases and revealed no further pathogenic or likely pathogenic dominant, homozygous or compound heterozygous variants in three of them. Notably, a frameshift variant in ARID1B was detected in one patient explaining part of her phenotype. This series of patients shows that pathogenic DICER1 variants may be associated with a broader phenotypic spectrum than initially assumed, including predisposition to different tumours, skeletal findings, dysmorphism and developmental abnormalities, but genetic work up in syndromic patients should be comprehensive in order not to miss additional underlying /modifying causes.

Novel insights into symbiont population structure: Globe‐trotting avian feather mites contradict the specialist–generalist variation hypothesis - Alix E. Matthews; Than J. Boves; Andrew D. Sweet; Elizabeth M. Ames; Lesley P. Bulluck; Erik I. Johnson; Matthew Johnson; Sara E. Lipshutz; Katie L. Percy; Douglas W. Raybuck; Wendy M. Schelsky; Christopher M. Tonra; et al. (Molecular Ecology, 2023)
Researchers often examine symbiont host specificity as a species‐level pattern, but it can also be key to understanding processes occurring at the population level, which are not as well understood. The specialist–generalist variation hypothesis (SGVH) attempts to explain how host specificity influences population‐level processes, stating that single‐host symbionts (specialists) exhibit stronger population genetic structure than multi‐host symbionts (generalists) because of fewer opportunities for dispersal and more restricted gene flow between populations. However, this hypothesis has not been tested in systems with highly mobile hosts, in which population connectivity may vary temporally and spatially. To address this gap, we tested the SGVH on proctophyllodid feather mites found on migratory warblers (family Parulidae) with contrasting host specificities, Amerodectes protonotaria (a host specialist of Protonotaria citrea ) and A. ischyros (a host generalist of 17 parulid species). We used a pooled‐sequencing approach and a novel workflow to analyse genetic variants obtained from whole genome data. Both mite species exhibited fairly weak population structure overall, and contrary to predictions of the SGVH, the generalist was more strongly structured than the specialist. These results may suggest that specialists disperse more freely among conspecifics, whereas generalists sort according to geography. Furthermore, our results may reflect an unexpected period for mite transmission – during the nonbreeding season of migratory hosts – as mite population structure more closely reflects the distributions of hosts during the nonbreeding season. Our findings alter our current understanding of feather mite biology and highlight the potential for studies to explore factors driving symbiont diversification at multiple evolutionary scales.

Maneuvering into the future: Open-Architecture Data Repository (OADR) prototype: Towards civil and commercial space traffic coordination - Mark A. Skinner; Brian Bates; Scott Leonard; Jon Neff; Patrick Bauer; Barry von Tobel; Michelle P. Caputy; Carleton Jillson; Moriba K. Jah; Douglas Hermes; Benjamin Ayers; Benjamin Feuge-Miller (Journal of Space Safety Engineering, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Sealants and Other Management Strategies for PFAS-Contaminated Concrete and Asphalt - Grant B. Douglas; Joanne L. Vanderzalm; Jason K. Kirby; Mike Williams; Trevor P. Bastow; Mark Bauer; Karl C. Bowles; Darren Skuse; Rai S. Kookana; Greg B. Davis (Current Pollution Reports, 2023)
Purpose of Review The unique properties of per- and polyfluoroalkyl substances (PFASs) have seen their widespread adoption, subsequent accumulation in the environment and concern regarding potential environmental effects. Globally, airfields and paved firefighting training surfaces are hotspots for accumulation of PFAS due to extensive use of aqueous film-forming foams (AFFF). Evidence from contaminated concrete and asphalt airfield and training pavements suggests they may serve as an enduring PFAS source. This review investigates sealants as remediation technologies to minimise PFAS mobilisation from pavements drawing on current knowledge of remediation options for soils, sediments, surface and groundwaters. Recent Findings The review did not identify any published sealant information specific to PFAS. Our analysis showed that surface and penetrative sealants may offer an immediate solution via encapsulation of PFAS residues in concrete and asphalt. The most promising surface sealants likely to minimise water ingress and PFAS leaching are selected polymers and (modified) bitumen, owing to the relatively low cost, good adhesion, trafficability and chemical, heat and UV resistance. Potential also exists to enhance PFAS immobilisation using additives to absorb or otherwise chemically bind PFAS. Prospective penetrative sealants include silicates or siloxanes that bind to internal mineral surfaces and/or fill pores to restrict PFAS mobility. It is likely that combinations of surface and penetrative sealants will be required to meet functional, operational and management requirements with respect to new or existing contamination in concrete or asphalt pavements. Summary At present, few if any sealants have been evaluated for their ability to bind or mitigate PFAS mobility. This review serves as a starting point for further studies to evaluate their short or long-term effectiveness in immobilisation of PFAS residues in in situ or ex situ concrete and asphalt. Several knowledge gaps along with suggestions for future research have been made.

Distribution of silicification intervals throughout the Barra Velha and Itapema formations: Host rock controls and chronology of silica precipitation (Pre-Salt, Santos Basin, Brazil) - Tainá P. Pereira; Silvia Terra; Douglas Renato da Silva; Gustavo L.C. Pires; Andre Ribeiro (Journal of South American Earth Sciences, 2023)

Outgassing behavior and heat treatment optimization of JSC-1A lunar regolith simulant - Ryan P. Wilkerson; Mihail P. Petkov; Gerald E. Voecks; Catherine S. Lynch; Holly S. Shulman; Santhoshkumar Sundaramoorthy; Amitava Choudhury; Douglas L. Rickman; Michael R. Effinger (Icarus, 2023)

Within-field yield stability and gross margin variations across corn fields and implications for precision conservation - Kabindra Adhikari; Douglas R. Smith; Chad Hajda; Tulsi P. Kharel (Precision Agriculture, 2023)
Soil spatial variability is a primary contributor to within-field yield variation across farms. Spatio-temporal yield stability and variability can be assessed through multi-year yield monitor data and geostatistical techniques. Our objective was to delineate yield stability zones using multi-year yield data coupled with gross margins to plan precision conservation prescriptions. This study employed corn yield measurements from 2018, 2019, 2020 and farm economics data to compile yield stability and gross margin maps for nine Texas Blackland Prairie corn fields, and identified nonprofitable areas in each field that may be unsuitable for crop production. Yield stability zones were delineated using mean and coefficient of variation of multi-year yield maps (Zone A: high yield, stable; Zone B: high yield, unstable; Zone C: low yield, unstable; and Zone D: low yield, stable). Approximately 57% of the area in the fields was classified as unstable and, nearly 29% of the area yielded consistently below the field mean (Zone D). Gross margin for stability zones ranged from − $693 to $775/ha. Stability zones A and B generally had positive gross margins, whereas zones C and D had negative margins. Based on yield and gross margin assessment, yield stability zone D could be removed from row crop production. As a part of the Long-Term Agroecosystem Research Network Common Cropland Experiment, Zone D was removed from production (fields Y-8 and Y-13) or received reduced inputs (field SW-16 and W-13). Further study is needed to verify the farm-level economic benefits to producers and to evaluate the environmental benefits of precision conservation.

Comparative biology of spatial navigation in three arachnid orders (Amblypygi, Araneae, and Scorpiones) - Joaquin Ortega-Escobar; Eileen A. Hebets; Verner P. Bingman; Daniel D. Wiegmann; Douglas D. Gaffin (Journal of Comparative Physiology A, 2023)

PFAS Exposures and the Human Metabolome: A Systematic Review of Epidemiological Studies - Sandra India-Aldana; Meizhen Yao; Vishal Midya; Elena Colicino; Leda Chatzi; Jaime Chu; Chris Gennings; Dean P. Jones; Ruth J. F. Loos; Veronica W. Setiawan; Mathew Ryan Smith; Ryan W. Walker; et al. (Current Pollution Reports, 2023)

Large and in charge: cortisol levels vary with sex, diet, and body mass in an Antarctic predator, the leopard seal - Emily S. Sperou; Daniel E. Crocker; Renato Borras-Chavez; Daniel P. Costa; Michael E. Goebel; Shane B. Kanatous; Douglas J. Krause; Stephen J. Trumble; Sarah S. Kienle (Frontiers in Marine Science, 2023)
Evaluating physiological responses in the context of a species’ life history, demographics, and ecology is essential to understanding the health of individuals and populations. Here, we measured the main mammalian glucocorticoid, cortisol, in an elusive Antarctic apex predator, the leopard seal ( Hydrurga leptonyx ). We also examined intraspecific variation in cortisol based on life history (sex), morphometrics (body mass, body condition), and ecological traits ( δ 15 N, δ 13 C). To do this, blood samples, life history traits, and morphometric data were collected from 19 individual leopard seals off the Western Antarctic Peninsula. We found that adult leopard seals have remarkably high cortisol concentrations (100.35 ± 16.72 μg/dL), showing the highest circulating cortisol concentration ever reported for a pinniped: 147 μg/dL in an adult male. Leopard seal cortisol concentrations varied with sex, body mass, and diet. Large adult females had significantly lower cortisol (94.49 ± 10.12 μg/dL) than adult males (120.85 ± 6.20 μg/dL). Similarly, leopard seals with higher isotope values (i.e., adult females, δ 15 N: 11.35 ± 0.69‰) had lower cortisol concentrations than seals with lower isotope values (i.e., adult males, δ 15 N: 10.14 ± 1.65‰). Furthermore, we compared cortisol concentrations across 26 closely related Arctoid taxa (i.e., mustelids, bears, and pinnipeds) with comparable data. Leopard seals had the highest mean cortisol concentrations that were 1.25 to 50 times higher than other Arctoids. More broadly, Antarctic ice seals (Lobodontini: leopard seal, Ross seal, Weddell seal, crabeater seal) had higher cortisol concentrations compared to other pinnipeds and Arctoid species. Therefore, high cortisol is a characteristic of all lobodontines and may be a specialized adaptation within this Antarctic-dwelling clade. Together, our results highlight exceptionally high cortisol concentrations in leopard seals (and across lobodontines) and reveal high variability in cortisol concentrations among individuals from a single location. This information provides the context for understanding how leopard seal physiology changes with life history, ecology, and morphology and sets the foundation for assessing their physiology in the context of a rapidly changing Antarctic environment.

Utilizing an immunostimulant (MCWF; Settle) to hasten the degradation of endometrial cups - Carleigh E. Fedorka; Maria R. Schnobrich; Natacha D. Muderspach; Kirsten E. Scoggin; Madison T. Dedman; Kelly E. Weigle; Mary G. May; Heidi P. Twist; Cara R. Linse; Robert H. Douglas; Mats H.T. Troedsson (Journal of Equine Veterinary Science, 2023)

Metabolic pathways altered by air pollutant exposure in association with lipid profiles in young adults - Jiawen Liao; Jesse Goodrich; Douglas I. Walker; Yan Lin; Fred Lurmann; Chenyu Qiu; Dean P. Jones; Frank Gilliland; Lida Chazi; Zhanghua Chen (Environmental Pollution, 2023)

Increasing Skin Cancer Prevention in Young Adults: the Cumulative Impact of Personalized UV Photography and MC1R Genetic Testing - Yelena P. Wu; Jada G. Hamilton; Kimberly A. Kaphingst; Jakob D. Jensen; Wendy Kohlmann; Bridget G. Parsons; Helen M. Lillie; Xuechen Wang; Benjamin Haaland; Ali P. Wankier; Douglas Grossman; Jennifer L. Hay (Journal of Cancer Education, 2023)

Retention of passive integrated transponder tags in hatchery brook trout: Effect of tag size, implantation site, and double tagging - Douglas P. Peterson; Ronald G. Twibell; Matthew S. Piteo (Fisheries Management and Ecology, 2023)
A fundamental assumption of mark‐recapture studies is that individuals do not lose their marks or tags, because tag loss can lead to biased parameter estimates. Retention of 8‐mm full‐duplex and 12‐mm half‐duplex passive integrated transponder (PIT) tags implanted in the abdomen, opercular musculature, and dorsal sinus of age‐0+ hatchery male brook trout ( Salvelinus fontinalis ) was evaluated in the laboratory. Treatments included single‐ and double‐tagged fish. Survival, growth, and tag retention were monitored for 181–187 days for 640 tagged fish and 80 untagged controls. Survival to 180 days ranged 95%–100% and was not affected by tagging. PIT‐tagging caused a short‐term reduction in growth rates. Tag retention to 180 days was 100% for dorsal implantation, 83.0% with 8‐mm tags in the operculum, 97.5% with 8‐mm tags in the abdomen, and 99.6% with 12‐mm tags in the abdomen. Retention of opercular tags was positively related to size at tagging. Tag loss was independent of whether fish were single‐ or double‐tagged. Double tagging with one full‐ and one half‐duplex PIT tag in different body locations would hedge against data loss relative to single tagging, especially for longer‐lived and iteroparous species where tag loss through time is more likely.

Morphological Comparison of the Chesapeake Logperch Percina bimaculata with the Logperch Percina c. caprodes and Percina c. semifasciata in Pennsylvania - Jay R. Stauffer; Jonathan A. Freedman; Douglas P. Fischer; Robert W. Criswell (Fishes, 2023)
The Chesapeake logperch, Percina bimaculata (Halderman) has a disjunct distribution when compared to other species in the subgenus Percina. Members of this subgenus in Pennsylvania include Percina caprodes caprodes (Rafinesque), Percina caprodes semifasciata (DeKay), and P. bimaculata. Historically the Chesapeake logperch was known only from the Susquehanna River and Potomac River basins. Its range is now restricted to the Susquehanna River below Holtwood Dam and upper Chesapeake Bay. It has been extirpated from the Potomac River and the type locality near Columbia, PA. Attempts are being made to reintroduce it into tributaries of the Susquehanna River near Columbia, PA. We postulate that P. bimaculata diverged from a population of Percina caprodes semifasciata. A naked nape and the fact that both of these species do not occur above the fall line in Pennsylvania support such a relationship.

Biogeochemical cycling of chromium and chromium isotopes in the sub-tropical North Atlantic Ocean - Wenhao Wang; Heather Goring-Harford; Korinna Kunde; E. Malcolm S. Woodward; Maeve C. Lohan; Douglas P. Connelly; Rachael H. James (Frontiers in Marine Science, 2023)
Chromium (Cr) is a redox-sensitive element and because Cr isotopes are fractionated by redox and/or biological processes, the Cr isotopic composition of ancient marine sediments may be used to infer changes in past seawater oxygenation or biological productivity. While there appears to be a ‘global correlation’ between the dissolved Cr concentration and Cr isotopic composition of seawater, there is ongoing debate about the relative importance of external sources and internal cycling on shaping the distribution of dissolved Cr that needs to be resolved to validate the efficacy of using Cr isotopes as a paleo proxy. Here, we present full water column depth profiles of total dissolved Cr (Cr(VI)+Cr(III)) and dissolved Cr isotopes (δ 53 Cr), together with ancillary data, for three stations along a transect (GEOTRACES GApr08) across the sub-tropical North Atlantic. Concentrations of dissolved Cr ranged between 1.84 and 2.63 nmol kg -1 , and δ 53 Cr values varied from 1.06 to 1.42‰. Although atmospheric dust, hydrothermal vents and seabed sediments have the potential to modify the distribution of Cr in the oceans, based on our observations, there is no clear evidence for substantial input of Cr from these sources in our study region although benthic inputs of Cr may be locally important in the vicinity of hydrothermal vents. Subsurface waters (below the surface mixed layer to 700 m water depth) were very slightly depleted in Cr (by up to ~0.4 nmol kg -1 ), and very slightly enriched in heavy Cr isotopes (by up to ~0.14‰), relative to deeper waters and the lowest Cr concentrations and highest δ 53 Cr values coincided with lowest concentrations of colloidal (0.02 to 0.2 μm size fraction) Fe. We found no direct evidence for biological uptake of dissolved Cr in the oligotrophic euphotic zone or removal of Cr in modestly oxygen depleted waters (O 2 concentrations ~130 μmol kg -1 ). Rather, we suggest removal of Cr (probably in the form of Cr(III)) in subsurface waters is associated with the formation of colloid aggregates of Fe-(oxyhydr)oxides. This process is likely enhanced by the high lithogenic particle load in this region, and represents a previously unrecognized export flux of Cr. Regeneration of Cr in deeper waters leads to subtly increased levels of Cr alongside decreased δ 53 Cr values at individual sites, but this trend is more obvious at the global scale, with δ 53 Cr values decreasing with increasing radiocarbon age of deep waters, from 1.16 ± 0.10‰ (1SD, n=11) in deep Atlantic waters to 0.77 ± 0.10‰ (1SD, n=25) in deep Pacific waters. Removal of relatively isotopically light Cr from subsurface waters onto particulate material and regeneration of this Cr back into the dissolved phase in deep waters partly accounts for the systematic relationship between δ 53 Cr and Cr concentrations in seawater discussed by other studies.

Multiproxy reconstruction of late quaternary upper ocean temperature in the subtropical southwestern Atlantic - Joana F. Cruz; Ioanna Bouloubassi; Arnaud Huguet; Alice M.S. Rodrigues; Thiago P. Santos; Igor M. Venancio; Douglas Lessa; Rodrigo L. Sobrinho; Rodrigo A. Nascimento; Marcelo C. Bernardes (Quaternary Science Reviews, 2023)

Dairy Food Intake Is Not Associated With Frailty in Adults From the Framingham Heart Study - Anna C. Siefkas; Courtney L. Millar; Alyssa B. Dufour; Douglas P. Kiel; Paul F. Jacques; Marian T. Hannan; Shivani Sahni (Journal of the Academy of Nutrition and Dietetics, 2023)

Efficacy of two intermittent cooling strategies during prolonged work-rest intervals in the heat with personal protective gear compared with a control condition - Sean P. Langan; Ciara N. Manning; Margaret C. Morrissey; Tushar Gulati; Srinivas Laxminarayan; Jaques Reifman; Douglas J. Casa (European Journal of Applied Physiology, 2023)

Metabolomic changes associated with chronic arsenic exposure in a Bangladeshi population - Haotian Wu; Vrinda Kalia; Megan M. Niedzwiecki; Marianthi-Anna Kioumourtzoglou; Brandon Pierce; Vesna Ilievski; Jeff Goldsmith; Dean P. Jones; Ana Navas-Acien; Douglas I. Walker; Mary V. Gamble (Chemosphere, 2023)

Enhancing UAV images to improve the observation of submerged whales using a water column correction method - Alexandra Jones; Eleanor Bruce; Kevin P. Davies; Douglas H. Cato (Marine Mammal Science, 2023)

Attenuation of Pb and Sb in shooting range soils by Fe amendments - Amanda J. Barker; Thomas A. Douglas; Karen J. Spaleta; Tom P. Trainor (Chemosphere, 2023)

Effects of common antiepileptic drugs on teleost fishes - Arash Salahinejad; Denis Meuthen; Anoosha Attaran; Douglas P. Chivers; Maud C.O. Ferrari (Science of The Total Environment, 2023)

Glacier contribution to lowland streamflow: A multi-year, daily geochemical hydrograph separation study in subarctic Alaska - Tiffany A. Gatesman; Anna K. Liljedahl; Thomas A. Douglas; Matvey V. Debolskiy; Thomas P. Trainor; Anne Gädeke (Chemical Geology, 2023)

Spatial variation on the abundance of a threatened South American large herbivore using spatiotemporally replicated drone surveys - Ismael V. Brack; Andreas Kindel; Douglas O. Berto; José L. P. Cordeiro; Igor P. Coelho; José J. Lahoz-Monfort; Luiz F. B. de Oliveira (Biodiversity and Conservation, 2023)

Circulating interleukin-37 declines with aging in healthy humans: relations to healthspan indicators and IL37 gene SNPs - Vienna E. Brunt; Akpevweoghene P. Ikoba; Brian P. Ziemba; Dov B. Ballak; Alexander Hoischen; Charles A. Dinarello; Marissa A. Ehringer; Douglas R. Seals (GeroScience, 2023)

Genetic analysis of North American Phragmites australis guides management approaches - Denise L. Lindsay; Joanna Freeland; Ping Gong; Xin Guan; Nathan E. Harms; Kurt P. Kowalski; Richard F. Lance; Dong-Ha Oh; Bradley T. Sartain; Douglas L. Wendell (Aquatic Botany, 2023)

Progress towards reestablishing Latin America as a major pearl producing region: A review - Pedro E. Saucedo; Douglas McLaurin; César Lodeiros; Luis Freites; Luis León; Jorge I. Cáceres‐Puig; Marcos C. P. Albuquerque; Paul C. Southgate; Héctor Acosta‐Salmon (Reviews in Aquaculture, 2023)
Globally, pearl culture is a profitable sector generating significant export incomes for producer countries, as well as livelihood opportunities for local communities. Latin America has a long history as a pearl producer from extensive fisheries that date back to the 15th century. The presence of pearl oyster beds on the Pacific and Caribbean coasts of many Latin American countries was a major incentive for colonisation of the region and subsequent social and economic development of areas in the Gulf of California and the Caribbean. This review presents the historic background of the pearl fishery in this region since the arrival of the Spanish in the 16th century, describes the current status of pearl culture in Latin America, and outlines future opportunities for sector development. Information on the current status of pearl culture in Latin American countries is divided between two major categories: commercial and pilot‐scale. Commercial pearl production currently occurs only in Mexico and production updates are provided for bead‐nucleated, half pearls (mabé) and non‐nucleated (keshi) pearls from the two pearl farms operating in the Gulf of California. The second category comprises countries whose pearling activities were relevant in the past (Venezuela, Panama) and others that are emerging, but still maintain pilot‐scale production of mabé pearls using Pteria sterna (Ecuador, Peru), Pinctada mazatlanica (Panama) and Pteria hirundo (Brazil). Finally, this review discusses future prospects for pearl culture in Latin America, analysing technology gaps and challenges to be addressed if the cultured pearl sector is to achieve its full potential in this region.

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda - Weston M. Eaton; Morey Burnham; Tahnee Robertson; J. G. Arbuckle; Kathryn J. Brasier; Mark E. Burbach; Sarah P. Church; Georgia Hart-Fredeluces; Douglas Jackson-Smith; Grace Wildermuth; Katherine N. Canfield; S. Carolina Córdova; et al. (Socio-Ecological Practice Research, 2022)
Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusion interests through engagement, while implied in key conceptual frameworks, remain underexplored in scholarly work and collaborative practice alike. A second line of inquiry relates to research–practice gaps. While both the practice of doing engagement work and scholarly research on the efficacy of engagement is on the rise, there is little concerted interplay among ‘on-the-ground’ practitioners and scholarly researchers. This means scientific research often misses or ignores insight grounded in practical and experiential knowledge, while practitioners are disconnected from potentially useful scientific research on stakeholder engagement. A third set of questions concerns gaps in empirical understanding of the efficacy of engagement processes and includes inquiry into how different engagement contexts and process features affect a range of behavioral, cognitive, and decision-making outcomes. Because of these gaps, a cohesive and actionable research agenda for stakeholder engagement research and practice in working landscapes remains elusive. In this review article, we present a co-produced research agenda for stakeholder engagement in working landscapes. The co-production process involved professionally facilitated and iterative dialogue among a diverse and international group of over 160 scholars and practitioners through a yearlong virtual workshop series. The resulting research agenda is organized under six cross-cutting themes: (1) Justice, Equity, Diversity, and Inclusion; (2) Ethics; (3) Research and Practice; (4) Context; (5) Process; and (6) Outcomes and Measurement. This research agenda identifies critical research needs and opportunities relevant for researchers, practitioners, and policymakers alike. We argue that addressing these research opportunities is necessary to advance knowledge and practice of stakeholder engagement and to support more just and effective engagement processes in working landscapes.

Characterizing the Biological Community before and after Partial Removal of an Offshore Gas Platform in the Northwestern Gulf of Mexico - Michelle A. Johnston; Marissa F. Nuttall; Emma L. Hickerson; Kelly O’Connell; Raven D. Blakeway; John A. Embesi; Jimmy MacMillan; Douglas Peter; George P. Schmahl (Environmental Management, 2022)

Hydraulic, Chemical, and Vegetation Characteristics of the Corridor Creek Wetland Filter: Implications for Biopolishing Efficiency - B. S. Sherman; C. Drury; G. B. Douglas; G. N. Rees; G. Miller; S. Perryman; J. Gallant; M. G. Trefry; M. Iles; P. Davey (Mine Water and the Environment, 2022)

Morphological Analysis of a Nearshore Nourishment along the Atlantic Coast of New Jersey, USA - Sean P. McGill; Brian D. Harris; Brian C. McFall; Douglas R. Krafft; Rachel L. Bain; Nicholas R. Olsen; Ian W. Conery; Monica A. Chasten (Journal of Marine Science and Engineering, 2022)
Nearshore nourishment is a common coastal flood risk management technique that can be constructed beneficially by using dredged sediment from navigation channels. A nearshore nourishment project was completed during the summer of 2021 in Harvey Cedars, NJ, USA, with 67,500 m3 of dredged sediment from Barnegat Inlet placed along approximately 450 m of beach in a depth of 3–4 m. In situ instruments were installed to monitor hydrodynamic conditions before and after dredged material placement, and nine topographic and bathymetric surveys were conducted to monitor nearshore morphological response to the nourishment. Shoreline location was extracted from satellite imagery using CoastSat software to compare historical trends to the shoreline response after construction. Seven months after construction, 40% of the nearshore nourishment was transported from the initial footprint and the centroid of the nourishment migrated towards shore and alongshore (north). The sheltering capacity of the nearshore berm appears to have captured an additional 58% of the placed volume from the longshore transport system and the beach width onshore of the placement increased by 10.9 m. Measured data, satellite imagery analysis, and rapid predictions all indicate that the nearshore nourishment at Harvey Cedars had a positive impact on the adjacent beach.

Riverine drift communities during larval fish dispersal over multiple recruitment years - Joseph P. Receveur; Alberto Doretto; Edward A. Baker; Douglas L. Larson; John M. Bauman; Ryan Walquist; M. Eric Benbow; Kim T. Scribner (Hydrobiologia, 2022)

Seasonal Mass Migration of Water Boatmen (Hemiptera: Corixidae) as a Wetland–River Linkage and Dietary Subsidy to Riverine Fish - Stephen H. Srayko; Timothy D. Jardine; Iain D. Phillips; Douglas P. Chivers (Ecosystems, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Exploring the impact of spatial correlations of earthquake ground motions in the catastrophe modelling process: a case study for Italy - E. Schiappapietra; S. Stripajová; P. Pažák; J. Douglas; G. Trendafiloski (Bulletin of Earthquake Engineering, 2022)
Catastrophe models are important tools to provide proper assessment and financial management of earthquake-related emergencies, which still create the largest protection gap across all perils. Earthquake catastrophe models include three main components, namely: (1) the earthquake hazard model, (2) the exposure model and, (3) the vulnerability model. Simulating spatially distributed ground-motion fields within either deterministic or probabilistic seismic hazard assessments poses a major challenge when site-related financial protection products are required. In this framework, we develop ad hoc correlation models for different Italian regions (specifically northern, central and southern Italy) and thereafter we perform both deterministic scenario-based and probabilistic event-based hazard and risk assessments in order to advance the understanding of spatial correlations within the catastrophe modelling process. We employ the OpenQuake engine for our calculations. This is an open-source tool suitable for accounting for the spatial correlation of earthquake ground-motion residuals. Our outcomes, albeit preliminary, demonstrate the importance of considering not only the spatial correlation of ground motions, but also its associated uncertainty in risk analyses. Although loss exceedance probability curves for the return periods of interest for the (re)insurance industry show similar trends, both hazard and risk footprints in terms of average annual losses feature less noisy and more realistic patterns if spatial correlation is taken into account. Such results will have implications for (re)insurance companies evaluating the risk to high-value civil engineering infrastructures.

A new approach to the classification of carcinogenicity - John E. Doe; Alan R. Boobis; Samuel M. Cohen; Vicki L. Dellarco; Penelope A. Fenner-Crisp; Angelo Moretto; Timothy P. Pastoor; Rita S. Schoeny; Jennifer G. Seed; Douglas C. Wolf (Archives of Toxicology, 2022)
Concern over substances that may cause cancer has led to various classification schemes to recognize carcinogenic threats and provide a basis to manage those threats. The least useful schemes have a binary choice that declares a substance carcinogenic or not. This overly simplistic approach ignores the complexity of cancer causation by considering neither how the substance causes cancer, nor the potency of that mode of action. Consequently, substances are classified simply as “carcinogenic”, compromising the opportunity to properly manage these kinds of substances. It will likely be very difficult, if not impossible, to incorporate New Approach Methodologies (NAMs) into binary schemes. In this paper we propose a new approach cancer classification scheme that segregates substances by both mode of action and potency into three categories and, as a consequence, provides useful guidance in the regulation and management of substances with carcinogenic potential. Examples are given, including aflatoxin (category A), trichlorethylene (category B), and titanium dioxide (category C), which demonstrate the clear differentiation among these substances that generate appropriate levels of concern and management options.

Once a reservoir, always a reservoir? Seasonality affects the pathogen maintenance potential of amphibian hosts - Mark Q. Wilber; Michel E. B. Ohmer; Karie A. Altman; Laura A. Brannelly; Brandon C. LaBumbard; Emily H. Le Sage; Nina B. McDonnell; Aura Y. Muñiz Torres; Caitlin L. Nordheim; Ferdinand Pfab; Corinne L. Richards‐Zawacki; Louise A. Rollins‐Smith; et al. (Ecology, 2022)
Host species that can independently maintain a pathogen in a host community and contribute to infection in other species are important targets for disease management. However, the potential of host species to maintain a pathogen is not fixed over time, and an important challenge is understanding how within‐ and across‐season variability in host maintenance potential affects pathogen persistence over longer time scales relevant for disease management (e.g., years). Here, we sought to understand the causes and consequences of seasonal infection dynamics in leopard frogs ( Rana sphenocephala and Rana pipiens ) infected with the fungal pathogen Batrachochytrium dendrobatidis ( Bd ). We addressed three questions broadly applicable to seasonal host–parasite systems. First, to what degree are observed seasonal patterns in infection driven by temperature‐dependent infection processes compared to seasonal host demographic processes? Second, how does seasonal variation in maintenance potential affect long‐term pathogen persistence in multi‐host communities? Third, does high deterministic maintenance potential relate to the long‐term stochastic persistence of pathogens in host populations with seasonal infection dynamics? To answer these questions, we used field data collected over 3 years on >1400 amphibians across four geographic locations, laboratory and mesocosm experiments, and a novel mathematical model. We found that the mechanisms that drive seasonal prevalence were different from those driving seasonal infection intensity. Seasonal variation in Bd prevalence was driven primarily by changes in host contact rates associated with breeding migrations to and from aquatic habitat. In contrast, seasonal changes in infection intensity were driven by temperature‐induced changes in Bd growth rate. Using our model, we found that the maintenance potential of leopard frogs varied significantly throughout the year and that seasonal troughs in infection prevalence made it unlikely that leopard frogs were responsible for long‐term Bd persistence in these seasonal amphibian communities, highlighting the importance of alternative pathogen reservoirs for Bd persistence. Our results have broad implications for management in seasonal host–pathogen systems, showing that seasonal changes in host and pathogen vital rates, rather than the depletion of susceptible hosts, can lead to troughs in pathogen prevalence and stochastic pathogen extirpation.

Echofilter: A Deep Learning Segmention Model Improves the Automation, Standardization, and Timeliness for Post-Processing Echosounder Data in Tidal Energy Streams - Scott C. Lowe; Louise P. McGarry; Jessica Douglas; Jason Newport; Sageev Oore; Christopher Whidden; Daniel J. Hasselman (Frontiers in Marine Science, 2022)
Understanding the abundance and distribution of fish in tidal energy streams is important for assessing the risks presented by the introduction of tidal energy devices into the habitat. However, tidal current flows suitable for tidal energy development are often highly turbulent and entrain air into the water, complicating the interpretation of echosounder data. The portion of the water column contaminated by returns from entrained air must be excluded from data used for biological analyses. Application of a single algorithm to identify the depth-of-penetration of entrained air is insufficient for a boundary that is discontinuous, depth-dynamic, porous, and varies with tidal flow speed. Using a case study at a tidal energy demonstration site in the Bay of Fundy, we describe the development and application of deep machine learning models with a U-Net based architecture that produce a pronounced and substantial improvement in the automated detection of the extent to which entrained air has penetrated the water column. Our model, Echofilter, was found to be highly responsive to the dynamic range of turbulence conditions and sensitive to the fine-scale nuances in the boundary position, producing an entrained-air boundary line with an average error of 0.33 m on mobile downfacing and 0.5–1.0 m on stationary upfacing data, less than half that of existing algorithmic solutions. The model’s overall annotations had a high level of agreement with the human segmentation, with an intersection-over-union score of 99% for mobile downfacing recordings and 92–95% for stationary upfacing recordings. This resulted in a 50% reduction in the time required for manual edits when compared to the time required to manually edit the line placement produced by the currently available algorithms. Because of the improved initial automated placement, the implementation of the models permits an increase in the standardization and repeatability of line placement.

Social integration of translocated wildlife: a case study of rehabilitated and released elephant calves in northern Kenya - Shifra Z. Goldenberg; Stephen M. Chege; Nelson Mwangi; Ian Craig; David Daballen; Iain Douglas-Hamilton; Nadine Lamberski; Moses Lenaipa; Reuben Lendira; Colman Lesowapir; Lekilia P. Lokooria; Mathew Mutinda; et al. (Mammalian Biology, 2022)
Conservation translocations have the potential to strengthen populations of threatened and endangered species, but facilitating integration of translocated individuals with resident populations remains a substantial challenge. Developing functional social relationships like cooperative partnerships or establishing clear dominance hierarchies may be critical to integration of released individuals. Developing such relationships has not received much attention in translocation research, especially for long-lived, socially complex animals for which establishment and navigation of social environments is often a lengthy process that requires sustained monitoring to understand. Here, we present a case study of the social associations of African savannah elephant ( Loxodonta africana ) calves that have been rehabilitated and released into a fenced wildlife sanctuary in northern Kenya with a resident population of elephants. We use focal follows of interactions pre-release and GPS tracking post-release to quantify social associations of calves with each other and with resident elephants at the release site. We demonstrate how this approach supports translocation monitoring by capturing temporal trends in social patterns within and between release cohorts and among released elephants and wild elephants already resident at the site during a transitional soft release period. Our results show that initial post-release social behavior of rehabilitated calves is related to histories of interaction with familiar individuals and cohort membership and that released calves increased their associations with residents over time. This information provides new behavioral insights for guiding elephant release projects, like the strength of relationships within and among release cohorts, the time to integration with the resident population, and the occurrence and increased incidence of societal fission–fusion. Further, this study provides an example of the utility of animal behavior research to achieve and assess progress towards conservation objectives, and to develop monitoring tools for conservation managers.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Speciation with gene flow in a narrow endemic West Virginia cave salamander (Gyrinophilus subterraneus) - Evan H. Campbell Grant; Kevin P. Mulder; Adrianne B. Brand; Douglas B. Chambers; Addison H. Wynn; Grace Capshaw; Matthew L. Niemiller; John G. Phillips; Jeremy F. Jacobs; Shawn R. Kuchta; Rayna C. Bell (Conservation Genetics, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

How thermal challenges change gene regulation in the songbird brain and gonad: Implications for sexual selection in our changing world - Sara E. Lipshutz; Clara R. Howell; Aaron M. Buechlein; Douglas B. Rusch; Kimberly A. Rosvall; Elizabeth P. Derryberry (Molecular Ecology, 2022)
In a rapidly warming world, exposure to high temperatures may impact fitness, but the gene regulatory mechanisms that link sublethal heat to sexually selected traits are not well understood, particularly in endothermic animals. Our experiment used zebra finches ( Taeniopygia guttata ), songbirds that experience extreme temperature fluctuations in their native Australia. We exposed captive males to an acute thermal challenge (43°C) compared with thermoneutral (35°C) and lower (27°C) temperatures. We found significantly more heat dissipation behaviours at 43°C, a temperature previously shown to reduce song production and fertility, and more heat retention behaviours at 27°C. Next, we characterized transcriptomic responses in tissues important for mating effort—the posterior telencephalon, for its role in song production, and the testis, for its role in fertility and hormone production. Differential expression of hundreds of genes in the testes, but few in the brain, suggests the brain is less responsive to extreme temperatures. Nevertheless, gene network analyses revealed that expression related to dopaminergic signalling in the brain covaried with heat dissipation behaviours, providing a mechanism by which temporary thermal challenges may alter motivational circuits for song production. In both brain and testis, we observed correlations between thermally sensitive gene networks and individual differences in thermoregulatory behaviour. Although we cannot directly relate these gene regulatory changes to mating success, our results suggest that individual variation in response to thermal challenges could impact sexually selected traits in a warming world.

Influences of seasonality and habitat quality on Great Lakes coastal wetland fish community composition and diets - Sara N. Diller; Anna M. Harrison; Kurt P. Kowalski; Valerie J. Brady; Jan J. H. Ciborowski; Matthew J. Cooper; Joshua D. Dumke; Joseph P. Gathman; Carl R. Ruetz; Donald G. Uzarski; Douglas A. Wilcox; Jeffrey S. Schaeffer (Wetlands Ecology and Management, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Pupillary responses to differences in luminance, color and set size - Julia Oster; Jeff Huang; Brian J. White; Ralph Radach; Laurent Itti; Douglas P. Munoz; Chin-An Wang (Experimental Brain Research, 2022)

Degradation of Sugarcane Bagasse by Cockroach Consortium Bacteria - Danielle B. Carvalho; Douglas A. Paixão; Gabriela F. Persinoti; Junio Cota; Sarita C. Rabelo; Adriana Grandis; Amanda P. Souza; Marcos Buckeridge; Roberto Ruller; Leticia M. Zanphorlin; Fabio M. Squina; Joao P. L. F. Cairo; et al. (BioEnergy Research, 2022)

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Extent of Sedge-Grass Meadow in a Lake Michigan Drowned River Mouth Wetland Dictated by Topography and Lake Level - Douglas A. Wilcox; John A. Bateman; Kurt P. Kowalski; James E. Meeker; Nicole Dunn (Wetlands, 2022)

Hereditary cancer panel testing challenges and solutions for the latinx community: costs, access, and variants - Michael P. Douglas; Grace A. Lin; Julia R. Trosman; Kathryn A. Phillips (Journal of Community Genetics, 2022)
Hereditary breast and ovarian cancers (HBOCs) are common among the Latinx population, and risk testing is recommended using multi-gene hereditary cancer panels (HCPs). However, little is known about how payer reimbursement and out-of-pocket expenses impact provider ordering of HCP in the Latinx population. Our objective is to describe key challenges and possible solutions for HCP testing in the Latinx population. As part of a larger study, we conducted semi-structured interviews with key provider informants (genetic counselors, oncologist, nurse practitioner) from safety-net institutions in the San Francisco Bay Area. We used a deductive thematic analysis approach to summarize themes around challenges and possible solutions to facilitating HCP testing in Latinx patients. We found few financial barriers for HCP testing for the Latinx population due to laboratory patient assistance programs that cover testing at low or no cost to patients. However, we found potential challenges related to the sustainability of low-cost testing and out-of-pocket expenses for patients, access to cascade testing for family members, and pathogenic variants specific to Latinx. Providers questioned whether current laboratory payment programs that decrease barriers to testing are sustainable and suggested solutions for accessing cascade testing and ensuring variants specific to the Latinx population were included in testing. The use of laboratories with payment assistance programs reduces barriers to HCP testing among the US population; however, other barriers are present that may impact testing use in the Latinx population and must be addressed to ensure equitable access to HCP testing for this population.

Pazopanib for severe bleeding and transfusion-dependent anemia in hereditary hemorrhagic telangiectasia - Joseph G. Parambil; James R. Gossage; Keith R. McCrae; Troy D. Woodard; K. V. Narayanan Menon; Kasi L. Timmerman; Douglas P. Pederson; Dennis L. Sprecher; Hanny Al-Samkari (Angiogenesis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Emerging new climate extremes over Europe - Albert Ossó; Richard P. Allan; Ed Hawkins; Len Shaffrey; Douglas Maraun (Climate Dynamics, 2022)
Human society and natural systems are intrinsically adapted to the local climate mean and variability. Therefore, changes relative to the local expected variability are highly relevant for assessing impact and planning for adaptation as the climate changes. We analyse the emerging climate signal relative to the diagnosed internal variability (signal-to-noise ratio, S/N) of a set of recently published climate indices over Europe. We calculate the signal-to-noise ratio with respect to a recent baseline (1951–1983) which relates to recent societal experience. In this framework, we find that during the 2000–2016 period, many areas of Europe already experienced significant changes in climate extremes, even when compared to this recent period which is within living memory. In particular, the S/N of extreme temperatures is larger than 1 and 2 over 34% and 4% of Europe, respectively. We also find that about 15% of Europe is experiencing more intense winter precipitation events, while in summer, 7% of Europe is experiencing stronger drought-inducing conditions.

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Amikacin for the treatment of carbapenem-resistant Klebsiella pneumoniae infections: clinical efficacy and toxicity - Diógenes Rodrigues; Giulia Soska Baldissera; Douglas Mathos; Aline Sartori; Alexandre P. Zavascki; Maria Helena Rigatto (Brazilian Journal of Microbiology, 2021)

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Disturbance cues facilitate associative learning of predators in a coral reef fish - Michael S. Pollock; Zoe Hoyle; Mark I. Mccormick; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2021)

The codification of hazard and its impact on the hazard versus risk controversy - John E. Doe; Alan R. Boobis; Samuel M. Cohen; Vicki L. Dellarco; Penelope A. Fenner-Crisp; Angelo Moretto; Timothy P. Pastoor; Rita S. Schoeny; Jennifer G. Seed; Douglas C. Wolf (Archives of Toxicology, 2021)
The long running controversy about the relative merits of hazard-based versus risk-based approaches has been investigated. There are three levels of hazard codification: level 1 divides chemicals into dichotomous bands of hazardous and non-hazardous; level 2 divides chemicals into bands of hazard based on severity and/or potency; and level 3 places each chemical on a continuum of hazard based on severity and/or potency. Any system which imposes compartments onto a continuum will give rise to issues at the boundaries, especially with only two compartments. Level 1 schemes are only justifiable if there is no variation in severity, or potency or if there is no threshold. This is the assumption implicit in GHS/EU classification for carcinogenicity, reproductive toxicity and mutagenicity. However, this assumption has been challenged. Codification level 2 hazard assessments offer a range of choices and reduce the built-in conflict inherent in the level 1 process. Level 3 assessments allow a full range of choices between the extremes and reduce the built-in conflict even more. The underlying reason for the controversy between hazard and risk is the use of level 1 hazard codification schemes in situations where there are ranges of severity and potency which require the use of level 2 or level 3 hazard codification. There is not a major difference between level 2 and level 3 codification, and they can both be used to select appropriate risk management options. Existing level 1 codification schemes should be reviewed and developed into level 2 schemes where appropriate.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

The quorum‐sensing systems of Vibrio campbellii DS40M4 and BB120 are genetically and functionally distinct - Chelsea A. Simpson; Blake D. Petersen; Nicholas W. Haas; Logan J. Geyman; Aimee H. Lee; Ram Podicheti; Robert Pepin; Laura C. Brown; Douglas B. Rusch; Michael P. Manzella; Kai Papenfort; Julia C. van Kessel (Environmental Microbiology, 2021)
Summary Vibrio campbellii BB120 (previously classified as Vibrio harveyi ) is a fundamental model strain for studying quorum sensing in vibrios. A phylogenetic evaluation of sequenced Vibrio strains in Genbank revealed that BB120 is closely related to the environmental isolate V. campbellii DS40M4. We exploited DS40M4's competence for exogenous DNA uptake to rapidly generate greater than 30 isogenic strains with deletions of genes encoding BB120 quorum‐sensing system homologues. Our results show that the quorum‐sensing circuit of DS40M4 is distinct from BB120 in three ways: (i) DS40M4 does not produce an acyl homoserine lactone autoinducer but encodes an active orphan LuxN receptor, (ii) the quorum regulatory small RNAs (Qrrs) are not solely regulated by autoinducer signalling through the response regulator LuxO and (iii) the DS40M4 quorum‐sensing regulon is much smaller than BB120 (~100 genes vs. ~400 genes, respectively). Using comparative genomics to expand our understanding of quorum‐sensing circuit diversity, we observe that conservation of LuxM/LuxN proteins differs widely both between and within Vibrio species. These strains are also phenotypically distinct: DS40M4 exhibits stronger interbacterial cell killing, whereas BB120 forms more robust biofilms and is bioluminescent. These results underscore the need to examine wild isolates for a broader view of bacterial diversity in the marine ecosystem.

Collaborative Automation and IoT Technologies for Coastal Ocean Observing Systems - Patrizio Mariani; Ralf Bachmayer; Sokol Kosta; Ermanno Pietrosemoli; Murat V. Ardelan; Douglas P. Connelly; Eric Delory; Jay S. Pearlman; George Petihakis; Fletcher Thompson; Alessandro Crise (Frontiers in Marine Science, 2021)
Coastal observing systems are typically nationally funded and built around national priorities. As a result, there are presently significant differences between countries in terms of sustainability, observing capacity and technologies, as well as methods and research priorities. Ocean observing systems in coastal areas must now move toward an integrated, multidisciplinary and multiscale system of systems, where heterogeneity should be exploited to deliver fit-for-purpose products that answer the diversity and complexity of the requirements from stakeholders and end-users. Essential elements of such distributed observation systems are the use of machine-to-machine communication, data fusion and processing applying recent technological developments for the Internet of Things (IoT) toward a common cyberinfrastructure. This perspective paper illustrates some of the challenges for sustained coastal observations and provides details on how to address present gaps. We discuss the role of collaborative robotics between unmanned platforms in coastal areas and the methods to benefit from IoT technologies. Given present trends in cost-effective solutions in ocean sensors and electronics, and methods for marine automation and communication, we consider that a distributed observation system can effectively provide timely information in coastal regions around the world, including those areas that are today poorly observed (e.g., developing countries). Adaptation in space and time of the sensing nodes, and the flexibility in handling different sensing platforms can provide to the system the ability to quickly respond to the rapid changes in oceanic and climatic processes, as well as to promptly respond to evolving stakeholder and end-user requirements.

Exposure to degraded coral habitat depresses oxygen uptake rate during exercise of a juvenile reef fish - Adam T. Downie; Caroline M. Phelps; Rhondda Jones; Jodie L. Rummer; Douglas P. Chivers; Maud C. O. Ferrari; Mark I. McCormick (Coral Reefs, 2021)

Nitrate nutrition increases foliar levels of nitric oxide and waterlogging tolerance in soybean - Cristiane Jovelina Da-Silva; Eduardo P. Shimoia; Douglas A. Posso; Amanda A. Cardoso; Timothy A. Batz; Ana Claudia B. Oliveira; Luciano do Amarante (Acta Physiologiae Plantarum, 2021)

Adult male Cuvier's beaked whales ( Ziphius cavirostris ) engage in prolonged bouts of synchronous diving - William R. Cioffi; Nicola J. Quick; Heather J. Foley; Danielle M. Waples; Zachary T. Swaim; Jeanne M. Shearer; Daniel L. Webster; Ari S. Friedlaender; Brandon L. Southall; Robin W. Baird; Douglas P. Nowacek; Andrew J. Read (Marine Mammal Science, 2021)
Studies of the social behavior of Cuvier's beaked whales ( Ziphius cavirostris ) are challenging because of their deep‐water habitat usually far from shore and the limited time they spend at the surface. The sociality of these deepest diving mammals is of interest, however, especially for our understanding of how social systems evolve in extreme habitats. High levels of scarring suggest that males compete agonistically for access to females and so we predicted that associations among adult males would be unstable due to competitive exclusion. We tested this prediction by evaluating the diving behavior of animals within social groups off Cape Hatteras, North Carolina, considering diving synchrony a proxy for group membership. Using data from satellite‐linked depth‐recording tags, we found that adult male–male pairs showed extended periods of synchrony in diving behavior, while all pairs that included an adult male with an individual of another age and/or sex dove synchronously for less than a day. We assessed three hypotheses to explain these surprising results: sexual segregation; extended bouts of male–male competition; and the presence of male alliances. Finally, we considered testable predictions to distinguish among these explanations.

Computational fluid dynamics of flow regime and hydrodynamic forces generated by a gliding North Atlantic right whale ( Eubalaena glacialis ) - Chen‐Yi Wu; Douglas P. Nowacek; Anna E. Nousek‐McGregor; Ross McGregor; Laurens E. Howle (Marine Mammal Science, 2021)
Accurate estimates of drag on marine animals are required to investigate the locomotive cost, propulsive efficiency, and the impacts of entanglement if the animal is carrying fishing gear. In this study, we performed computational fluid dynamics analysis of a 10 m (length over all) right whale to obtain baseline measurements of drag on the animal. Swimming speeds covering known right whale speed range (0.125 m/s to 8 m/s) were tested. We found a weak dependence between drag coefficient and Reynolds number. At a swimming speed of 2 m/s, we analyzed the boundary layer thicknesses, the flow regimes, and drag components. We found the thickest boundary layer at the lateral sides of the peduncle, whereas the boundary layer thickness over the outer part of the flukes was less than 1.7 cm. Laminar flow occurred over the anterior ~0.6 LoA and turbulent flow from ~0.8 LoA to the fluke notch. On the surfaces of the flukes outside of the body wake region, flow was laminar. Our most significant finding is that the drag coefficient (0.0071–0.0059) of a right whale for swimming speeds ranging from 0.25 m/s to 2 m/s is approximately twice that of many previous estimates for cetaceans.

Submarine groundwater discharge drives nitrous oxide source/sink dynamics in a metropolitan estuary - Michael J. Reading; Douglas R. Tait; Damien T. Maher; Luke C. Jeffrey; Rogger E. Correa; James P. Tucker; Haile A. Shishaye; Isaac R. Santos (Limnology and Oceanography, 2021)
Coastal waterways can be significant sources of the potent greenhouse gas nitrous oxide (N 2 O) due to nitrogen inputs and eutrophication. Here, we quantify groundwater derived N 2 O inputs and atmospheric emissions within a modified urban embayment (Sydney Harbour, Australia). Overall, we found low N 2 O saturation (91–171%) and air–water fluxes (−2.2 to 24.6 μ mol m −2 d −1 ). Concentrations were highest in upstream brackish areas and a commercial/industrial subembayment. Dissolved inorganic nitrogen concentrations were low and inversely correlated to N 2 O throughout the harbor. N 2 O surface water dynamics were apparently driven by saline submarine groundwater discharge, as quantified by the radioisotope tracer radon‐222. Groundwater discharge was highest within the embayments and mangrove‐lined upper estuary. While groundwater was a net N 2 O source to surface waters, two upstream sub‐embayments featured groundwater N 2 O concentrations lower than surface water, suggesting a sink driven by surface waters recirculating in intertidal sediments. Surface‐water N 2 O was undersaturated within one upstream embayment, likely due to N 2 O consumption within sediments. Contrastingly, the downstream embayments featured higher groundwater N 2 O and accounted for 45% ± 21% of the groundwater N 2 O flux. Sydney Harbour was a net source of N 2 O to the atmosphere (mean 0.6 ± 0.3 μ mol m −2 d −1 ) with larger N 2 O fluxes occurring from relatively small areas. N 2 O emissions (expressed in CO 2 equilivents) were equivalent to 17% of CO 2 emission estimates from previous studies. The low N 2 O emissions in Sydney Harbour contrast with other modified estuaries which often emit higher N 2 O fluxes due to larger nitrogen inputs.

Copper and lead ion removal from wastewater using fava d’anta fodder (Dimorphandra gardneriana Tulasne) - Antônio H. Santana; José A. S. Araújo; Amanda M. S. Bento; Ana R. Santos; Leocácia G. Santos; Hiago de O. Gomes; José Galberto M. da Costa; Jorge Marcell C. Menezes; Henrique Douglas Melo Coutinho; Francisco José de P. Filho; Raimundo Nonato P. Teixeira (Environmental Geochemistry and Health, 2021)

Are populations of economically important bonefish and queen conch 'open' or 'closed' in the northern caribbean basin? - Marlis R. Douglas; Tyler K. Chafin; Julie E. Claussen; David P. Philipp; Michael E. Douglas (Marine Ecology, 2021)
Demographics of co‐occurring species can often be diagnosed through population genomic analyses of single nucleotide polymorphisms (SNPs). These data can define population structure, gene flow, and candidate regions in the genome that potentially reflect local adaptations. They can also gauge whether populations are demographically “open” or “closed” (i.e., with global or local recruitment). We derived SNPs from double‐digest restriction‐site associated DNA (ddRAD) to test the demographics of commercially important bonefish Albula vulpes ( N = 117) and queen conch Lobatus gigas ( N = 60) from two northeast Caribbean Basin islands (Grand Bahama to the north and Eleuthera to the south). Specifically, we tested the hypothesis that the strong west‐to‐east current in the Great Bahama Canyon is a vicariant barrier separating the two islands. We conducted Bayesian assignment tests on putatively neutral ( A. vulpes = 36,206 SNPs; L. gigas = 64,863) and highly differentiated outlier datasets ( A. vulpes = 123 and 79 SNPs; L. gigas = 88 and 51, respectively). For bonefish, results diagnosed asymmetrical gene flow and north‐south differentiation, as potentially driven by adult mobility and easterly currents. However, both analyses indicated genetic structure in conch, substantiating the vicariant hypothesis. These results provide templates for future research endeavors with these impacted species. Outlier loci, for example, can potentially place populations of each within a demographic continuum, rather than within a dichotomous “open/closed” framework, as well as diagnose “source” and “sink” populations, as herein. These methodologies can then be applied to co‐distributed species with similar but less well‐understood ecologies so as to evaluate basin‐wide trends in connectivity and local adaptation.

Connecting high‐throughput biodiversity inventories: Opportunities for a site‐based genomic framework for global integration and synthesis - Paula Arribas; Carmelo Andújar; Martin I. Bidartondo; Kristine Bohmann; Éric Coissac; Simon Creer; Jeremy R. deWaard; Vasco Elbrecht; Gentile F. Ficetola; Marta Goberna; Susan Kennedy; Henrik Krehenwinkel; et al. (Molecular Ecology, 2021)
High‐throughput sequencing (HTS) is increasingly being used for the characterization and monitoring of biodiversity. If applied in a structured way, across broad geographical scales, it offers the potential for a much deeper understanding of global biodiversity through the integration of massive quantities of molecular inventory data generated independently at local, regional and global scales. The universality, reliability and efficiency of HTS data can potentially facilitate the seamless linking of data among species assemblages from different sites, at different hierarchical levels of diversity, for any taxonomic group and regardless of prior taxonomic knowledge. However, collective international efforts are required to optimally exploit the potential of site‐based HTS data for global integration and synthesis, efforts that at present are limited to the microbial domain. To contribute to the development of an analogous strategy for the nonmicrobial terrestrial domain, an international symposium entitled “Next Generation Biodiversity Monitoring” was held in November 2019 in Nicosia (Cyprus). The symposium brought together evolutionary geneticists, ecologists and biodiversity scientists involved in diverse regional and global initiatives using HTS as a core tool for biodiversity assessment. In this review, we summarize the consensus that emerged from the 3‐day symposium. We converged on the opinion that an effective terrestrial Genomic Observatories network for global biodiversity integration and synthesis should be spatially led and strategically united under the umbrella of the metabarcoding approach. Subsequently, we outline an HTS‐based strategy to collectively build an integrative framework for site‐based biodiversity data generation.

Nitrogen cycling microbiomes are structured by plant mycorrhizal associations with consequences for nitrogen oxide fluxes in forests - Ryan M. Mushinski; Zachary C. Payne; Jonathan D. Raff; Matthew E. Craig; Sally E. Pusede; Douglas B. Rusch; Jeffrey R. White; Richard P. Phillips (Global Change Biology, 2021)
Volatile nitrogen oxides (N 2 O, NO, NO 2 , HONO, …) can negatively impact climate, air quality, and human health. Using soils collected from temperate forests across the eastern United States, we show microbial communities involved in nitrogen (N) cycling are structured, in large part, by the composition of overstory trees, leading to predictable N‐cycling syndromes, with consequences for emissions of volatile nitrogen oxides to air. Trees associating with arbuscular mycorrhizal (AM) fungi promote soil microbial communities with higher N‐cycle potential and activity, relative to microbial communities in soils dominated by trees associating with ectomycorrhizal (ECM) fungi. Metagenomic analysis and gene expression studies reveal a 5 and 3.5 times greater estimated N‐cycle gene and transcript copy numbers, respectively, in AM relative to ECM soil. Furthermore, we observe a 60% linear decrease in volatile reactive nitrogen gas flux (NO y ≡ NO, NO 2 , HONO) as ECM tree abundance increases. Compared to oxic conditions, gas flux potential of N 2 O and NO increase significantly under anoxic conditions for AM soil (30‐ and 120‐fold increase), but not ECM soil—likely owing to small concentrations of available substrate ( ) in ECM soil. Linear mixed effects modeling shows that ECM tree abundance, microbial process rates, and geographic location are primarily responsible for variation in peak potential NO y flux. Given that nearly all tree species associate with either AM or ECM fungi, our results indicate that the consequences of tree species shifts associated with global change may have predictable consequences for soil N cycling.

The gut microbiome–derived metabolite trimethylamine N-oxide modulates neuroinflammation and cognitive function with aging - Vienna E. Brunt; Thomas J. LaRocca; Amy E. Bazzoni; Zachary J. Sapinsley; Jill Miyamoto-Ditmon; Rachel A. Gioscia-Ryan; Andrew P. Neilson; Christopher D. Link; Douglas R. Seals (GeroScience, 2021)

Scenarios for Global Aquaculture and Its Role in Human Nutrition - Jessica A. Gephart; Christopher D. Golden; Frank Asche; Ben Belton; Cecile Brugere; Halley E. Froehlich; Jillian P. Fry; Benjamin S. Halpern; Christina C. Hicks; Robert C. Jones; Dane H. Klinger; David C. Little; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Correction to: Air Pollution and Adverse Pregnancy and Birth Outcomes: Mediation Analysis Using Metabolomic Profiles - Kosuke Inoue; Qi Yan; Onyebuchi A. Arah; Kimberly Paul; Douglas I. Walker; Dean P. Jones; Beate Ritz (Current Environmental Health Reports, 2020)

Dorsolateral prefrontal cortex hyperactivity during inhibitory control in children with ADHD in the antisaccade task - Juan Fernandez-Ruiz; Rebecca M. Hakvoort Schwerdtfeger; Nadia Alahyane; Donald C. Brien; Brian C. Coe; Douglas P. Munoz (Brain Imaging and Behavior, 2020)

Forget the audience: tadpoles release similar disturbance cues regardless of kinship or familiarity - Kevin R. Bairos-Novak; Adam L. Crane; Gabrielle H. Achtymichuk; Jonathan Hsin; Ita A. E. Rivera-Hernández; Olena M. Simko; Theresa E. Wrynn; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2020)

Physical drivers facilitating a toxigenic cyanobacterial bloom in a major Great Lakes tributary - Paul G. Matson; Gregory L. Boyer; Thomas B. Bridgeman; George S. Bullerjahn; Douglas D. Kane; Robert M. L. McKay; Katelyn M. McKindles; Heather A. Raymond; Brenda K. Snyder; Richard P. Stumpf; Timothy W. Davis (Limnology and Oceanography, 2020)
The Maumee River is the primary source for nutrients fueling seasonal Microcystis ‐dominated blooms in western Lake Erie's open waters though such blooms in the river are infrequent. The river also serves as source water for multiple public water systems and a large food services facility in northwest Ohio. On 20 September 2017, an unprecedented bloom was reported in the Maumee River estuary within the Toledo metropolitan area, which triggered a recreational water advisory. Here we (1) explore physical drivers likely contributing to the bloom's occurrence, and (2) describe the toxin concentration and bacterioplankton taxonomic composition. A historical analysis using 10‐years of seasonal river discharge, water level, and local wind data identified two instances when high‐retention conditions occurred over ≥ 10 d in the Maumee River estuary: in 2016 and during the 2017 bloom. Observation by remote sensing imagery supported the advection of cyanobacterial cells into the estuary from the lake during 2017 and the lack of an estuary bloom in 2016 due to a weak cyanobacterial bloom in the lake. A rapid‐response survey during the 2017 bloom determined levels of the cyanotoxins, specifically microcystins, in excess of recreational contact limits at sites within the lower 20 km of the river while amplicon sequencing found these sites were dominated by Microcystis . These results highlight the need to broaden our understanding of physical drivers of cyanobacterial blooms within the interface between riverine and lacustrine systems, particularly as such blooms are expected to become more prominent in response to a changing climate.

How a typical West African day in the future-climate compares with current-climate conditions in a convection-permitting and parameterised convection climate model - Rory G. J. Fitzpatrick; Douglas J. Parker; John H. Marsham; David P. Rowell; Lawrence S. Jackson; Declan Finney; Chetan Deva; Simon Tucker; Rachael Stratton (Climatic Change, 2020)
Current-climate precipitation and temperature extremes have been identified by decision makers in West Africa as among the more impactful weather events causing lasting socioeconomic damage. In this article, we use a plausible future-climate scenario (RCP8.5) for the end of the twenty-first century to explore the relative commonness of such extremes under global warming. The analysis presented considers what a typical day in the future climate will feel like relative to current extrema. Across much of West Africa, we see that the typical future-climate day has maximum and minimum temperatures greater than 99.5% of currently experienced values. This finding exists for most months but is particularly pronounced during the Boreal spring and summer. The typical future precipitation event has a daily rainfall rate greater than 95% of current storms. These findings exist in both a future scenario model run with and without parameterised convection, and for many of the Coupled Model Inter-comparison Project version 5 ensemble members. Additionally, agronomic monsoon onset is projected to occur later and have greater inter-annual variability in the future. Our findings suggest far more extreme conditions in future climate over West Africa. The projected changes in temperature and precipitation could have serious socioeconomic implications, stressing the need for effective mitigation given the potential lack of adaptation pathways available to decision makers.

Traditional approaches to estimate length at first maturity ( L 50 ) retrieve better results than alternative ones in a Neotropical heptapterid - Bruno E. Soares; Thiago F. Barros; Danielly T. Hashiguti; Douglas C. Pereira; Karina C. F. Ferreira; Érica P. Caramaschi (Journal of Fish Biology, 2020)
Length at first maturity ( L 50 ) is an important tool for the management and conservation of fish populations. Traditional approaches based on macroscopic and microscopic maturity staging exhibit high accuracy and precision, while alternative approaches ( e.g. , I g ‐based staging, stanza changing point) are less resource‐demanding. Herein, we compare four approaches to estimate L 50 in a population of the heptapterid Rhamdioglanis transfasciatus from Atlantic Forest streams. Fish were sampled monthly during a year by using electrofishing. We measured the length (cm), mass (g), and gonad mass (g) of each specimen, then classified their maturity status macroscopically and microscopically. Alternative approaches were strongly discordant from traditional ones. Logistic curves considering mature individuals as those displaying at least 1% of the maximum I g in the sample greatly underestimated L 50 for females and overestimated L 50 for males. The stanza changing point derived from the polyphasic growth model underestimated L 50 in both cases. Despite the increasing development of less onerous approaches, it seems that they are not suitable for all fish populations and the requirements to use such approaches demand further investigation.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Air Pollution and Adverse Pregnancy and Birth Outcomes: Mediation Analysis Using Metabolomic Profiles - Kosuke Inoue; Qi Yan; Onyebuchi A. Arah; Kimberly Paul; Douglas I. Walker; Dean P. Jones; Beate Ritz (Current Environmental Health Reports, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Response of Wild Spotted Wing Drosophila (Drosophila suzukii) to Microbial Volatiles - Eduardo Bueno; Kyle R. Martin; Robert A. Raguso; John G. Mcmullen; Stephen P. Hesler; Greg M. Loeb; Angela E. Douglas (Journal of Chemical Ecology, 2020)

Understanding Skin Screening Practices Among Children at Elevated Risk for Melanoma to Inform Interventions for Melanoma Prevention and Control - Bridget G. Parsons; Jennifer L. Hay; Lisa G. Aspinwall; Kelsey Zaugg; Angela Zhu; Ryan H. Mooney; Stephanie Z. Klein; Douglas Grossman; Sancy A. Leachman; Yelena P. Wu (Journal of Cancer Education, 2020)

Nanoscale imaging using differential expansion microscopy - Sebastian P. Pernal; Asiri Liyanaarachchi; Domenico L. Gatti; Brent Formosa; Rishika Pulvender; Eric R. Kuhn; Rafael Ramos; Akshata R. Naik; Kathleen George; Suzan Arslanturk; Douglas J. Taatjes; Bhanu P. Jena (Histochemistry and Cell Biology, 2020)

The effects of lutein and zeaxanthin on resting state functional connectivity in older Caucasian adults: a randomized controlled trial - Cutter A. Lindbergh; Jinglei Lv; Yu Zhao; Catherine M. Mewborn; Antonio N. Puente; Douglas P. Terry; Lisa M. Renzi-Hammond; Billy R. Hammond; Tianming Liu; L. Stephen Miller (Brain Imaging and Behavior, 2020)

Another chemolithotrophic metabolism missing in nature: sulfur comproportionation - Jan P. Amend; Heidi S. Aronson; Jennifer Macalady; Douglas E. LaRowe (Environmental Microbiology, 2020)
Summary Chemotrophic microorganisms gain energy for cellular functions by catalyzing oxidation–reduction (redox) reactions that are out of equilibrium. Calculations of the Gibbs energy ( ΔG r ) can identify whether a reaction is thermodynamically favourable and quantify the accompanying energy yield at the temperature, pressure and chemical composition in the system of interest. Based on carefully calculated values of ΔG r , we predict a novel microbial metabolism – sulfur comproportionation (3H 2 S + + 2H + ⇌ 4S 0 + 4H 2 O). We show that at elevated concentrations of sulfide and sulfate in acidic environments over a broad temperature range, this putative metabolism can be exergonic ( ΔG r −1 . We suggest that this may be sufficient energy to support a chemolithotrophic metabolism currently missing from the literature. Other versions of this metabolism, comproportionation to thiosulfate (H 2 S + ⇌ + H 2 O) and to sulfite (H 2 S + 3 ⇌ 4 + 2H + ), are only moderately exergonic or endergonic even at ideal geochemical conditions. Natural and impacted environments, including sulfidic karst systems, shallow‐sea hydrothermal vents, sites of acid mine drainage, and acid–sulfate crater lakes, may be ideal hunting grounds for finding microbial sulfur comproportionators.

Identification of genes from the general phenylpropanoid and monolignol-specific metabolism in two sugarcane lignin-contrasting genotypes - Douglas Jardim-Messeder; Tatiane da Franca Silva; Jose Pedro Fonseca; José Nicomedes Junior; Lucia Barzilai; Thais Felix-Cordeiro; Joyce Carvalho Pereira; Clara Rodrigues-Ferreira; Isabela Bastos; Tereza Cristina da Silva; Vinicius de Abreu Waldow; Daniela Cassol; et al. (Molecular Genetics and Genomics, 2020)

Terrestrial water storage and Pacific SST affect the monthly water balance of Itacaiúnas River Basin (Eastern Amazonia) - Rosane B. L. Cavalcante; Paulo R. M. Pontes; Renata G. Tedeschi; Cláudia P. W. Costa; Douglas B. S. Ferreira; Pedro W. M. Souza‐Filho; Everaldo B. de Souza (International Journal of Climatology, 2020)
At subannual timescales, terrestrial water storage (TWS) plays a critical role in the partitioning of precipitation into runoff and evapotranspiration, and Amazonia stands out due to the great amplitude of the annual cycles. In this study, we analyse the monthly variation of the water balance and extreme hydrological events using GRACE data for a watershed situated in the “arc‐of‐deforestation” in the Eastern Brazilian Legal Amazon. The existence of a correlation and lag time response between the monthly sea surface temperatures in the Pacific and North Atlantic and the variables of the water balance were also investigated. The results showed a weak seasonal cycle of evapotranspiration, with higher water intercepted by the vegetation canopy in the rainy season and higher potential evapotranspiration supplied by TWS in the dry season. The lowest value of water storage was reached in December 2015 during the strongest El Niño event observed in the analysed period (2002–2016). This value impacted the streamflow for at least the entire rainy season. The correlation analysis showed that positive anomalies of the Niño 3.4 index from October to March caused a significant decrease in precipitation in the following March to May and in November, a significant increase in the reference evapotranspiration in April and May, and longer lasting effects on the streamflow and TWS. Although the underlying mechanisms contributing to the time delays remain incompletely understood, the results indicate that consideration of the ENSO influence on the water balance and of the TWS influence on streamflow would improve flood and drought forecasts with benefits for water management.

Restore or Redefine: Future Trajectories for Restoration - Melinda Ann Coleman; Georgina Wood; Karen Filbee-Dexter; Antoine J. P. Minne; Hugh Douglas Goold; Adriana Vergés; Ezequiel Miguel Marzinelli; Peter David Steinberg; Thomas Wernberg (Frontiers in Marine Science, 2020)

Short-term time-restricted feeding is safe and feasible in non-obese healthy midlife and older adults - Christopher R. Martens; Matthew J. Rossman; Melissa R. Mazzo; Lindsey R. Jankowski; Erzsebet E. Nagy; Blair A. Denman; James J. Richey; Sarah A. Johnson; Brian P. Ziemba; Yang Wang; Courtney M. Peterson; Michel Chonchol; et al. (GeroScience, 2020)

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Extracellular vesicles from mesenchymal stem cells reduce microglial-mediated neuroinflammation after cortical injury in aged Rhesus monkeys - Veronica Go; Bethany G. E. Bowley; Monica A. Pessina; Zheng Gang Zhang; Michael Chopp; Seth P. Finklestein; Douglas L. Rosene; Maria Medalla; Benjamin Buller; Tara L. Moore (GeroScience, 2020)

Understanding racial disparities in renal cell carcinoma incidence: estimates of population attributable risk in two US populations - Catherine L. Callahan; Kendra Schwartz; Douglas A. Corley; Julie J. Ruterbusch; Wei K. Zhao; Brian Shuch; Barry I. Graubard; Nathaniel Rothman; Wong-Ho Chow; Debra T. Silverman; Mark P. Purdue; Jonathan N. Hofmann (Cancer Causes & Control, 2020)

How do Allenby’s gerbils titrate risk and reward in response to different predators? - Douglas F. Makin; Burt P. Kotler (Behavioral Ecology and Sociobiology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

Comparative diversity of anemone-associated fishes and decapod crustaceans in a Belizean coral reef and seagrass system - Rohan M. Brooker; William E. Feeney; Tiffany L. Sih; Maud. C. O. Ferrari; Douglas P. Chivers (Marine Biodiversity, 2019)

Sustainable Sugarcane Straw Special Issue: Considerations for Brazilian Bioenergy Production - João Luís Nunes Carvalho; Carlos Eduardo P. Cerri; Douglas L. Karlen (BioEnergy Research, 2019)

Whole‐genome sequencing reveals Listeria monocytogenes diversity and allows identification of long‐term persistent strains in Brazil - Anderson C. Camargo; Alexandra Moura; Johannetsy Avillan; Nicole Herman; Adelle P. McFarland; Srinand Sreevatsan; Douglas R. Call; Joshua J. Woodward; Marc Lecuit; Luís A. Nero (Environmental Microbiology, 2019)
Summary Advances in whole‐genome sequencing (WGS) technologies have documented genetic diversity and epidemiology of the major foodborne pathogen Listeria monocytogenes ( Lm ) in Europe and North America, but data concerning South America are scarce. Here, we examined the population structure and genetic diversity of this major foodborne pathogen collected in Brazil. Based on core genome multilocus sequence typing (cgMLST), isolates from lineages I ( n = 22; 63%) and II ( n = 13; 37%) were distributed into 10 different sublineages (SLs) and represented 31 new cgMLST types (CTs). The most prevalent SLs were SL9 ( n = 9; 26%), SL3 ( n = 6; 17%) and SL2 and SL218 ( n = 5; 14%). Isolates belonging to CTs L2‐SL9‐ST9‐CT4420 and L1‐SL315‐ST520‐CT4429 were collected 3 and 9 years apart, respectively, revealing long‐term persistence of Lm in Brazil. Genetic elements associated with stress survival were present in 60% of isolates (57% SSI‐1 and 3% SSI‐2). Pathogenic islands were present in 100% (LIPI‐1), 43% (LIPI‐3) and 6% (LIPI‐4) of the isolates. Mutations leading to premature stop codons were detected in the prfA and inlA virulence genes. This study is an important contribution to understanding the genomic diversity and epidemiology of Lm in South America. In addition, the results highlight the importance of using WGS to reveal Lm long‐term persistence.

Differences in reported sun protection practices, skin cancer knowledge, and perceived risk for skin cancer between rural and urban high school students - Elizabeth S. Nagelhout; Bridget G. Parsons; Benjamin Haaland; Kenneth P. Tercyak; Kelsey Zaugg; Angela Zhu; Garrett Harding; Jeffrey Yancey; Jakob D. Jensen; Douglas Grossman; David W. Wetter; Yelena P. Wu (Cancer Causes & Control, 2019)

Application of Stable Carbon Isotopes in a Subtropical North Atlantic MesocosmStudy: A New Approach to Assess CO2 Effects on the Marine Carbon Cycle - Mario Esposito; Eric P. Achterberg; Lennart T. Bach; Douglas P. Connelly; Ulf Riebesell; Jan Taucher (Frontiers in Marine Science, 2019)

Selective Sensory Axon Reinnervation and TRPV1 Activation - T. Poitras; A. Chandrasekhar; L. McCoy; P. Komirishetty; A. Areti; C. A. Webber; Douglas W. Zochodne (Molecular Neurobiology, 2019)

Correction to: Clinicians’ use of breast cancer risk assessment tools according to their perceived importance of breast cancer risk factors: an international survey - Anne Brédart; Jean-Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Marjanka K. Schmidt; Sylvie Dolbeault; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Journal of Community Genetics, 2019)

Systematic relationships of sympatric pipefishes ( Syngnathus spp.): A mismatch between morphological and molecular variation - Eric Garcia; Cristy A. Rice; Douglas J. Eernisse; Kristy L. Forsgren; Juan P. Quimbayo; Greg W. Rouse (Journal of Fish Biology, 2019)
Analyses of mitochondrial DNA and morphological variation were performed on specimens of all five currently recognised Syngnathus pipefish species from the eastern Pacific Ocean with type localities currently considered to lie within the Californian marine biogeographic province: kelp pipefish Syngnathus californiensis , bay pipefish S. leptorhynchus , barred pipefish S. auliscus , barcheek pipefish S. exilis and chocolate pipefish S. euchrous . Results consistently differentiate S. auliscus from the other species and fail to distinguish all other specimens as distinct species, as indicated by extensive morphological overlap as well as incomplete lineage sorting and considerably low genetic divergence for 16s and coI genes( Syngnathus spp. and proposes the synonymy of S. leptorhynchus , S. euchrous and S. exilis , under the senior synonym, S. californiensis . There is still a need to study populations of Syngnathus spp. from north and south of the Californian province to assess whether these too are synonyms of the two‐species recognised here.

Minireview: demystifying microbial reaction energetics - Jan P. Amend; Douglas E. LaRowe (Environmental Microbiology, 2019)
Summary The biology literature is rife with misleading information on how to quantify catabolic reaction energetics. The principal misconception is that the sign and value of the standard Gibbs energy ( ) define the direction and energy yield of a reaction; they do not. is one part of the actual Gibbs energy of a reaction ( ΔG r ), with a second part accounting for deviations from the standard composition. It is also frequently assumed that applies only to 25 °C and 1 bar; it does not. is a function of temperature and pressure. Here, we review how to determine ΔG r as a function of temperature, pressure and chemical composition for microbial catabolic reactions, including a discussion of the effects of ionic strength on ΔG r and highlighting the large effects when multi‐valent ions are part of the reaction. We also calculate ΔG r for five example catabolisms at specific environmental conditions: aerobic respiration of glucose in freshwater, anaerobic respiration of acetate in marine sediment, hydrogenotrophic methanogenesis in a laboratory batch reactor, anaerobic ammonia oxidation in a wastewater reactor and aerobic pyrite oxidation in acid mine drainage. These examples serve as templates to determine the energy yields of other catabolic reactions at environmentally relevant conditions.

Future Ocean Observations to Connect Climate, Fisheries and Marine Ecosystems - Jörn O. Schmidt; Steven J. Bograd; Haritz Arrizabalaga; José L. Azevedo; Steven J. Barbeaux; John A. Barth; Tim Boyer; Stephanie Brodie; Juan José Cárdenas; Scott Cross; Jean-Noël Druon; Agneta Fransson; et al. (Frontiers in Marine Science, 2019)

Survival, behaviour, and morphology of larval wood frogs, Lithobates sylvaticus, under threat from an exotic crayfish predator, Orconectes virilis - Adam L. Crane; Kevin R. Bairos-Novak; Dale M. Jefferson; Douglas P. Chivers; Maud C. O. Ferrari (Aquatic Ecology, 2019)

Wetland methane emissions dominated by plant‐mediated fluxes: Contrasting emissions pathways and seasons within a shallow freshwater subtropical wetland - Luke C. Jeffrey; Damien T. Maher; Scott G. Johnston; Brendan P. Kelaher; Andy Steven; Douglas R. Tait (Limnology and Oceanography, 2019)
Wetlands represent the largest natural source of methane; however, very few studies have simultaneously quantified the three main atmospheric flux pathways (i.e., diffusive, ebullition, and plant‐mediated). Unlike better‐studied northern hemisphere systems, many Australian subtropical wetlands undergo extreme wet/dry oscillations, which may strongly impact methane dynamics. We assessed diurnal methane emissions of multiple pathways during three distinct seasonal events within an Australian freshwater wetland. Six‐fold higher methane emissions occurred during summer compared to autumn floods (which followed an extensive dry‐period) and winter/cool conditions. Over three seasons, diffusion represented the highest average areal fluxes (25.9 ± 73.2 mmol m −2 d −1 ) but were within range of fluxes through water lily aerenchyma (20.8 ± 41.5 mmol m −2 d −1 ). Average ebullition rates were 5.5 ± 9.7 mmol m −2 d −1 . Water column CH 4 displayed high spatiotemporal variability, ranging from 55.0 to 253.5 μ mol L −1 . Time series δ 13 C–CH 4 isotope measurements revealed an oxidation fraction of ~ 15% at night‐time and ~ 36% during day‐time, and night‐time diffusive fluxes were consistently ~ three‐fold higher than day‐time fluxes. By aggregating seasons and weighting for changes in lily coverage, plant‐mediated fluxes accounted for ~ 59% of the annual methane emissions, whereas ebullition and diffusion each accounted for ~ 20%. The up‐scaled annual area‐weighted wetland methane flux (combined pathways) was 27.3 ± 36.7 mmol m −2 d −1 . We contend that water lilies ( Nymphaea sp.) are the significant carbon source, mediator, and conduit for methane fluxes in this system, and the extremely large seasonal variability of methane emissions reflect dynamic redox oscillations driven by oscillating wet and dry conditions.

For common community phylogenetic analyses, go ahead and use synthesis phylogenies - Daijiang Li; Lauren Trotta; Hannah E. Marx; Julie M. Allen; Miao Sun; Douglas E. Soltis; Pamela S. Soltis; Robert P. Guralnick; Benjamin Baiser (Ecology, 2019)
Should we build our own phylogenetic trees based on gene sequence data, or can we simply use available synthesis phylogenies? This is a fundamental question that any study involving a phylogenetic framework must face at the beginning of the project. Building a phylogeny from gene sequence data (purpose‐built phylogeny) requires more effort, expertise, and cost than subsetting an already available phylogeny (synthesis‐based phylogeny). However, we still lack a comparison of how these two approaches to building phylogenetic trees influence common community phylogenetic analyses such as comparing community phylogenetic diversity and estimating trait phylogenetic signal. Here, we generated three purpose‐built phylogenies and their corresponding synthesis‐based trees (two from Phylomatic and one from the Open Tree of Life, OTL ). We simulated 1,000 communities and 12,000 continuous traits along each purpose‐built phylogeny. We then compared the effects of different trees on estimates of phylogenetic diversity (alpha and beta) and phylogenetic signal (Pagel's λ and Blomberg's K). Synthesis‐based phylogenies generally yielded higher estimates of phylogenetic diversity when compared to purpose‐built phylogenies. However, resulting measures of phylogenetic diversity from both types of phylogenies were highly correlated (Spearman's > 0.8 in most cases). Mean pairwise distance (both alpha and beta) is the index that is most robust to the differences in tree construction that we tested. Measures of phylogenetic diversity based on the OTL showed the highest correlation with measures based on the purpose‐built phylogenies. Trait phylogenetic signal estimated with synthesis‐based phylogenies, especially from the OTL , was also highly correlated with estimates of Blomberg's K or close to Pagel's λ from purpose‐built phylogenies when traits were simulated under Brownian motion. For commonly employed community phylogenetic analyses, our results justify taking advantage of recently developed and continuously improving synthesis trees, especially the Open Tree of Life.

In situ Autonomous Acquisition and Preservation of Marine Environmental DNA Using an Autonomous Underwater Vehicle - Kevan M. Yamahara; Christina M. Preston; James Birch; Kristine Walz; Roman Marin; Scott Jensen; Douglas Pargett; Brent Roman; William Ussler; Yanwu Zhang; John Ryan; Brett Hobson; et al. (Frontiers in Marine Science, 2019)

Diffuse Hydrothermal Venting: A Hidden Source of Iron to the Oceans - Alastair J. M. Lough; Douglas P. Connelly; William B. Homoky; Jeffrey A. Hawkes; Valerie Chavagnac; Alain Castillo; Majid Kazemian; Ko-ichi Nakamura; Tohru Araki; Burkhard Kaulich; Rachel A. Mills (Frontiers in Marine Science, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Correction to: Mercury accumulation, speciation, and temporal trends in Atlantic Stingrays (Hypanus sabinus) - Brianne K. Soulen; Douglas H. Adams; Aaron P. Roberts (Ecotoxicology, 2019)

The Effects of Selenomethionine on the Escape Behaviours of Fathead Minnows - Philip J. Anderson; Matthew D. Mitchell; Katherine J. Fedoroff; Douglas P. Chivers; Maud C. O. Ferrari (Archives of Environmental Contamination and Toxicology, 2019)

Simulation of the entanglement of a North Atlantic right whale ( Eubalaena glacialis ) with fixed fishing gear - Laurens E. Howle; Scott D. Kraus; Timothy B. Werner; Douglas P. Nowacek (Marine Mammal Science, 2019)
Population estimates of the critically endangered North Atlantic right whale ( Eubalaena glacialis ) put the number of individuals at 458 with the actual number likely being lower due to a recent unusual mortality event. Entanglement with fixed fishing gear is the most significant cause of mortality of North Atlantic right whales. There remains little documentation of how North Atlantic right whales become enwrapped during an encounter with fixed fishing gear. In order to gain a better understanding of how entanglements might occur, an interactive simulator was developed that allows the user to swim a virtual whale model using a standard game controller through a gear field in an attempt to re‐create an entanglement. The morphologically accurate right whale model produces realistic swimming motions and is capable of pectoral fin motions in response to user input. Using the simulator, gear entanglements involving the pectoral flippers including ropes wrapping around the body and entanglements involving the tailstock were re‐created. Entanglements involving the pectoral flippers with body wraps were more easily generated than entanglements involving the tailstock only. The simulator should aid scientists, fisheries experts, fishing gear designers, and bycatch reduction scientists in understanding entanglement dynamics and testing potential new gear configurations.

Plasticity in elk migration timing is a response to changing environmental conditions - Gregory J. M. Rickbeil; Jerod A. Merkle; Greg Anderson; M. Paul Atwood; Jon P. Beckmann; Eric K. Cole; Alyson B. Courtemanch; Sarah Dewey; David D. Gustine; Matthew J. Kauffman; Douglas E. McWhirter; Tony Mong; et al. (Global Change Biology, 2019)
Migration is an effective behavioral strategy for prolonging access to seasonal resources and may be a resilient strategy for ungulates experiencing changing climatic conditions. In the Greater Yellowstone Ecosystem ( GYE ), elk are the primary ungulate, with approximately 20,000 individuals migrating to exploit seasonal gradients in forage while also avoiding energetically costly snow conditions. How climate‐induced changes in plant phenology and snow accumulation are influencing elk migration timing is unknown. We present the most complete record of elk migration across the GYE , spanning 9 herds and 414 individuals from 2001 to 2017, to evaluate the drivers of migration timing and test for temporal shifts. The timing of elk departure from winter range involved a trade‐off between current and anticipated forage conditions, while snow melt governed summer range arrival date. Timing of elk departure from summer range and arrival on winter range were both influenced by snow accumulation and exposure to hunting. At the GYE scale, spring and fall migration timing changed through time, most notably with winter range arrival dates becoming almost 50 days later since 2001. Predicted herd‐level changes in migration timing largely agreed with observed GYE ‐wide changes—except for predicted winter range arrival dates which did not reflect the magnitude of change detected in the elk telemetry data. Snow melt, snow accumulation, and spring green‐up dates all changed through time, with different herds experiencing different rates and directions of change. We conclude that elk migration is plastic, is a direct response to environmental cues, and that these environmental cues are not changing in a consistent manner across the GYE . The impacts of changing elk migration timing on predator–prey dynamics, carnivore–livestock conflict, disease ecology, and harvest management across the GYE are likely to be significant and complex.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Patterns in island endemic forest-dependent bird research: the Caribbean as a case-study - Eleanor S. Devenish-Nelson; Douglas Weidemann; Jason Townsend; Howard P. Nelson (Biodiversity and Conservation, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Liver and muscle glycogen oxidation and performance with dose variation of glucose–fructose ingestion during prolonged (3 h) exercise - Andy J. King; John P. O’Hara; Nicola C. Arjomandkhah; Josh Rowe; Douglas J. Morrison; Thomas Preston; Roderick F. G. J. King (European Journal of Applied Physiology, 2019)

Who’s where? Ecological uncertainty shapes neophobic predator avoidance in Trinidadian guppies - Laurence E. A. Feyten; Ebony E. E. M. Demers; Indar W. Ramnarine; Douglas P. Chivers; Maud C. O. Ferrari; Grant E. Brown (Behavioral Ecology and Sociobiology, 2019)

Trends in Sandeel Growth and Abundance off the East Coast of Scotland - Alan MacDonald; Douglas C. Speirs; Simon P. R. Greenstreet; Philip Boulcott; Michael R. Heath (Frontiers in Marine Science, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Mercury accumulation, speciation, and temporal trends in Atlantic Stingrays (Hypanus sabinus) - Brianne K. Soulen; Douglas H. Adams; Aaron P. Roberts (Ecotoxicology, 2019)

MEMORIES - Frances M. D. Gulland; Peter O. Thomas; Ian Stirling; Douglas P. DeMaster; Randall R. Reeves; Kathy Frost (Marine Mammal Science, 2019)

Timing of Sandeel Spawning and Hatching Off the East Coast of Scotland - Alan MacDonald; Michael R. Heath; Simon P. R. Greenstreet; Douglas C. Speirs (Frontiers in Marine Science, 2019)

Rising Sea Levels: Helping Decision-Makers Confront the Inevitable - John A. Hall; Christopher P. Weaver; Jayantha Obeysekera; Mark Crowell; Radley M. Horton; Robert E. Kopp; John Marburger; Douglas C. Marcy; Adam Parris; William V. Sweet; William C. Veatch; Kathleen D. White (Coastal Management, 2019)

Better estimates of soil carbon from geographical data: a revised global approach - Sandra Duarte-Guardia; Pablo L. Peri; Wulf Amelung; Douglas Sheil; Shawn W. Laffan; Nils Borchard; Michael I. Bird; Wouter Dieleman; David A. Pepper; Brian Zutta; Esteban Jobbagy; Lucas C. R. Silva; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Effects of Liming and Urochloa brizantha Management on Leaching Potential of Picloram - Ana Beatriz R. J. Passos; Matheus F. Souza; Douglas T. Saraiva; Antônio Alberto da Silva; Maria Eliana L. R. Queiroz; Felipe P. Carvalho; Daniel Valadão Silva (Water, Air, & Soil Pollution, 2019)

Clinicians’ use of breast cancer risk assessment tools according to their perceived importance of breast cancer risk factors: an international survey - Anne Brédart; Jean-Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Marjanka K. Schmidt; Sylvie Dolbeault; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Journal of Community Genetics, 2019)

An integrated analysis of mRNA and sRNA transcriptional profiles in Coffea arabica L. roots: insights on nitrogen starvation responses - Tiago Benedito dos Santos; João D. M. Soares; Joni E. Lima; Juliana C. Silva; Suzana T. Ivamoto; Viviane Y. Baba; Silvia G. H. Souza; Alan P. R. Lorenzetti; Alexandre R. Paschoal; Anderson R. Meda; Milton Y. Nishiyama Júnior; Úrsula C. de Oliveira; et al. (Functional & Integrative Genomics, 2019)

Intertidal clams exhibit population synchrony across spatial and temporal scales - Julie S. Barber; Casey P. Ruff; James T. McArdle; Lindy L. Hunter; Camille A. Speck; Douglas W. Rogers; Courtney M. Greiner (Limnology and Oceanography, 2019)
Long‐term datasets can be particularly useful for parsing out factors influencing populations, yet few studies have utilized continuous datasets to quantify population dynamics in bivalve molluscs. We used dynamic factor analysis on a clam biomass dataset spanning 28 yr and five distinct regions in the southern Salish Sea to determine (1) if native intertidal clam populations exhibit synchrony and (2) what environmental covariates may be correlated with these population trends. Once covariates were accounted for, the model with the most data support included three predominant trends to describe multidecadal change in clam biomass. Intraspecific synchrony was highest among Saxidomus gigantea and Leukoma staminea populations, with no clear evidence of covariance in Clinocardium nuttallii . Specifically, we quantified a pronounced decadal decline in L. staminea and an increase in S. gigantea biomass on most beaches. No beaches showed synchrony in trends across all three species, indicating that species‐specific trends (regardless of location) were more common than beach‐specific trends (regardless of species). Seven environmental covariates were evaluated in their capacity to explain variability in annual mean biomass. Of these, the North Pacific Gyre Oscillation lagged 4 yr prior to the observation year was most supported by the data in the best fitting model, implying that 4 yr old clam biomass is partially determined by oceanographic processes affecting larval clams. Although results suggest large‐scale density‐independent factors play a role in venerid clam population dynamics, it is also likely local factors account for variability not explained by our model.

Environmental variability controls recruitment but with different drivers among spawning components in Gulf of St. Lawrence herring stocks - Pablo Brosset; Thomas Doniol‐Valcroze; Douglas P. Swain; Caroline Lehoux; Elisabeth Van Beveren; Baye C. Mbaye; Kim Emond; Stéphane Plourde (Fisheries Oceanography, 2019)
The factors affecting herring recruitment are still poorly understood, complicating the prediction of stock dynamics and the choice of operational management strategies. We investigated effects of intrinsic ( SSB ) and extrinsic factors (physical and biological environments, including competition and predation) on recruitment of the spring and fall spawning components of each of the two herring stocks occurring in the Gulf of the St. Lawrence between 1971 and 2014. Effects of potential explanatory factors on recruit (age 2) abundance were tested using Generalized Additive Models. Model fit was significantly improved by incorporating both physical and biological environmental variability, but effects of herring SSB and predation were not significant. Indices of zooplankton abundance and phenology explained more variance in recruitment than physical indices. Our results emphasize the dominance of bottom‐up processes over SSB in the regulation of herring recruitment. Environmental variability did not seem to act uniformly on the recruitment of either stock or their respective spawning components. A long‐term trend of decreasing recruitment in spring spawners was associated with a long‐term decline in abundance of cold water copepods. In fall spawners, optimal recruitment was dependent on warmer environmental conditions combined with an adequate supply (species composition and phenology) of zooplankton. These results provide the first empirical evidence that spring and fall spawning herring are adapted to contrasting environmental conditions and shed light on the potential mechanisms linking herring recruitment to key zooplankton community characteristics and phenology. Management strategies can be improved by incorporating this new knowledge on environmental drivers of herring recruitment.

Microbial Communities of the Gut and Nest of the Humus- and Litter-Feeding Termite Procornitermes araujoi (Syntermitinae) - Edimar A. Moreira; Thabata M. Alvarez; Gabriela F. Persinoti; Douglas Antonio Alvaredo Paixão; Letícia R. Menezes; João P. Franco Cairo; Fabio Marcio Squina; Ana M. Costa-Leonardo; Tiago Carrijo; Alberto Arab (Current Microbiology, 2018)

Brachyuran crab (Crustacea, Decapoda) assemblage associated with Sargassum cymosum in southeastern Brazil - Samara de P. Barros-Alves; Douglas Fernandes Rodrigues Alves; Valter José Cobo (Marine Biodiversity, 2018)

Biomimetic Placenta-Fetus Model Demonstrating Maternal–Fetal Transmission and Fetal Neural Toxicity of Zika Virus - Navein Arumugasaamy; Leila E. Ettehadieh; Che-Ying Kuo; Dominic Paquin-Proulx; Shannon M. Kitchen; Marco Santoro; Jesse K. Placone; Paola P. Silveira; Renato S. Aguiar; Douglas F. Nixon; John P. Fisher; Peter C. W. Kim (Annals of Biomedical Engineering, 2018)

Morphometric differences between two exotic invasive freshwater caridean species (genus Macrobrachium ) - Thiago Elias da Silva; Douglas Fernandes Rodrigues Alves; Samara de P. Barros-Alves; Ariádine Cristine Almeida; Fabiano Gazzi Taddei; Adilson Fransozo (Invertebrate Reproduction & Development, 2018)

Correction to: Cerebellar Modules and Their Role as Operational Cerebellar Processing Units: A Consensus paper - Richard Apps; Richard Hawkes; Sho Aoki; Fredrik Bengtsson; Amanda M. Brown; Gang Chen; Timothy J. Ebner; Philippe Isope; Henrik Jörntell; Elizabeth P. Lackey; Charlotte Lawrenson; Bridget Lumb; et al. (The Cerebellum, 2018)

Cerebellar Modules and Their Role as Operational Cerebellar Processing Units - Richard Apps; Richard Hawkes; Sho Aoki; Fredrik Bengtsson; Amanda M. Brown; Gang Chen; Timothy J. Ebner; Philippe Isope; Henrik Jörntell; Elizabeth P. Lackey; Charlotte Lawrenson; Bridget Lumb; et al. (The Cerebellum, 2018)

An expanded fish-based index of biotic integrity for Great Lakes coastal wetlands - Matthew J. Cooper; Gary A. Lamberti; Ashley H. Moerke; Carl R. Ruetz; Douglas A. Wilcox; Valerie J. Brady; Terry N. Brown; Jan J. H. Ciborowski; Joseph P. Gathman; Greg P. Grabas; Lucinda B. Johnson; Donald G. Uzarski (Environmental Monitoring and Assessment, 2018)

Microbially-enriched poultry litter-derived biochar for the treatment of acid mine drainage - Admir J. Giachini; Thays S. Sulzbach; Antônio L. Pinto; Rafael D. Armas; Douglas H. Cortez; Emanuela P. Silva; Elizandra B. Buzanello; Álvaro G. Soares; Cláudio R. F. S. Soares; Márcio J. Rossi (Archives of Microbiology, 2018)

A review of regulations and guidelines related to winter manure application - Jian Liu; Peter J. A. Kleinman; Helena Aronsson; Don Flaten; Richard W. McDowell; Marianne Bechmann; Douglas B. Beegle; Timothy P. Robinson; Ray B. Bryant; Hongbin Liu; Andrew N. Sharpley; Tamie L. Veith (Ambio, 2018)

Why the COI barcode should be the community DNA metabarcode for the metazoa - Carmelo Andújar; Paula Arribas; Douglas W. Yu; Alfried P. Vogler; Brent C. Emerson (Molecular Ecology, 2018)
Metabarcoding of complex metazoan communities is increasingly being used to measure biodiversity in terrestrial, freshwater and marine ecosystems, revolutionizing our ability to observe patterns and infer processes regarding the origin and conservation of biodiversity. A fundamentally important question is which genetic marker to amplify, and although the mitochondrial cytochrome oxidase subunit I ( COI ) gene is one of the more widely used markers in metabarcoding for the Metazoa, doubts have recently been raised about its suitability. We argue that (a) the extensive coverage of reference sequence databases for COI ; (b) the variation it presents; (c) the comparative advantages for denoising protein‐coding genes; and (d) recent advances in DNA sequencing protocols argue in favour of standardizing for the use of COI for metazoan community samples. We also highlight where research efforts should focus to maximize the utility of metabarcoding.

Manatee behavioral response to boats - Athena M. Rycyk; Charles J. Deutsch; Margaret E. Barlas; Stacie K. Hardy; Katherine Frisch; Erin H. Leone; Douglas P. Nowacek (Marine Mammal Science, 2018)
The long‐term viability of the Florida manatee is threatened in part by mortality from boat collisions. This study investigated manatee behavior during boat approaches to better understand factors that lead to manatee–boat collisions. Digital acoustic recording tags (DTAGs) and Argos‐linked GPS tags were deployed on 18 manatees in southwest Florida, and boat traffic around them was mapped. Suites of manatee behavioral, environmental, and boat‐related factors were recorded during opportunistic boat passes. We built generalized linear mixed models to determine which factors accounted for variation in occurrence, number, and timing of manatee behavioral changes during boat passes. Manatees responded to boats, changing their orientation, depth, and fluking behavior most often when a boat approached closely (

Morphological and phylogenetic characterization of a novel Unicauda species, infecting the kidney of Astyanax altiparanae (Teleostei: Characidae) in Brazil - Letícia P. Vidal; Douglas McIntosh; José L. Luque (Acta Parasitologica, 2018)
During a parasitological survey of Astyanax altiparanae captured in the Mogi Guaçú river, Pirassununga, state of São Paulo, Brazil, a new species of myxozoa was observed infecting the kidney of 30 of 42 specimens. Plasmodia of the new myxozoa, referred to herein as Unicauda whippsi n. sp. were spherical and varied from 450 to 1000 μm in length. The mature spore was elongated and measured 11 ± 1.2 (10–12) μm long by 5.4 ± 0.6 (4.7–7.2) μm wide. Polar capsules of unequal length with the filament coiled 7–9 times and a unique caudal process characteristic of the genus Unicauda , were recorded. Phylogenetic analysis demonstrated that U. whippsi n. sp. clustered with members of the genus Unicauda and Myxobolus , confirming it’s placement within the family Myxobolidae. This is the first record of a species of Unicauda infecting characiform fish, as well as the first registered occurrence of species of this genus in South America.

Exploring the Influence of Food and Temperature on North Sea Sandeels Using a New Dynamic Energy Budget Model - Alan MacDonald; Douglas C. Speirs; Simon P. R. Greenstreet; Michael R. Heath (Frontiers in Marine Science, 2018)

Correction to: Harden up: metal acquisition in the weaponized ovipositors of aculeate hymenoptera - Kate Baumann; Edward P. Vicenzi; Thomas Lam; Janet Douglas; Kevin Arbuckle; Bronwen Cribb; Seán G. Brady; Bryan G. Fry (Zoomorphology, 2018)

Harden up: metal acquisition in the weaponized ovipositors of aculeate hymenoptera - Kate Baumann; Edward P. Vicenzi; Thomas Lam; Janet Douglas; Kevin Arbuckle; Bronwen Cribb; Seán G. Brady; Bryan G. Fry (Zoomorphology, 2018)

Development of an Educational Program Integrating Concepts of Genetic Risk and Preventive Strategies for Children with a Family History of Melanoma - Yelena P. Wu; Lisa G. Aspinwall; Elizabeth Nagelhout; Wendy Kohlmann; Kimberly A. Kaphingst; Sheila Homburger; Ryan D. Perkins; Douglas Grossman; Garrett Harding; Pamela Cassidy; Sancy A. Leachman (Journal of Cancer Education, 2018)

Bloodlines: mammals, leeches, and conservation in southern Asia - Michael Tessler; Sarah R. Weiskopf; Lily Berniker; Rebecca Hersch; Kyle P. Mccarthy; Douglas W. Yu; Mark E. Siddall (Systematics and Biodiversity, 2018)

Corrections to: Use of the BOADICEA Web Application in clinical practice: appraisals by clinicians from various countries - Anne Brédart; Jean‑Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Sylvie Dolbeault; Léonore Robieux; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Familial Cancer, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Refining Protein Penetration into the Lipid Bilayer Using Fluorescence Quenching and Molecular Dynamics Simulations: The Case of Diphtheria Toxin Translocation Domain - Alexander Kyrychenko; Nathan M. Lim; Victor Vasquez-Montes; Mykola V. Rodnin; J. Alfredo Freites; Linh P. Nguyen; Douglas J. Tobias; David L. Mobley; Alexey S. Ladokhin (The Journal of Membrane Biology, 2018)

Impairment of exercise performance following cold water immersion is not attenuated after 7 days of cold acclimation - Douglas M. Jones; Bart Roelands; Stephen P. Bailey; Michael J. Buono; Romain Meeusen (European Journal of Applied Physiology, 2018)

Repeated mild traumatic brain injuries is not associated with volumetric differences in former high school football players - Douglas P. Terry; L. Stephen Miller (Brain Imaging and Behavior, 2018)

Volatile and Contact Chemical Cues Associated with Host and Mate Recognition Behavior of Sphenophorus venatus and Sphenophorus parvulus (Coleoptera: Dryophthoridae) - Alexandra G. Duffy; Gabriel P. Hughes; Matthew D. Ginzel; Douglas S. Richmond (Journal of Chemical Ecology, 2018)

Multiple shifts to open habitats in Melastomateae (Melastomataceae) congruent with the increase of African Neogene climatic aridity - Marie Claire Veranso‐Libalah; Gudrun Kadereit; Robert Douglas Stone; Thomas L. P. Couvreur (Journal of Biogeography, 2018)
Aim African Melastomateae (Melastomataceae) comprise c . 185 species occurring in closed or open habitats throughout sub‐Saharan Africa. We sought to reconstruct biogeographical and habitat history, and shifts in diversification rates of African Melastomateae using a well‐sampled, dated molecular phylogeny. Location Americas, sub‐Saharan Africa, Madagascar, SE Asia. Taxon Angiosperms, Melastomataceae, African Melastomateae. Methods Phylogenetic relationships were estimated based on an extensive sampling of New and Old World Melastomateae, using two nuclear and three plastid markers. Divergence times were estimated in BEAST based on three calibration priors under Bayesian uncorrelated lognormal relaxed clock and birth–death speciation process. The dated phylogeny was used to infer the biogeographical history under a dispersal–extinction–cladogenesis model in “BioGeoBEARS”. The ancestral habitat of African Melastomateae was estimated using maximum likelihood and stochastic character mapping in “Phytools” and “ape” respectively. Finally, shifts in diversification rates were tested using BAMM. Results Melastomateae dispersed from South America to Africa during the Oligocene with subsequent dispersals to Madagascar and SE Asia during the Middle Miocene. Ancestral African Melastomateae were adapted to closed habitats with at least 12 shifts to open habitats occurring during the Middle Miocene or Pliocene. Speciation rates steadily increased since the Neogene, and none of the habitat shifts led to a significant increase in diversification rates. Main conclusions Long‐distance dispersal from South America during the Early Miocene explains the origin of African Melastomateae. The inferred adaptation to open habitats from an ancestrally closed habitat is congruent with the Neogene increase of aridity across Africa. The adaptation to open habitats during the Neogene is an important driver of African plant diversity, but is not always followed by increased diversification rates.

Evaluation of days of total collection and use of internal markers in nutritional trials with small ruminants - Catarine S. C. da Teixeira; Gleidson G. P. de Carvalho; Isis C. M. Nicory; Aracele V. Santos; Douglas S. dos Pina; José E. F. de Júnior; Maria L. G. M. L. de Araújo; Luana M. A. de Rufino; Luís G. A. Cirne; Aureliano J. V. Pires (Tropical Animal Health and Production, 2018)

Dietary lipophilic iron accelerates regional brain iron-load in C57BL6 mice - Douglas G. Peters; Carson J. Purnell; Michael P. Haaf; Qing X. Yang; James R. Connor; Mark D. Meadowcroft (Brain Structure and Function, 2018)

Predictive ability of genomic selection models in a multi-population perennial ryegrass training set using genotyping-by-sequencing - Marty J. Faville; Siva Ganesh; Mingshu Cao; M. Z. Zulfi Jahufer; Timothy P. Bilton; H. Sydney Easton; Douglas L. Ryan; Jason A. K. Trethewey; M. Philip Rolston; Andrew G. Griffiths; Roger Moraga; Casey Flay; et al. (Theoretical and Applied Genetics, 2018)

Melanoma risk assessment based on relatives’ age at diagnosis - Yelena P. Wu; Wendy Kohlmann; Karen Curtin; Zhe Yu; Heidi A. Hanson; Mia Hashibe; Bridget G. Parsons; Jathine Wong; Joshua D. Schiffman; Douglas Grossman; Sancy A. Leachman (Cancer Causes & Control, 2018)

Microscopy-based high-throughput assays enable multi-parametric analysis to assess adverse effects of nanomaterials in various cell lines - Iris Hansjosten; Juliane Rapp; Luisa Reiner; Ruben Vatter; Susanne Fritsch-Decker; Ravindra Peravali; Taina Palosaari; Elisabeth Joossens; Kirsten Gerloff; Peter Macko; Maurice Whelan; Douglas Gilliland; et al. (Archives of Toxicology, 2018)

Use of the BOADICEA Web Application in clinical practice: appraisals by clinicians from various countries - Anne Brédart; Jean-Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Sylvie Dolbeault; Léonore Robieux; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Familial Cancer, 2018)

Metabarcoding of freshwater invertebrates to detect the effects of a pesticide spill - Carmelo Andújar; Paula Arribas; Clare Gray; Catherine Bruce; Guy Woodward; Douglas W. Yu; Alfried P. Vogler (Molecular Ecology, 2018)
Biomonitoring underpins the environmental assessment of freshwater ecosystems and guides management and conservation. Current methodology for surveys of (macro)invertebrates uses coarse taxonomic identification where species‐level resolution is difficult to obtain. Next‐generation sequencing of entire assemblages (metabarcoding) provides a new approach for species detection, but requires further validation. We used metabarcoding of invertebrate assemblages with two fragments of the cox1 “barcode” and partial nuclear ribosomal ( SSU ) genes, to assess the effects of a pesticide spill in the River Kennet (southern England). Operational taxonomic unit ( OTU ) recovery was tested under 72 parameters (read denoising, filtering, pair merging and clustering). Similar taxonomic profiles were obtained under a broad range of parameters. The SSU marker recovered Platyhelminthes and Nematoda, missed by cox1 , while Rotifera were only amplified with cox1 . A reference set was created from all available barcode entries for Arthropoda in the BOLD database and clustered into OTU s. The River Kennet metabarcoding produced matches to 207 of these reference OTU s, five times the number of species recognized with morphological monitoring. The increase was due to the following: greater taxonomic resolution (e.g., splitting a single morphotaxon “Chironomidae” into 55 named OTU s); splitting of Linnaean binomials into multiple molecular OTU s; and the use of a filtration‐flotation protocol for extraction of minute specimens (meiofauna). Community analyses revealed strong differences between “impacted” vs. “control” samples, detectable with each gene marker, for each major taxonomic group, and for meio‐ and macrofaunal samples separately. Thus, highly resolved taxonomic data can be extracted at a fraction of the time and cost of traditional nonmolecular methods, opening new avenues for freshwater invertebrate biodiversity monitoring and molecular ecology.

Methodological considerations of terrestrial laser scanning for vegetation monitoring in the sagebrush steppe - Kyle E. Anderson; Nancy F. Glenn; Lucas P. Spaete; Douglas J. Shinneman; David S. Pilliod; Robert S. Arkle; Susan K. McIlroy; DeWayne R. Derryberry (Environmental Monitoring and Assessment, 2017)

Evaluation of a Ferrozine Based Autonomous in Situ Lab-on-Chip Analyzer for Dissolved Iron Species in Coastal Waters - Felix Geißler; Eric P. Achterberg; Alexander D. Beaton; Mark J. Hopwood; Jennifer S. Clarke; André Mutzberg; Matt C. Mowlem; Douglas P. Connelly (Frontiers in Marine Science, 2017)

Serum global metabolomics profiling reveals profound metabolic impairments in patients with MPS IIIA and MPS IIIB - Haiyan Fu; Aaron S. Meadows; Ricardo J. Pineda; Robert P. Mohney; Steve Stirdivant; Douglas M. McCarty (Metabolic Brain Disease, 2017)

The mating system of the symbiotic pea-crab Dissodactylus crinitichelis (Brachyura, Pinnotheridae): monogamy or promiscuity? - Douglas Fernandes Rodrigues Alves; Gustavo Luis Hirose; Samara de P. Barros-Alves; J. Antonio Baeza (Marine Biology, 2017)

Transmembrane helices containing a charged arginine are thermodynamically stable - Martin B. Ulmschneider; Jakob P. Ulmschneider; J. Alfredo Freites; Gunnar von Heijne; Douglas J. Tobias; Stephen H. White (European Biophysics Journal, 2017)

Factors influencing the spatial ecology of Lake Sturgeon and Walleye within an impounded reach of the Winnipeg River - Daniel P. Struthers; Lee F.G. Gutowsky; Eva C. Enders; Karen E. Smokorowski; Douglas A. Watkinson; Ana T. Silva; Maja Cvetkovic; Eric Bibeau; Steven J. Cooke (Environmental Biology of Fishes, 2017)

Extinctions of introduced game species on oceanic islands: curse for hunters or conservation opportunities? - Ricardo Rocha; Miguel M. Sequeira; Leo R. Douglas; Manuela Gouveia; Roberto Jardim; José Jesus; Holly P. Jones; Danilo Russo (Biodiversity and Conservation, 2017)

Increased Arctic sea ice drift alters adult female polar bear movements and energetics - George M. Durner; David C. Douglas; Shannon E. Albeke; John P. Whiteman; Steven C. Amstrup; Evan Richardson; Ryan R. Wilson; Merav Ben‐David (Global Change Biology, 2017)
Recent reductions in thickness and extent have increased drift rates of Arctic sea ice. Increased ice drift could significantly affect the movements and the energy balance of polar bears ( Ursus maritimus ) which forage, nearly exclusively, on this substrate. We used radio‐tracking and ice drift data to quantify the influence of increased drift on bear movements, and we modeled the consequences for energy demands of adult females in the Beaufort and Chukchi seas during two periods with different sea ice characteristics. Westward and northward drift of the sea ice used by polar bears in both regions increased between 1987–1998 and 1999–2013. To remain within their home ranges, polar bears responded to the higher westward ice drift with greater eastward movements, while their movements north in the spring and south in fall were frequently aided by ice motion. To compensate for more rapid westward ice drift in recent years, polar bears covered greater daily distances either by increasing their time spent active (7.6%–9.6%) or by increasing their travel speed (8.5%–8.9%). This increased their calculated annual energy expenditure by 1.8%–3.6% (depending on region and reproductive status), a cost that could be met by capturing an additional 1–3 seals/year. Polar bears selected similar habitats in both periods, indicating that faster drift did not alter habitat preferences. Compounding reduced foraging opportunities that result from habitat loss; changes in ice drift, and associated activity increases, likely exacerbate the physiological stress experienced by polar bears in a warming Arctic.

A Lab-On-Chip Phosphate Analyzer for Long-term In Situ Monitoring at Fixed Observatories: Optimization and Performance Evaluation in Estuarine and Oligotrophic Coastal Waters - Maxime M. Grand; Geraldine S. Clinton-Bailey; Alexander D. Beaton; Allison M. Schaap; Thomas H. Johengen; Mario N. Tamburri; Douglas P. Connelly; Matthew C. Mowlem; Eric P. Achterberg (Frontiers in Marine Science, 2017)

Temporal aspects of polar bear (Ursus maritimus) occurrences at field camps in Wapusk National Park, Canada - Michel P. Laforge; Douglas A. Clark; Aimee L. Schmidt; Jessica L. Lankshear; Sheldon Kowalchuk; Ryan K. Brook (Polar Biology, 2017)

Niche Differentiation and Prey Selectivity among Common Bottlenose Dolphins (Tursiops truncatus) Sighted in St. George Sound, Gulf of Mexico - Rachel M. Wilson; Reny B. Tyson; James A. Nelson; Brian C. Balmer; Jeffrey P. Chanton; Douglas P. Nowacek (Frontiers in Marine Science, 2017)

Novel Bio-Logging Tool for Studying Fine-Scale Behaviors of Marine Turtles in Response to Sound - Reny B. Tyson; Wendy E. D. Piniak; Camila Domit; David Mann; Michael Hall; Douglas P. Nowacek; Mariana M. P. B. Fuentes (Frontiers in Marine Science, 2017)

Designing a global assessment of climate change on inland fishes and fisheries: knowns and needs - Craig P. Paukert; Abigail J. Lynch; T. Douglas Beard; Yushun Chen; Steven J. Cooke; Michael S. Cooperman; Ian G. Cowx; Lilian Ibengwe; Dana M. Infante; Bonnie J. E. Myers; Hòa Phú Nguyễn; Ian J. Winfield (Reviews in Fish Biology and Fisheries, 2017)

Methylene blue modulates functional connectivity in the human brain - Pavel Rodriguez; Amar P. Singh; Kristen E. Malloy; Wei Zhou; Douglas W. Barrett; Crystal G. Franklin; Wilson B. Altmeyer; Juan E. Gutierrez; Jinqi Li; Betty L. Heyl; Jack L. Lancaster; F. Gonzalez-Lima; et al. (Brain Imaging and Behavior, 2017)

Impact of Fiber Structure on the Material Stability and Rupture Mechanisms of Coronary Atherosclerotic Plaques - Graeham R. Douglas; Adam J. Brown; Jonathan H. Gillard; Martin R. Bennett; Michael P. F. Sutcliffe; Zhongzhao Teng (Annals of Biomedical Engineering, 2017)

Estimating partial regulation in spatiotemporal models of community dynamics - James T. Thorson; Stephan B. Munch; Douglas P. Swain (Ecology, 2017)
Niche‐based approaches to community analysis often involve estimating a matrix of pairwise interactions among species (the “community matrix”), but this task becomes infeasible using observational data as the number of modeled species increases. As an alternative, neutral theories achieve parsimony by assuming that species within a trophic level are exchangeable, but generally cannot incorporate stabilizing interactions even when they are evident in field data. Finally, both regulated (niche) and unregulated (neutral) approaches have rarely been fitted directly to survey data using spatiotemporal statistical methods. We therefore propose a spatiotemporal and model‐based approach to estimate community dynamics that are partially regulated. Specifically, we start with a neutral spatiotemporal model where all species follow ecological drift, which precludes estimating pairwise interactions. We then add regulatory relations until model selection favors stopping, where the “rank” of the interaction matrix may range from zero to the number of species. A simulation experiment shows that model selection can accurately identify the rank of the interaction matrix, and that the identified spatiotemporal model can estimate the magnitude of species interactions. A 40‐yr case study for the Gulf of St. Lawrence marine community shows that recovering grey seals have an unregulated and negative relationship with demersal fishes. We therefore conclude that partial regulation is a plausible approximation to community dynamics using field data and hypothesize that estimating partial regulation will be expedient in future analyses of spatiotemporal community dynamics given limited field data. We conclude by recommending ongoing research to add explicit models for movement, so that meta‐community theory can be confronted with data in a spatiotemporal statistical framework.

Microglia activation and phagocytosis: relationship with aging and cognitive impairment in the rhesus monkey - Eli Shobin; Michael P. Bowley; Larissa I. Estrada; Nadine C. Heyworth; Mary E. Orczykowski; Sherri A. Eldridge; Samantha M. Calderazzo; Farzad Mortazavi; Tara L. Moore; Douglas L. Rosene (GeroScience, 2017)

Factors driving the variability in diving and movement behavior of migrating humpback whales ( Megaptera novaeangliae ): Implications for anthropogenic disturbance studies - Ailbhe S. Kavanagh; Michael J. Noad; Simon P. Blomberg; Anne W. Goldizen; Eric Kniest; Douglas H. Cato; Rebecca A. Dunlop (Marine Mammal Science, 2017)
Humpback whales ( Megaptera novaeangliae ) undertake one of the longest migrations of any animal and while on a broad‐scale this journey appears direct, on a fine‐scale, behaviors associated with socializing and breeding are regularly observed. However, little is known about which social and environmental factors influence behavior during this time. Here we examined the effect of multiple factors on the movement (speed and course) and diving behavior (dive and surfacing duration) of humpback whales during migration off the eastern coast of Australia. Focal data (202 h) were collected on 94 different whale groups with simultaneous social and environmental context data. The environmental factors water depth and wind speed were found to be important predictors of dive and movement behavior, whereas social factors were less influential at this site. Groups tended to dive for longer with increased water depth but traveled more slowly in increasing wind speeds. These baseline studies are crucial when examining the effect of anthropogenic disturbance. Determining which natural factors significantly affect behavior ensures any observed behavioral changes are correctly attributed to the disturbance and are not a result of other factors. In addition, any responses observed can be put into biological context and their relative magnitude determined.

Ex situ genetic conservation potential of seeds of two high elevation white pines - Richard A. Sniezko; Angelia Kegley; Douglas P. Savin (New Forests, 2017)

Trace Element Scavenging in Dry Wash Surficial Sediments in an Arid Region of Southern Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Vatalis I. Konstantinos; Modis P. Konstantinos (Mine Water and the Environment, 2017)

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

Body size drives allochthony in food webs of tropical rivers - Timothy D. Jardine; Thomas S. Rayner; Neil E. Pettit; Dominic Valdez; Douglas P. Ward; Garry Lindner; Michael M. Douglas; Stuart E. Bunn (Oecologia, 2017)

Habitat degradation disrupts neophobia in juvenile coral reef fish - Mark I. McCormick; Douglas P. Chivers; Bridie J. M. Allan; Maud C. O. Ferrari (Global Change Biology, 2017)
Habitat degradation not only disrupts habitat‐forming species, but alters the sensory landscape within which most species must balance behavioural activities against predation risk. Rapidly developing a cautious behavioural phenotype, a condition known as neophobia, is advantageous when entering a novel risky habitat. Many aquatic organisms rely on damage‐released conspecific cues (i.e. alarm cues) as an indicator of impending danger and use them to assess general risk and develop neophobia. This study tested whether settlement‐stage damselfish associated with degraded coral reef habitats were able to use alarm cues as an indicator of risk and, in turn, develop a neophobic response at the end of their larval phase. Our results indicate that fish in live coral habitats that were exposed to alarm cues developed neophobia, and, in situ , were found to be more cautious, more closely associated with their coral shelters and survived four‐times better than non‐neophobic control fish. In contrast, fish that settled onto degraded coral habitats did not exhibit neophobia and consequently suffered much greater mortality on the reef, regardless of their history of exposure to alarm cues. Our results show that habitat degradation alters the efficacy of alarm cues with phenotypic and survival consequences for newly settled recruits.

Evidence for the functions of surface‐active behaviors in humpback whales ( Megaptera novaeangliae ) - Ailbhe S. Kavanagh; Kylie Owen; Michael J. Williamson; Simon P. Blomberg; Michael J. Noad; Anne W. Goldizen; Eric Kniest; Douglas H. Cato; Rebecca A. Dunlop (Marine Mammal Science, 2017)
As part of their social sound repertoire, migrating humpback whales ( Megaptera novaeangliae ) perform a large variety of surface‐active behaviors, such as breaching and repetitive slapping of the pectoral fins and tail flukes; however, little is known about what factors influence these behaviors and what their functions might be. We investigated the potential functions of surface‐active behaviors in humpback whale groups by examining the social and environmental contexts in which they occurred. Focal observations on 94 different groups of whales were collected in conjunction with continuous acoustic monitoring, and data on the social and environmental context of each group. We propose that breaching may play a role in communication between distant groups as the probability of observing this behavior decreased significantly when the nearest whale group was within 4,000 m compared to beyond 4,000 m. Involvement in group interactions, such as the splitting of a group or a group joining with other whales, was an important factor in predicting the occurrence of pectoral, fluke, and peduncle slapping, and we suggest that they play a role in close‐range or within‐group communication. This study highlights the potentially important and diverse roles of surface‐active behaviors in the communication of migrating humpback whales.

Collaborative research partnerships inform monitoring and management of aquatic ecosystems by Indigenous rangers - Rebecca J. Dobbs; Christy L. Davies; Michelle L. Walker; Neil E. Pettit; Bradley J. Pusey; Paul G. Close; Yoshi Akune; Ninjana Walsham; Brendan Smith; Albert Wiggan; Preston Cox; Douglas P. Ward; et al. (Reviews in Fish Biology and Fisheries, 2016)

The distribution, diversity and function of predominant Thermoproteales in high‐temperature environments of Yellowstone National Park - Zackary J. Jay; Jacob P. Beam; Mark A. Kozubal; Ryan deM. Jennings; Douglas B. Rusch; William P. Inskeep (Environmental Microbiology, 2016)
Summary High‐temperature environments (> 70°C) contain diverse and abundant members of the crenarchaeal order Thermoproteales. However, a comprehensive study of the distribution and function of diverse members of this group across different habitat types has not been conducted. Consequently, the goals of this study were to determine the distribution of different Thermoproteales genera across geochemically distinct geothermal habitats of Yellowstone National Park, and to identify key functional attributes of major genera that correlate with environmental parameters. Curated sequence assemblies belonging to five genera were characterized in replicate samples of 11 high‐temperature communities ranging in pH from 3 to 9. Thermocladium , Vulcanisaeta and Caldivirga spp. were the primary Thermoproteales populations present in low pH (pH Thermoproteus populations were found in mildly‐acidic (pH 5–6) sulfur sediments, and Pyrobaculum populations were confined to higher pH (pH > 6) sulfur sediments and/or filamentous ‘streamer’ communities. Metabolic reconstruction and comparative genomics among assemblies show that these populations are primarily chemoorganotrophs that utilize different electron acceptors depending on geochemical conditions. The presence of potential CO 2 fixation pathways in some Thermoproteales populations appears to be linked with NiFe hydrogenases, which combined with high levels of H 2 in many sulfidic systems, may provide the energy required to fix inorganic C.

Turnover of hydrogen isotopes in lake sturgeon blood: implications for tracking movements of wild populations - Natasha M. Kreitals; Keith A. Hobson; Brittney M. Hoemsen; Adam L. Crane; Van Wishingrad; Janelle Sloychuk; Michael S. Pollock; Douglas P. Chivers; Iain D. Phillips (Isotopes in Environmental and Health Studies, 2016)

First detection of the crayfish plague pathogen Aphanomyces astaci in South America: a high potential risk to native crayfish - Douglas Fernando Peiró; Mauricio P. Almerão; Carine Delaunay; Japo Jussila; Jenny Makkonen; Didier Bouchon; Paula B. Araujo; Catherine Souty-Grosset (Hydrobiologia, 2016)

Strength and Persistence of Energy-Based Vessel Seals Rely on Tissue Water and Glycosaminoglycan Content - Eric A. Kramer; James D. Cezo; Douglas P. Fankell; Kenneth D. Taylor; Mark E. Rentschler; Virginia L. Ferguson (Annals of Biomedical Engineering, 2016)

A Novel Parameter for Predicting Arterial Fusion and Cutting in Finite Element Models - Douglas P. Fankell; Eric Kramer; James Cezo; Ken D. Taylor; Virginia L. Ferguson; Mark E. Rentschler (Annals of Biomedical Engineering, 2016)

Intake and ingestive behavior in lambs fed low-digestibility forages - Antônio E. Filho; Gleidson G. P. Carvalho; Aureliano J. V. Pires; Robério R. Silva; Paulo E. F. Santos; Rogério M. Murta; Fabiano M. Pereira; Bruna M. A. Carvalho; Camila M. A. Maranhão; Luana M. A. Rufino; Stefanie A. Santos; Douglas S. Pina (Tropical Animal Health and Production, 2016)

Late Pleistocene climate inferences from a water balance model of Jakes Valley, Nevada (USA) - Cornelia Barth; Douglas P. Boyle; Benjamin J. Hatchett; Scott D. Bassett; Christopher B. Garner; Kenneth D. Adams (Journal of Paleolimnology, 2016)

Diet cues alter the development of predator recognition templates in tadpoles - Matthew D. Mitchell; Maud C. O. Ferrari; Tyrone Lucon-Xiccato; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2016)

The potential and pitfalls of de‐extinction - Douglas J. Richmond; Mikkel‐Holger S. Sinding; M. Thomas P. Gilbert (Zoologica Scripta, 2016)
‘De‐extinction’ is the nascent discipline that aims to one day literally revive now‐extinct species from the dead. Although we have yet to see any successful attempts to truly resurrect an extinct species, several technologies are now in place that might one day provide a plausible solution. Thus, the area is receiving increased attention from both scientists and the general public. However, how far does present technology place us from the ultimate goal? We address the state of the art of several prominent de‐extinction methods: back‐breeding, cloning, synthetic genomics and genome editing, and discuss some of the major outstanding challenges for each. We also discuss some of the wider challenges facing de‐extinction, including both what might constitute the definition of success and what might be needed to successfully take a recreated animal and confer on it the ability to establish itself back in the wild.

Guiding principles for the development and application of solid-phase phosphorus adsorbents for freshwater ecosystems - G. B. Douglas; D. P. Hamilton; M. S. Robb; G. Pan; B. M. Spears; M. Lurling (Aquatic Ecology, 2016)

Recent Scientific Publications Cast Doubt on North Atlantic Right Whale Future - Scott D. Kraus; Robert D. Kenney; Charles A. Mayo; William A. McLellan; Michael J. Moore; Douglas P. Nowacek (Frontiers in Marine Science, 2016)

Seasonal nutritional status in Norway lobsters, Nephrops norvegicus (L.): are females nutritionally compromised over the winter? - Andrew J. R. Watts; Amaya Albalat; Ian P. Smith; Robert J. A. Atkinson; Douglas M. Neil (Marine Biology Research, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Seasonal changes in atmospheric noise levels and the annual variation in pigeon homing performance - Jonathan T. Hagstrum; Hugh P. McIsaac; Douglas P. Drob (Journal of Comparative Physiology A, 2016)

Costs of reproduction can explain the correlated evolution of semelparity and egg size: theory and a test with salmon - Holly K. Kindsvater; Douglas C. Braun; Sarah P. Otto; John D. Reynolds (Ecology Letters, 2016)
Species’ life history traits, including maturation age, number of reproductive bouts, offspring size and number, reflect adaptations to diverse biotic and abiotic selection pressures. A striking example of divergent life histories is the evolution of either iteroparity (breeding multiple times) or semelparity (breed once and die). We analysed published data on salmonid fishes and found that semelparous species produce larger eggs, that egg size and number increase with salmonid body size among populations and species and that migratory behaviour and parity interact. We developed three hypotheses that might explain the patterns in our data and evaluated them in a stage‐structured modelling framework accounting for different growth and survival scenarios. Our models predict the observation of small eggs in iteroparous species when egg size is costly to maternal survival or egg number is constrained. By exploring trait co‐variation in salmonids, we generate new hypotheses for the evolution of trade‐offs among life history traits.

PlanTE-MIR DB: a database for transposable element-related microRNAs in plant genomes - Alan P. R. Lorenzetti; Gabriel Y. A. de Antonio; Alexandre R. Paschoal; Douglas S. Domingues (Functional & Integrative Genomics, 2016)

Multiple processes generate productivity–diversity relationships in experimental wood‐fall communities - Craig R. McClain; James P. Barry; Douglas Eernisse; Tammy Horton; Jenna Judge; Keiichi Kakui; Chris Mah; Anders Warén (Ecology, 2016)
Energy availability has long been recognized as a predictor of community structure, and changes in both terrestrial and marine productivity under climate change necessitate a deeper understanding of this relationship. The productivity–diversity relationship (PDR) is well explored in both empirical and theoretical work in ecology, but numerous questions remain. Here, we test four different theories for PDRs (More‐Individuals Hypothesis, Resource‐Ratio Theory, More Specialization Theory, and the Connectivity–Diversity Hypothesis) with experimental deep‐sea wood falls. We manipulated productivity by altering wood‐fall sizes and measured responses after 5 and 7 years. In November 2006, 32 Acacia sp. logs were deployed at 3203 m in the Northeast Pacific Ocean (Station Deadwood: 36.154098° N, 122.40852° W). Overall, we found a significant increase in diversity with increased wood‐fall size for these communities. Increases in diversity with wood‐fall size occurred because of the addition of rare species and increases of overall abundance, although individual species responses varied. We also found that limited dispersal helped maintain the positive PDR relationship. Our experiment suggests that multiple interacting mechanisms influence PDRs.

Nitrogen sources and net growth efficiency of zooplankton in three A mazon River plume food webs - Natalie Loick‐Wilde; Sarah C. Weber; Brandon J. Conroy; Douglas G. Capone; Victoria J. Coles; Patricia M. Medeiros; Deborah K. Steinberg; Joseph P. Montoya (Limnology and Oceanography, 2016)

Determining optimal diagnostic criteria through chronicity and comorbidity - Douglas Steinley; Sean P. Lane; Kenneth J. Sher (In Silico Pharmacology, 2016)
Purpose Contemporary approaches to clinical diagnosis have not adequately exploited state-of-the-art empirical techniques in deriving diagnostic criterion sets that are statistically optimal based on 1) relevant external indicators and 2) replicability across data sets. We provide a proof of concept that optimal criterion sets can be derived with respect to alcohol use disorder (AUD) diagnosis that are both more efficient and precise than current systems. Methods Using data from the National Epidemiologic Survey on Alcohol and Related Conditions we selected chronicity (i.e. persistence) of AUD diagnosis and comorbidity of AUD with other disorders as validation criteria on which to optimize the size of the AUD criterion set and the threshold for AUD diagnosis. We used cross-validation and consensus approaches for choosing a final solution. Results Cross-validation did not produce a solution that replicated across random subsamples or differed from conventional diagnosis. Alternatively, consensus produced a more global solution that was associated with greater validity than “conventional” diagnosis. Conclusion Such methods, if applied to extant diagnostic criteria and algorithms can generate simpler and more reliable rules and hold promise for greatly reducing misclassification of individuals in both research and applied clinical contexts.

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Toward an integrated monitoring framework to assess the effects of tropical forest degradation and recovery on carbon stocks and biodiversity - Mercedes M. C. Bustamante; Iris Roitman; T. Mitchell Aide; Ane Alencar; Liana O. Anderson; Luiz Aragão; Gregory P. Asner; Jos Barlow; Erika Berenguer; Jeffrey Chambers; Marcos H. Costa; Thierry Fanin; et al. (Global Change Biology, 2016)
Tropical forests harbor a significant portion of global biodiversity and are a critical component of the climate system. Reducing deforestation and forest degradation contributes to global climate‐change mitigation efforts, yet emissions and removals from forest dynamics are still poorly quantified. We reviewed the main challenges to estimate changes in carbon stocks and biodiversity due to degradation and recovery of tropical forests, focusing on three main areas: (1) the combination of field surveys and remote sensing; (2) evaluation of biodiversity and carbon values under a unified strategy; and (3) research efforts needed to understand and quantify forest degradation and recovery. The improvement of models and estimates of changes of forest carbon can foster process‐oriented monitoring of forest dynamics, including different variables and using spatially explicit algorithms that account for regional and local differences, such as variation in climate, soil, nutrient content, topography, biodiversity, disturbance history, recovery pathways, and socioeconomic factors. Generating the data for these models requires affordable large‐scale remote‐sensing tools associated with a robust network of field plots that can generate spatially explicit information on a range of variables through time. By combining ecosystem models, multiscale remote sensing, and networks of field plots, we will be able to evaluate forest degradation and recovery and their interactions with biodiversity and carbon cycling. Improving monitoring strategies will allow a better understanding of the role of forest dynamics in climate‐change mitigation, adaptation, and carbon cycle feedbacks, thereby reducing uncertainties in models of the key processes in the carbon cycle, including their impacts on biodiversity, which are fundamental to support forest governance policies, such as Reducing Emissions from Deforestation and Forest Degradation.

Atomic connectomics signatures for characterization and differentiation of mild cognitive impairment - Jinli Ou; Li Xie; Xiang Li; Dajiang Zhu; Douglas P. Terry; A. Nicholas Puente; Rongxin Jiang; Yaowu Chen; Lihong Wang; Dinggang Shen; Jing Zhang; L. Stephen Miller; et al. (Brain Imaging and Behavior, 2015)

Reducing Neointima Formation in a Swine Model with IVUS and Sirolimus Microbubbles - Joseph P. Kilroy; Ali H. Dhanaliwala; Alexander L. Klibanov; Douglas K. Bowles; Brian R. Wamhoff; John A. Hossack (Annals of Biomedical Engineering, 2015)

Phosphorus and nitrogen losses from poultry litter stacks and leaching through soils - Jian Liu; Peter J. A. Kleinman; Douglas B. Beegle; Jennifer L. Weld; Andrew N. Sharpley; Lou S. Saporito; John P. Schmidt (Nutrient Cycling in Agroecosystems, 2015)

Bay breeze influence on surface ozone at Edgewood, MD during July 2011 - Ryan M. Stauffer; Anne M. Thompson; Douglas K. Martins; Richard D. Clark; Daniel L. Goldberg; Christopher P. Loughner; Ruben Delgado; Russell R. Dickerson; Jeffrey W. Stehr; Maria A. Tzortziou (Journal of Atmospheric Chemistry, 2015)

Considering sampling approaches when determining carnivore diets: the importance of where, how, and when scats are collected - Robin Steenweg; Michael P. Gillingham; Katherine L. Parker; Douglas C. Heard (Mammal Research, 2015)

Leaching of copper and nickel in soil-water systems contaminated by bauxite residue (red mud) from Ajka, Hungary: the importance of soil organic matter - Cindy L. Lockwood; Douglas I. Stewart; Robert J. G. Mortimer; William M. Mayes; Adam P. Jarvis; Katalin Gruiz; Ian T. Burke (Environmental Science and Pollution Research, 2015)

Background risk and recent experience influences retention of neophobic responses to predators - Grant E. Brown; Chris K. Elvidge; Indar Ramnarine; Maud C. O. Ferrari; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2015)

Interactive effects of ocean acidification and rising sea temperatures alter predation rate and predator selectivity in reef fish communities - Maud. C. O. Ferrari; Philip L. Munday; Jodie L. Rummer; Mark I. McCormick; Katherine Corkill; Sue‐Ann Watson; Bridie J. M. Allan; Mark G. Meekan; Douglas P. Chivers (Global Change Biology, 2015)
Ocean warming and acidification are serious threats to marine life. While each stressor alone has been studied in detail, their combined effects on the outcome of ecological interactions are poorly understood. We measured predation rates and predator selectivity of two closely related species of damselfish exposed to a predatory dottyback. We found temperature and CO 2 interacted synergistically on overall predation rate, but antagonistically on predator selectivity. Notably, elevated CO 2 or temperature alone reversed predator selectivity, but the interaction between the two stressors cancelled selectivity. Routine metabolic rates of the two prey showed strong species differences in tolerance to CO 2 and not temperature, but these differences did not correlate with recorded mortality. This highlights the difficulty of linking species‐level physiological tolerance to resulting ecological outcomes. This study is the first to document both synergistic and antagonistic effects of elevated CO 2 and temperature on a crucial ecological process like predator–prey dynamics.

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Phylogenetic distribution of symbiotic bacteria from Panamanian amphibians that inhibit growth of the lethal fungal pathogen Batrachochytrium dendrobatidis - Matthew H. Becker; Jenifer B. Walke; Lindsey Murrill; Douglas C. Woodhams; Laura K. Reinert; Louise A. Rollins‐Smith; Elizabeth A. Burzynski; Thomas P. Umile; Kevin P. C. Minbiole; Lisa K. Belden (Molecular Ecology, 2015)
The introduction of next‐generation sequencing has allowed for greater understanding of community composition of symbiotic microbial communities. However, determining the function of individual members of these microbial communities still largely relies on culture‐based methods. Here, we present results on the phylogenetic distribution of a defensive functional trait of cultured symbiotic bacteria associated with amphibians. Amphibians are host to a diverse community of cutaneous bacteria and some of these bacteria protect their host from the lethal fungal pathogen Batrachochytrium dendrobatidis (Bd) by secreting antifungal metabolites. We cultured over 450 bacterial isolates from the skins of Panamanian amphibian species and tested their interactions with Bd using an in vitro challenge assay. For a subset of isolates, we also completed coculture experiments and found that culturing isolates with Bd had no effect on inhibitory properties of the bacteria, but it significantly decreased metabolite secretion. In challenge assays, approximately 75% of the bacterial isolates inhibited Bd to some extent and these inhibitory isolates were widely distributed among all bacterial phyla. Although there was no clear phylogenetic signal of inhibition, three genera, Stenotrophomonas, Aeromonas and Pseudomonas, had a high proportion of inhibitory isolates (100%, 77% and 73%, respectively). Overall, our results demonstrate that antifungal properties are phylogenetically widespread in symbiotic microbial communities of Panamanian amphibians and that some functional redundancy for fungal inhibition occurs in these communities. We hope that these findings contribute to the discovery and development of probiotics for amphibians that can mitigate the threat of chytridiomycosis.

Association of TGF-β2 levels in breast milk with severity of breast biopsy diagnosis - Hannah P. Yang; Sallie Smith Schneider; Christina M. Chisholm; Eva P. Browne; Sidra Mahmood; Gretchen L. Gierach; Sarah Lenington; Douglas L. Anderton; Mark E. Sherman; Kathleen F. Arcaro (Cancer Causes & Control, 2015)

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Treatment of exertional heat stress developed during low or moderate physical work - Andreas D. Flouris; Heather E. Wright-Beatty; Brian J. Friesen; Douglas J. Casa; Glen P. Kenny (European Journal of Applied Physiology, 2014)

Nasal chondromesenchymal hamartomas arise secondary to germline and somatic mutations of DICER1 in the pleuropulmonary blastoma tumor predisposition disorder - Douglas R. Stewart; Yoav Messinger; Gretchen M. Williams; Jiandong Yang; Amanda Field; Kris Ann P. Schultz; Laura A. Harney; Leslie A. Doros; Louis P. Dehner; D. Ashley Hill (Human Genetics, 2014)

Homeologous genes involved in mannitol synthesis reveal unequal contributions in response to abiotic stress in Coffea arabica - Kenia de Carvalho; Carmen L. O. Petkowicz; Getulio T. Nagashima; João C. Bespalhok Filho; Luiz G. E. Vieira; Luiz F. P. Pereira; Douglas S. Domingues (Molecular Genetics and Genomics, 2014)

The effect of seasonal and long-period geopotential variations on the GPS orbits - Stavros A. Melachroinos; Frank G. Lemoine; Douglas S. Chinn; Nikita P. Zelensky; Joseph B. Nicholas; Brian D. Beckley (GPS Solutions, 2014)

The paradox of marine heterotrophic nitrogen fixation: abundances of heterotrophic diazotrophs do not account for nitrogen fixation rates in the E astern T ropical S outh P acific - Kendra A. Turk‐Kubo; Muskan Karamchandani; Douglas G. Capone; Jonathan P. Zehr (Environmental Microbiology, 2014)
Summary Results of recent modelling efforts imply denitrification‐influenced waters, such as those in the E astern T ropical S outh P acific ( ETSP ), may support high rates of biological nitrogen fixation ( BNF ), yet little is known about the N 2 ‐fixing microbial community in this region. Our characterization of the ETSP diazotrophic community along a gradient from upwelling‐influenced to oligotrophic waters did not detect cyanobacterial diazotrophs commonly found in other open ocean regions. Most of the nifH genes amplified by polymerase chain reaction ( PCR ) from DNA and RNA samples clustered with γ‐proteobacterial nifH sequences, although a novel T richodesmium phylotype was also recovered. Three quantitative PCR assays were developed to target γ‐proteobacterial phylotypes, but all were found to be present at low abundances. An analysis of the expected BNF rates based on abundances and plausible cell‐specific N 2 fixation rates indicates that these γ‐proteobacteria are unlikely to be responsible for previously reported BNF rates from corresponding samples. Therefore, the organisms responsible for the measured BNF rates remain poorly understood. Furthermore, there is little direct evidence, at this time, to support the hypothesis that heterotrophic N 2 fixation contributes significantly to oceanic BNF rates based on our analysis of heterotrophic cell‐specific N 2 fixation rates required to explain BNF rates reported in previously published studies.

Reliance of mobile species on sensitive habitats: a case study of manta rays (Manta alfredi) and lagoons - Douglas J. McCauley; Paul A. DeSalles; Hillary S. Young; Yannis P. Papastamatiou; Jennifer E. Caselle; Mark H. Deakos; Jonathan P. A. Gardner; David W. Garton; John D. Collen; Fiorenza Micheli (Marine Biology, 2014)

Modeling the Potential Impacts of Climate Change on Pacific Salmon Culture Programs: An Example at Winthrop National Fish Hatchery - Kyle C. Hanson; Douglas P. Peterson (Environmental Management, 2014)

The Effects of Chronic Exposure to Environmentally Relevant Levels of Waterborne Cadmium on Reproductive Capacity and Behaviour in Fathead Minnows - Yinxian Wang; Maud C. O. Ferrari; Zachary Hoover; Ali M. Yousafzai; Douglas P. Chivers; Som Niyogi (Archives of Environmental Contamination and Toxicology, 2014)

Estimated SLR station position and network frame sensitivity to time-varying gravity - Nikita P. Zelensky; Frank G. Lemoine; Douglas S. Chinn; Stavros Melachroinos; Brian D. Beckley; Jennifer Wiser Beall; Oleg Bordyugov (Journal of Geodesy, 2014)

Assessing the influence of habitat quality on movements of the endangered shortnose sturgeon - Daniel J. Farrae; Shannon E. Albeke; Krishna Pacifici; Nathan P. Nibbelink; Douglas L. Peterson (Environmental Biology of Fishes, 2014)

Observing Global Surface Water Flood Dynamics - Paul D. Bates; Jefferey C. Neal; Douglas Alsdorf; Guy J.-P. Schumann (Surveys in Geophysics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Frugal cannibals: how consuming conspecific tissues can provide conditional benefits to wood frog tadpoles (Lithobates sylvaticus) - Dale M. Jefferson; Keith A. Hobson; Brandon S. Demuth; Maud C. O. Ferrari; Douglas P. Chivers (The Science of Nature, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Reference database for seismic ground-motion in Europe (RESORCE) - S. Akkar; M. A. Sandıkkaya; M. Şenyurt; A. Azari Sisi; B. Ö. Ay; P. Traversa; J. Douglas; F. Cotton; L. Luzi; B. Hernandez; S. Godey (Bulletin of Earthquake Engineering, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Assessing the efficacy of chironomid and diatom assemblages in tracking eutrophication in High Arctic sewage ponds - E. M. Stewart; R. McIver; N. Michelutti; M. S. V. Douglas; J. P. Smol (Hydrobiologia, 2014)

Background level of risk determines the intensity of predator neophobia in juvenile convict cichlids - Grant E. Brown; Douglas P. Chivers; Chris K. Elvidge; Christopher D. Jackson; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2014)

An evaluation of lipid extraction techniques for interpretation of carbon and nitrogen isotope values in bottlenose dolphin ( Tursiops truncatus ) skin tissue - Rachel Marie Wilson; Jeffrey P. Chanton; Brian C. Balmer; Douglas P. Nowacek (Marine Mammal Science, 2014)
We studied the effects of two common chemical extraction techniques on bottlenose dolphin ( Tursiops truncatus ) skin tissues with the intent to develop a mathematical lipid correction for dolphin skin δ 13 C. One method employs a hot solvent mixture (chloroform and methanol) while the other method requires washing the samples with cold solvent followed by water. The water wash method resulted in significant alteration of tissue δ 15 N. We found no correlation between change in sample mass and C/N or between change in sample mass and the change in δ 13 C (Δδ 13 C) following lipid extraction. Although Δδ 13 C was positive following lipid extraction (mean = 1.6‰ and 1.2‰, for the two methods), there was no correlation between C/N and Δδ 13 C for either method. Cumulatively, these results prevented us from applying a mathematical lipid normalization. Based on our findings and consideration of previously reported results, we suggest that applying these extraction techniques to dolphin skin with C/N 13 C needs to be accounted for when implementing isotope mixing models to assess diet or organic matter sources.

Butterfly distribution in fragmented landscapes containing agroforestry practices in Southeastern Brazil - Wendy Francesconi; P. K. R. Nair; Douglas J. Levey; Jaret Daniels; Laury Cullen (Agroforestry Systems, 2013)

Modeling Combined Geological and Grade Uncertainty: Application of Multiple-Point Simulation at the Apensu Gold Deposit, Ghana - P. Jones; I. Douglas; A. Jewbali (Mathematical Geosciences, 2013)

Towards a unified paradigm for sequence‐based identification of fungi - Urmas Kõljalg; R. Henrik Nilsson; Kessy Abarenkov; Leho Tedersoo; Andy F. S. Taylor; Mohammad Bahram; Scott T. Bates; Thomas D. Bruns; Johan Bengtsson‐Palme; Tony M. Callaghan; Brian Douglas; Tiia Drenkhan; et al. (Molecular Ecology, 2013)
The nuclear ribosomal internal transcribed spacer ( ITS ) region is the formal fungal barcode and in most cases the marker of choice for the exploration of fungal diversity in environmental samples. Two problems are particularly acute in the pursuit of satisfactory taxonomic assignment of newly generated ITS sequences: (i) the lack of an inclusive, reliable public reference data set and (ii) the lack of means to refer to fungal species, for which no Latin name is available in a standardized stable way. Here, we report on progress in these regards through further development of the UNITE database ( http://unite.ut.ee ) for molecular identification of fungi. All fungal species represented by at least two ITS sequences in the international nucleotide sequence databases are now given a unique, stable name of the accession number type (e.g. H ymenoscyphus pseudoalbidus | GU 586904| SH 133781.05 FU ), and their taxonomic and ecological annotations were corrected as far as possible through a distributed, third‐party annotation effort. We introduce the term ‘species hypothesis’ ( SH ) for the taxa discovered in clustering on different similarity thresholds (97–99%). An automatically or manually designated sequence is chosen to represent each such SH. These reference sequences are released ( http://unite.ut.ee/repository.php ) for use by the scientific community in, for example, local sequence similarity searches and in the QIIME pipeline. The system and the data will be updated automatically as the number of public fungal ITS sequences grows. We invite everybody in the position to improve the annotation or metadata associated with their particular fungal lineages of expertise to do so through the new Web‐based sequence management system in UNITE .

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Hyperbaric biofilms on engineering surfaces formed in the deep sea - Alexandra Meier; Nefeli-Maria Tsaloglou; Matthew C. Mowlem; C. William Keevil; Douglas P. Connelly (Biofouling, 2013)

Gypsum addition to soils contaminated by red mud: implications for aluminium, arsenic, molybdenum and vanadium solubility - Alizée P. Lehoux; Cindy L. Lockwood; William M. Mayes; Douglas I. Stewart; Robert J. G. Mortimer; Katalin Gruiz; Ian T. Burke (Environmental Geochemistry and Health, 2013)

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Global DNA methylation profiles of somatic embryos of peach palm (Bactris gasipaes Kunth) are influenced by cryoprotectants and droplet-vitrification cryopreservation - Angelo S. Heringer; Douglas A. Steinmacher; Hugo P. F. Fraga; Leila N. Vieira; Joseph Francis Ree; Miguel P. Guerra (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Plant functional types and traits as biodiversity indicators for tropical forests: two biogeographically separated case studies including birds, mammals and termites - Andrew N. Gillison; David E. Bignell; Kenneth R. W. Brewer; Erick C. M. Fernandes; David T. Jones; Douglas Sheil; Peter H. May; Allan D. Watt; Reginaldo Constantino; Eduardo G. Couto; Kurniatun Hairiah; Paul Jepson; et al. (Biodiversity and Conservation, 2013)

Linking anti‐predator behaviour to prey demography reveals limited risk effects of an actively hunting large carnivore - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; Michael D. Jimenez; Rachel C. Cook; John G. Cook; Shannon E. Albeke; Hall Sawyer; P. J. White (Ecology Letters, 2013)
Ecological theory predicts that the diffuse risk cues generated by wide‐ranging, active predators should induce prey behavioural responses but not major, population‐ or community‐level consequences. We evaluated the non‐consumptive effects ( NCE s) of an active predator, the grey wolf ( Canis lupus ), by simultaneously tracking wolves and the behaviour, body fat, and pregnancy of elk ( Cervus elaphus ), their primary prey in the Greater Yellowstone Ecosystem. When wolves approached within 1 km, elk increased their rates of movement, displacement and vigilance. Even in high‐risk areas, however, these encounters occurred only once every 9 days. Ultimately, despite 20‐fold variation in the frequency of encounters between wolves and individual elk, the risk of predation was not associated with elk body fat or pregnancy. Our findings suggest that the ecological consequences of actively hunting large carnivores, such as the wolf, are more likely transmitted by consumptive effects on prey survival than NCE s on prey behaviour.

Adapting to inversion of the visual field: a new twist on an old problem - Timothy P. Lillicrap; Pablo Moreno-Briseño; Rosalinda Diaz; Douglas B. Tweed; Nikolaus F. Troje; Juan Fernandez-Ruiz (Experimental Brain Research, 2013)

Gene expression analysis distinguishes tissue-specific and gender-related functions among adult Ascaris suum tissues - Zhengyuan Wang; Xin Gao; John Martin; Yong Yin; Sahar Abubucker; Amy C. Rash; Ben-Wen Li; Bill Nash; Kym Hallsworth-Pepin; Douglas P. Jasmer; Makedonka Mitreva (Molecular Genetics and Genomics, 2013)

Mitigating amphibian chytridiomycosis with bioaugmentation: characteristics of effective probiotics and strategies for their selection and use - Molly C. Bletz; Andrew H. Loudon; Matthew H. Becker; Sara C. Bell; Douglas C. Woodhams; Kevin P. C. Minbiole; Reid N. Harris (Ecology Letters, 2013)
Probiotic therapy through bioaugmentation is a feasible disease mitigation strategy based on growing evidence that microbes contribute to host defences of plants and animals. Amphibians are currently threatened by the rapid global spread of the pathogen, Batrachochytrium dendrobatidis (Bd), which causes the disease chytridiomycosis. Bioaugmentation of locally occurring protective bacteria on amphibians has mitigated this disease effectively in laboratory trials and one recent field trial. Areas still naïve to Bd provide an opportunity for conservationists to proactively implement probiotic strategies to prevent further amphibian declines. In areas where Bd is endemic, bioaugmentation can facilitate repatriation of susceptible amphibians currently maintained in assurance colonies. Here, we synthesise the current research in amphibian microbial ecology and bioaugmentation to identify characteristics of effective probiotics in relation to their interactions with Bd , their host, other resident microbes and the environment. To target at‐risk species and amphibian communities, we develop sampling strategies and filtering protocols that result in probiotics that inhibit Bd under ecologically relevant conditions and persist on susceptible amphibians. This filtering tool can be used proactively to guide amphibian disease mitigation and can be extended to other taxa threatened by emerging infectious diseases.

Microevolution in time and space: SNP analysis of historical DNA reveals dynamic signatures of selection in A tlantic cod - Nina O. Therkildsen; Jakob Hemmer‐Hansen; Thomas D. Als; Douglas P. Swain; M. Joanne Morgan; Edward A. Trippel; Stephen R. Palumbi; Dorte Meldrup; Einar E. Nielsen (Molecular Ecology, 2013)
Little is known about how quickly natural populations adapt to changes in their environment and how temporal and spatial variation in selection pressures interact to shape patterns of genetic diversity. We here address these issues with a series of genome scans in four overfished populations of Atlantic cod ( G adus morhua ) studied over an 80‐year period. Screening of >1000 gene‐associated single‐nucleotide polymorphisms ( SNP s) identified 77 loci that showed highly elevated levels of differentiation, likely as an effect of directional selection, in either time, space or both. Exploratory analysis suggested that temporal allele frequency shifts at certain loci may correlate with local temperature variation and with life history changes suggested to be fisheries induced. Interestingly, however, largely nonoverlapping sets of loci were temporal outliers in the different populations and outliers from the 1928 to 1960 period showed almost complete stability during later decades. The contrasting microevolutionary trajectories among populations resulted in sequential shifts in spatial outliers, with no locus maintaining elevated spatial differentiation throughout the study period. Simulations of migration coupled with observations of temporally stable spatial structure at neutral loci suggest that population replacement or gene flow alone could not explain all the observed allele frequency variation. Thus, the genetic changes are likely to at least partly be driven by highly dynamic temporally and spatially varying selection. These findings have important implications for our understanding of local adaptation and evolutionary potential in high gene flow organisms and underscore the need to carefully consider all dimensions of biocomplexity for evolutionarily sustainable management.

Fragmentation and thermal risks from climate change interact to affect persistence of native trout in the Colorado River basin - James J. Roberts; Kurt D. Fausch; Douglas P. Peterson; Mevin B. Hooten (Global Change Biology, 2013)
Impending changes in climate will interact with other stressors to threaten aquatic ecosystems and their biota. Native C olorado R iver cutthroat trout ( CRCT ; O ncorhynchus clarkii pleuriticus ) are now relegated to 309 isolated high‐elevation (>1700 m) headwater stream fragments in the Upper C olorado R iver Basin, owing to past nonnative trout invasions and habitat loss. Predicted changes in climate (i.e., temperature and precipitation) and resulting changes in stochastic physical disturbances (i.e., wildfire, debris flow, and channel drying and freezing) could further threaten the remaining CRCT populations. We developed an empirical model to predict stream temperatures at the fragment scale from downscaled climate projections along with geomorphic and landscape variables. We coupled these spatially explicit predictions of stream temperature with a B ayesian Network ( BN ) model that integrates stochastic risks from fragmentation to project persistence of CRCT populations across the upper C olorado R iver basin to 2040 and 2080. Overall, none of the populations are at risk from acute mortality resulting from high temperatures during the warmest summer period. In contrast, only 37% of populations have a ≥90% chance of persistence for 70 years (similar to the typical benchmark for conservation), primarily owing to fragmentation. Populations in short stream fragments CRCT populations. The reason for this paradox is that past nonnative trout invasions and habitat loss have restricted most CRCT populations to high‐elevation stream fragments that are buffered from the potential consequences of warming, but at risk of extirpation from stochastic events. The greatest conservation need is for management to increase fragment lengths to forestall these risks.

Estimates of soil carbon concentration in tropical and temperate forest and woodland from available GIS data on three continents - Brenton Ladd; Shawn W. Laffan; Wulf Amelung; Pablo L. Peri; Lucas C. R. Silva; Pina Gervassi; Stephen P. Bonser; Marcelo Navall; Douglas Sheil (Global Ecology and Biogeography, 2013)
Aim Concern about climate change, with the subsequent emergence of carbon markets and policy initiatives such as REDD (reducing carbon emissions by decreasing deforestation and forest degradation), have focused attention on assessing and monitoring terrestrial carbon reserves. Most effort has focused on above‐ground forest biomass. Soil has received less attention despite containing more carbon than above‐ground terrestrial biomass and the atmosphere combined. Our aim was to explore how well soil carbon concentration could be estimated on three continents from existing climate, topography and vegetation‐cover data. Location P eru, B razil, A rgentina, A ustralia, C hina. Methods Soil carbon concentration and leaf area index ( LAI ) as well as GIS ‐derived climate and topography variables for 65 temperate and 43 tropical, forest and woodland ecosystems, were either directly measured or estimated from freely available global datasets. We then used multiple regressions to determine how well soil carbon concentration could be predicted from LAI , climate and topography at a given site. We compared our measurements with top soil carbon estimates from the F ood and A griculture O rganization of the U nited N ations ( FAO ) harmonized world soil map. Results Our empirical model based on estimates of temperature, water availability and plant productivity provided a good estimate of soil carbon concentrations ( R 2 = 0.79). In contrast, the values of topsoil carbon concentrations from the FAO harmonized world soil map correlated poorly with the measured values of soil carbon concentration ( R 2 = 0.0011). Main conclusions The lack of correlation between the measured values of soil carbon and the values from the FAO harmonized world soil map indicate that substantial improvements in the production of soil carbon maps are needed and possible. Our results demonstrate that the inclusion of freely available GIS data offers improved estimates of soil carbon and will allow the creation of more accurate soil carbon maps.

Contributions of neutrophils to resolution of mucosal inflammation - Sean P. Colgan; Stefan F. Ehrentraut; Louise E. Glover; Douglas J. Kominsky; Eric L. Campbell (Immunologic Research, 2013)

An assessment of karyotype restructuring in the neoallotetraploid Tragopogon miscellus (Asteraceae) - Michael Chester; Malorie J. Lipman; Joseph P. Gallagher; Pamela S. Soltis; Douglas E. Soltis (Chromosome Research, 2013)

Structural and ecophysiological adaptations to forest gaps - Guilherme R. Rabelo; Ângela P. Vitória; Marcos V. A. da Silva; Ricardo A. Cruz; Elis I. B. Pinho; Douglas R. Ribeiro; Anita V. Freitas; Maura Da Cunha (Trees, 2013)

Contrasting the effects of climatic, nutrient, and oxygen dynamics on subfossil chironomid assemblages: a paleolimnological experiment from eutrophic High Arctic ponds - Emily M. Stewart; Neal Michelutti; Jules M. Blais; Mark L. Mallory; Marianne S. V. Douglas; John P. Smol (Journal of Paleolimnology, 2013)

Regional groundwater flow in an area mapped as continuous permafrost, NE Alaska (USA) - Douglas L. Kane; Kenji Yoshikawa; James P. McNamara (Hydrogeology Journal, 2013)

Gastric cancer incidence estimation in a resource-limited nation: use of endoscopy registry methodology - Ricardo L. Dominguez; Seth D. Crockett; Jennifer L. Lund; Lia P. Suazo; Paris Heidt; Christopher Martin; Douglas R. Morgan (Cancer Causes & Control, 2013)

5-Azacytidine combined with 2,4-D improves somatic embryogenesis of Acca sellowiana (O. Berg) Burret by means of changes in global DNA methylation levels - Hugo P. F. Fraga; Leila N. Vieira; Clarissa A. Caprestano; Douglas A. Steinmacher; Gustavo A. Micke; Daniel A. Spudeit; Rosete Pescador; Miguel P. Guerra (Plant Cell Reports, 2012)

Cell adhesion molecule 1 (CADM1) is ubiquitously present in the endothelium and smooth muscle cells of the human macro- and micro-vasculature - Kanayo Tatsumi; Douglas J. Taatjes; Marilyn P. Wadsworth; Beth A. Bouchard; Edwin G. Bovill (Histochemistry and Cell Biology, 2012)

Application of Electrochemical Degradation of Wastewater Composed of Mixtures of Phenol–Formaldehyde - Ana Luiza T. Fornazari; Geoffroy R. P. Malpass; Douglas W. Miwa; Artur J. Motheo (Water, Air, & Soil Pollution, 2012)

An intra-specific consensus genetic map of pigeonpea [Cajanus cajan (L.) Millspaugh] derived from six mapping populations - Abhishek Bohra; Rachit K. Saxena; B. N. Gnanesh; Kulbhushan Saxena; M. Byregowda; Abhishek Rathore; P. B. KaviKishor; Douglas R. Cook; Rajeev K. Varshney (Theoretical and Applied Genetics, 2012)

Persistent activation of omentum influences the pattern of muscular lesion in the mdx diaphragm - Douglas Florindo Pinheiro; Rafael F. da Silva; Lian P. Carvalho; Eustaquio L. Paiva-Oliveira; Ricardo S. Pereira; Paulo Emilio C. Leite; Maria de Fátima Pinho; Thereza Quirico-Santos; Jussara Lagrota-Candido (Cell and Tissue Research, 2012)

Nprl3 is required for normal development of the cardiovascular system - Monika S. Kowalczyk; Jim R. Hughes; Christian Babbs; Luis Sanchez-Pulido; Dorota Szumska; Jacqueline A. Sharpe; Jacqueline A. Sloane-Stanley; Gillian M. Morriss-Kay; Leslie B. Smoot; Amy E. Roberts; Hugh Watkins; Shoumo Bhattacharya; et al. (Mammalian Genome, 2012)

Desorption and Transformation of Nitroaromatic (TNT) and Nitramine (RDX and HMX) Explosive Residues on Detonated Pure Mineral Phases - Thomas A. Douglas; Marianne E. Walsh; Charles A. Weiss; Christian J. McGrath; Thomas P. Trainor (Water, Air, & Soil Pollution, 2012)

A longitudinal systems biology analysis of lactulose withdrawal in hepatic encephalopathy - Jasmohan S. Bajaj; Patrick M. Gillevet; Neeral R. Patel; Vishwadeep Ahluwalia; Jason M Ridlon; Birgit Kettenmann; Christine M. Schubert; Masoumeh Sikaroodi; Douglas M. Heuman; Mary M. E. Crossey; Debulon E. Bell; Philip B. Hylemon; et al. (Metabolic Brain Disease, 2012)

3D organization and function of the cell: Golgi budding and vesicle biogenesis to docking at the porosome complex - Sunxi Wang; Jin-Sook Lee; Nicole Bishop; Aleksandar Jeremic; Won Jin Cho; Xuequn Chen; Guangzhao Mao; Douglas J. Taatjes; Bhanu P. Jena (Histochemistry and Cell Biology, 2012)

Unexpected toxicity decrease during photoelectrochemical degradation of atrazine with NaCl - Geoffroy R. P. Malpass; Douglas W. Miwa; Ricardo L. Santos; Eny M. Vieira; Artur J. Motheo (Environmental Chemistry Letters, 2012)

Effects of herbivory, nutrients, and reef protection on algal proliferation and coral growth on a tropical reef - Douglas B. Rasher; Sebastian Engel; Victor Bonito; Gareth J. Fraser; Joseph P. Montoya; Mark E. Hay (Oecologia, 2012)

Effects of an experimental environmental flow release on the diet of fish in a regulated coastal Australian river - Robert J. Rolls; Andrew J. Boulton; Ivor O. Growns; Sally E. Maxwell; Darren S. Ryder; Douglas P. Westhorpe (Hydrobiologia, 2012)

Well-informed foraging: damage-released chemical cues of injured prey signal quality and size to predators - Oona M. Lonnstedt; Mark I. McCormick; Douglas P. Chivers (Oecologia, 2012)

Can rare positive interactions become common when large carnivores consume livestock? - Vijayan Sundararaj; Brian E. McLaren; Douglas W. Morris; S. P. Goyal (Ecology, 2012)
Livestock populations in protected areas are viewed negatively because of their interaction with native ungulates through direct competition for food resources. However, livestock and native prey can also interact indirectly through their shared predator. Indirect interactions between two prey species occur when one prey modifies either the functional or numerical responses of a shared predator. This interaction is often manifested as negative effects (apparent competition) on one or both prey species through increased predation risk. But indirect interactions can also yield positive effects on a focal prey if the shared predator modifies its functional response toward increased consumption of an abundant and higher‐quality alternative prey. Such a phenomenon between two prey species is underappreciated and overlooked in nature. Positive indirect effects can be expected to occur in livestock‐dominated wildlife reserves containing large carnivores. We searched for such positive effects in Acacia–Zizhypus forests of India's Gir sanctuary where livestock ( Bubalus bubalis and Bos indicus ) and a coexisting native prey (chital deer, Axis axis ) are consumed by Asiatic lions ( Panthera leo persica ). Chital vigilance was higher in areas with low livestock density than in areas with high livestock density. This positive indirect effect occurred because lion predation rates on livestock were twice as great where livestock were abundant than where livestock density was low. Positive indirect interactions mediated by shared predators may be more common than generally thought with rather major consequences for ecological understanding and conservation. We encourage further studies to understand outcomes of indirect interactions on long‐term predator–prey dynamics in livestock‐dominated protected areas.

Coccidia of New World passerine birds (Aves: Passeriformes): a review of Eimeria Schneider, 1875 and Isospora Schneider, 1881 (Apicomplexa: Eimeriidae) - Bruno P. Berto; Walter Flausino; Douglas McIntosh; Walter L. Teixeira-Filho; Carlos W. G. Lopes (Systematic Parasitology, 2011)

A high-resolution analyser for the measurement of ammonium in oligotrophic seawater - Samer K. Abi Kaed Bey; Douglas P. Connelly; François-Eric Legiret; Andy J. K. Harris; Matthew C. Mowlem (Ocean Dynamics, 2011)

Genetic structure and connectivity among lake populations of threatened Paratherina sailfin silversides from Sulawesi, Indonesia - Ryan P. Walter; J. Derek Hogan; G. Douglas Haffner; Daniel D. Heath (Conservation Genetics, 2011)

A Quantitative Real-Time PCR Approach for the Detection and Characterization of Endothelial Cells in Whole Blood - Sudhir P. Deosarkar; Pooja Bhatt; Christopher J. Lewis; Douglas J. Goetz (Annals of Biomedical Engineering, 2011)

Physiological characterization and light response of the CO2-concentrating mechanism in the filamentous cyanobacterium Leptolyngbya sp. CPCC 696 - Elvin D. de Araujo; Jason Patel; Charlotte de Araujo; Susan P. Rogers; Steven M. Short; Douglas A. Campbell; George S. Espie (Photosynthesis Research, 2011)

DNA Aptamer Beacon Assay for C-Telopeptide and Handheld Fluorometer to Monitor Bone Resorption - John Gordon Bruno; Maria P. Carrillo; Taylor Phillips; Douglas Hanson; Jonathan A. Bohmann (Journal of Fluorescence, 2011)

Intrageneric variation in antipredator responses of coral reef fishes affected by ocean acidification: implications for climate change projections on marine communities - MAUD C. O. FERRARI; DANIELLE L. DIXSON; PHILIP L. MUNDAY; MARK I. McCORMICK; MARK G. MEEKAN; ANDREW SIH; DOUGLAS P. CHIVERS (Global Change Biology, 2011)
Our planet is experiencing an increase in the concentration of atmospheric carbon dioxide (CO 2 ) unprecedented in the past 800 000 years. About 30% of excess atmospheric CO 2 is absorbed by the oceans, thus increasing the concentration of carbonic acid and reducing the ocean's pH. Species able to survive the physiological stress imposed by ocean acidification may still suffer strong indirect negative consequences. Comparing the tolerance of different species to dissolved CO 2 is a necessary first step towards predicting the ecological impacts of rising CO 2 levels on marine communities. While it is intuitive that not all aquatic species will be affected the same way by CO 2 , one could predict that closely related species, sharing similar life histories and ecology, may show similar tolerance levels to CO 2 . Our ability to create functional groups of species according to their CO 2 tolerance may be crucial in our ability to predict community change in the future. Here, we tested the effects of CO 2 exposure on the antipredator responses of four damselfish species ( Pomacentrus chrysurus, Pomacentrus moluccensis, Pomacentrus amboinensis and Pomacentrus nagasakiensis ). Although being sympatric and sharing the same ecology and life history, the four congeneric species showed striking and unexpected variation in CO 2 tolerance, with CO 2 ‐induced loss of response to predation risk ranging from 30% to 95%. Using P. chrysurus as a model species, we further tested if these behavioural differences translated into differential ability to survive predators under natural conditions. Our results indicate that P. chrysurus larvae raised under CO 2 levels predicted by 2070 and 2100 showed decreased antipredator responses to risk, leading to a five‐ to sevenfold increase in predation‐related mortality in the first few hours of settlement. Examining ocean acidification, along with other environmental variables, will be a critical step in further evaluating ecological responses to predicted climatic change.

A model for inferring dissolved organic carbon (DOC) in lakewater from visible-near-infrared spectroscopy (VNIRS) measures in lake sediment - Alexandra Rouillard; Peter Rosén; Marianne S. V. Douglas; Reinhard Pienitz; John P. Smol (Journal of Paleolimnology, 2011)

Shallow and deep lunge feeding of humpback whales in fjords of the West Antarctic Peninsula - Colin Ware; Ari S. Friedlaender; Douglas P. Nowacek (Marine Mammal Science, 2011)
Humpback whales ( Megaptera novaeangliae ) belong to the class of marine mammals known as rorquals that feed through extraordinarily energetic lunges during which they engulf large volumes of water equal to as much as 70% of their body mass. To understand the kinematics of humpback lunge feeding, we attached high‐resolution digital recording tags incorporating accelerometers, magnetometers, pressure and sound recording to whales feeding on euphausiids in fjords of the West Antarctic Peninsula. Instances of near vertical lunges gave us the unique opportunity to use the signal from the accelerometer to obtain a fine scale record of the body accelerations involved in lunging. We found that lunges contain extreme accelerations reaching 2.5 m/s 2 in certain instances, which are then followed by decelerations. When animals are intensively feeding the inter‐lunge interval is similar for both deep and shallow lunges suggesting a biomechanical constraint on lunges. However, the number of lunges per dive varies from one for shallow feeding (

Chironomid assemblages from seabird-affected High Arctic ponds - Neal Michelutti; Mark L. Mallory; Jules M. Blais; Marianne S. V. Douglas; John P. Smol (Polar Biology, 2011)

Growth rate and retention of learned predator cues by juvenile rainbow trout: faster-growing fish forget sooner - Grant E. Brown; Maud C. O. Ferrari; Patrick H. Malka; Marie-Anne Oligny; Matthew Romano; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2011)

Climate change links fate of glaciers and an endemic alpine invertebrate - Clint C. Muhlfeld; J. Joseph Giersch; F. Richard Hauer; Gregory T. Pederson; Gordon Luikart; Douglas P. Peterson; Christopher C. Downs; Daniel B. Fagre (Climatic Change, 2011)

A microcosm study of the common night crawler earthworm (Lumbricus terrestris) and physical, chemical and biological properties of a designed urban soil - Bryant C. Scharenbroch; Douglas P. Johnston (Urban Ecosystems, 2011)

Cultural eutrophication, anoxia, and ecosystem recovery in Meretta Lake, High Arctic Canada - Dermot Antoniades; Neal Michelutti; Roberto Quinlan; Jules M. Blais; Sylvia Bonilla; Marianne S. V. Douglas; Reinhard Pienitz; John P. Smol; Warwick F. Vincent (Limnology and Oceanography, 2011)
We studied the effects of four decades of cultural eutrophication on Meretta Lake, in the Canadian High Arctic, through a multiproxy analysis of its sediments, including sedimentary pigments, metal concentrations, stable isotope ratios, chironomids, and diatoms. While Meretta Lake's biota clearly responded to nutrient inputs, the manner in which the changes differed from those expected in temperate lakes underlined the profound effects in Arctic lakes of extended ice and snow cover on light penetration, mixing, and interactions with the atmosphere. Hypolimnetic anoxia developed rapidly in Meretta Lake in response to sewage enrichment and was accompanied by the appearance of photosynthetic sulfur bacteria. Benthic communities responded rapidly to sewage inputs, but phytoplankton biomass did not increase until eutrophication was accompanied by climate warming, further reinforcing the importance of ice cover in controlling biotic processes in high Arctic lakes. With climate‐mediated ice cover reductions in Meretta Lake, the response to eutrophication began to more closely resemble temperate processes. Recent trajectories indicate that slightly more than a decade after the cessation of sewage inputs, Meretta Lake is recovering toward pre‐enrichment conditions.

Methods for Conducting Bioassays Using Embryos and Larvae of Pacific Herring, Clupea pallasi - Paul A. Dinnel; Douglas P. Middaugh; Nathan T. Schwarck; Heather M. Farren; Richard K. Haley; Richard A. Hoover; James Elphick; Karen Tobiason; Randall R. Marshall (Archives of Environmental Contamination and Toxicology, 2011)

Regressive progression, progressive regression or neither? Phylogeny and evolution of the Percopsiformes (Teleostei, Paracanthopterygii) - Casey B. Dillman; Dean E. Bergstrom; Douglas B. Noltie; Timothy P. Holtsford; Richard L. Mayden (Zoologica Scripta, 2011)
Dillman, C.B., Bergstrom, D.E., Noltie, D.B., Holtsford, T.P. & Mayden, R.L. (2010). Regressive progression, progressive regression or neither? Phylogeny and evolution of the Percopsiformes (Teleostei, Paracanthopterygii). — Zoologica Scripta , 40 , 45–60. Cave animals have fascinated scientists for centuries, and clades consisting primarily of cave‐adapted species are even more intriguing. The percopsiforms are an enigmatic group of fishes comprised of nine species in seven genera, with four species in three genera exhibiting characteristic troglomorphic features, such as a lack of pigmentation and eyes. Nucleotide characters presented here provide the first test of monophyly for both the Percopsiformes and Amblyopsidae with this character type and taxonomic completeness. Characters of ND2 support a monophyletic Percopsiformes and Amblyopsidae and further document phylogeographic subdivision in two stygobitic genera, Amblyopsis and Typhlichthys , in Amblyopsidae. Age estimates from time‐calibrated branch lengths utilizing two independent intra‐lineage fossils indicate that the ancestor to amblyopsids is Eocene in age, and that phylogeographic subdivision in both Amblyopsis and Typhlichthys occurred primarily in the Miocene. Interestingly, ancestral character state reconstruction for the amblyopsids strongly supports the re‐evolution of eyes and body pigment. While certainly unconventional, but supported with this character set, the hypothesis provides continued challenge to Dollo’s Law.

Acute effects of removing large fish from a near-pristine coral reef - Douglas J. McCauley; Fiorenza Micheli; Hillary S. Young; Derek P. Tittensor; Daniel R. Brumbaugh; Elizabeth M. P. Madin; Katherine E. Holmes; Jennifer E. Smith; Heike K. Lotze; Paul A. DeSalles; Suzanne N. Arnold; Boris Worm (Marine Biology, 2010)

Diatom-inferred Holocene climatic and environmental changes in an unusually subsaline high Arctic nunatak pond on Ellesmere Island (Nunavut, Canada) - C. A. Paul; M. S. V. Douglas; J. P. Smol (Journal of Paleolimnology, 2010)

Development of a rotorcraft dust-emission parameterization using a CFD model - Jerrold D. McAlpine; Darko R. Koracin; Douglas P. Boyle; John A. Gillies; Eric V. McDonald (Environmental Fluid Mechanics, 2010)

Hydrolytic Enzyme Production is Associated with Candida Albicans Biofilm Formation from Patients with Type 1 Diabetes - Ranjith Rajendran; Douglas P. Robertson; Penny J. Hodge; David F. Lappin; Gordon Ramage (Mycopathologia, 2010)

Brevetoxins in sharks and rays (Chondrichthyes, Elasmobranchii) from Florida coastal waters - Leanne J. Flewelling; Douglas H. Adams; Jerome P. Naar; Karen E. Atwood; April A. Granholm; Sheila N. O’Dea; Jan H. Landsberg (Marine Biology, 2010)

Limitation of lowland riverine bacterioplankton by dissolved organic carbon and inorganic nutrients - Douglas P. Westhorpe; Simon M. Mitrovic; David Ryan; Tsuyoshi Kobayashi (Hydrobiologia, 2010)

Seasonal home ranges and fidelity to breeding sites among ringed seals - Brendan P. Kelly; Oriana H. Badajos; Mervi Kunnasranta; John R. Moran; Micaela Martinez-Bakker; Douglas Wartzok; Peter Boveng (Polar Biology, 2010)

Nutrient enrichment in the High Arctic associated with Thule Inuit whalers: a paleolimnological investigation from Ellesmere Island (Nunavut, Canada) - Kristopher R. Hadley; Marianne S. V. Douglas; Jules M. Blais; John P. Smol (Hydrobiologia, 2010)

Road and Rail Side Vegetation Management Implications of Habitat Use by Moose Relative to Brush Cutting Season - Roy V. Rea; Kenneth N. Child; David P. Spata; Douglas MacDonald (Environmental Management, 2010)

The Biotechnology Roadmap for Sugarcane Improvement - Carlos T. Hotta; Carolina G. Lembke; Douglas S. Domingues; Edgar A. Ochoa; Guilherme M. Q. Cruz; Danila M. Melotto-Passarin; Thiago G. Marconi; Melissa O. Santos; Marcelo Mollinari; Gabriel R. A. Margarido; Augusto César Crivellari; Wanderley D. dos Santos; et al. (Tropical Plant Biology, 2010)

Ecological influences of Thule Inuit whalers on high Arctic pond ecosystems: a comparative paleolimnological study from Bathurst Island (Nunavut, Canada) - Kristopher R. Hadley; Marianne S. V. Douglas; Robert McGhee; Jules M. Blais; John P. Smol (Journal of Paleolimnology, 2010)

Dye-tracing studies in southwestern Missouri, USA: indication of stratigraphic flow control in the Burlington Limestone - Douglas Gouzie; Rebecca P. Dodd; David M. White (Hydrogeology Journal, 2010)

Geologic control of natural marine hydrocarbon seep emissions, Coal Oil Point seep field, California - Ira Leifer; Marc J. Kamerling; Bruce P. Luyendyk; Douglas S. Wilson (Geo-Marine Letters, 2010)

Integration of novel SSR and gene-based SNP marker loci in the chickpea genetic map and establishment of new anchor points with Medicago truncatula genome - Spurthi N. Nayak; Hongyan Zhu; Nicy Varghese; Subhojit Datta; Hong-Kyu Choi; Ralf Horres; Ruth Jüngling; Jagbir Singh; P. B. Kavi Kishor; S. Sivaramakrishnan; Dave A. Hoisington; Günter Kahl; et al. (Theoretical and Applied Genetics, 2010)

The Temporal Morphology of Infrasound Propagation - Douglas P. Drob; Milton Garcés; Michael Hedlin; Nicolas Brachet (Pure and Applied Geophysics, 2010)

Effect of opioid administration on cardiorespiratory and muscle oxygenation during lifting in chronic back pain patients - Yagesh Bhambhani; Douglas P. Gross; Mark Haykowsky; Saifudin Rashiq (European Journal of Applied Physiology, 2010)

A hybrid model for intensively managed Douglas-fir plantations in the Pacific Northwest, USA - Aaron R. Weiskittel; Douglas A. Maguire; Robert A. Monserud; Gregory P. Johnson (European Journal of Forest Research, 2010)

Nitrate and fecal coliform concentration differences at the soil/bedrock interface in Appalachian silvopasture, pasture, and forest - Douglas G. Boyer; James P. S. Neel (Agroforestry Systems, 2010)

Effect of Early Introduction of Microencapsulated Diet to Larval Atlantic Halibut, Hippoglossus hippoglossus L. Assessed by Microarray Analysis - H. M. Murray; S. P. Lall; R. Rajaselvam; L. A. Boutilier; R. M. Flight; B. Blanchard; S. Colombo; V. Mohindra; M. Yúfera; S. E. Douglas (Marine Biotechnology, 2010)

Initiation of embryogenic cell suspensions of taro (Colocasia esculenta var. esculenta) and plant regeneration - Pradeep C. Deo; Mary Taylor; Robert M. Harding; Anand P. Tyagi; Douglas K. Becker (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

The ghost of predation future: threat-sensitive and temporal assessment of risk by embryonic woodfrogs - Maud C. O. Ferrari; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2010)

Responses of Estuarine Bacterioplankton, Phytoplankton and Zooplankton to Dissolved Organic Carbon (DOC) and Inorganic Nutrient Additions - James N. Hitchcock; Simon M. Mitrovic; Tsuyoshi Kobayashi; Douglas P. Westhorpe (Estuaries and Coasts, 2010)

Multiple sightings of large groups of Arnoux's beaked whales (Berardius arnouxii) in the Gerlache Strait, Antarctica - Ari S. Friedlaender; Douglas P. Nowacek; David W. Johnston; Andrew J. Read; Reny B. Tyson; Lindsey Peavey; Eletta M. S. Revelli (Marine Mammal Science, 2009)

The evolution of intermediate castration virulence and ant coexistence in a spatially structured environment - András Szilágyi; István Scheuring; David P. Edwards; Jerome Orivel; Douglas W. Yu (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1306–1316 Abstract Theory suggests that spatial structuring should select for intermediate levels of virulence in parasites, but empirical tests are rare and have never been conducted with castration (sterilizing) parasites. To test this theory in a natural landscape, we construct a spatially explicit model of the symbiosis between the ant‐plant Cordia nodosa and its two, protecting ant symbionts, Allomerus and Azteca . Allomerus is also a castration parasite, preventing fruiting to increase colony fecundity. Limiting the dispersal of Allomerus and host plant selects for intermediate castration virulence. Increasing the frequency of the mutualist, Azteca , selects for higher castration virulence in Allomerus , because seeds from Azteca ‐inhabited plants are a public good that Allomerus exploits. These results are consistent with field observations and, to our knowledge, provide the first empirical evidence supporting the hypothesis that spatial structure can reduce castration virulence and the first such evidence in a natural landscape for either mortality or castration virulence.

Somatic embryogenesis, organogenesis and plant regeneration in taro (Colocasia esculenta var. esculenta) - Pradeep C. Deo; Robert M. Harding; Mary Taylor; Anand P. Tyagi; Douglas K. Becker (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Subacute exposure to N-ethyl perfluorooctanesulfonamidoethanol results in the formation of perfluorooctanesulfonate and alters superoxide dismutase activity in female rats - Wei Xie; Qian Wu; Izabela Kania-Korwel; Job C. Tharappel; Sanjay Telu; Mitchell C. Coleman; Howard P. Glauert; Kurunthachalam Kannan; S. V. S. Mariappan; Douglas R. Spitz; Jamie Weydert; Hans-Joachim Lehmler (Archives of Toxicology, 2009)

The effect of spatial–temporal audiovisual disparities on saccades in a complex scene - Marc M. Van Wanrooij; Andrew H. Bell; Douglas P. Munoz; A. John Van Opstal (Experimental Brain Research, 2009)

SDHB-associated renal oncocytoma suggests a broadening of the renal phenotype in hereditary paragangliomatosis - Alex Henderson; F. Douglas; P. Perros; C. Morgan; E. R. Maher (Familial Cancer, 2009)

Invasion versus Isolation: Trade‐Offs in Managing Native Salmonids with Barriers to Upstream Movement - KURT D. FAUSCH; BRUCE E. RIEMAN; JASON B. DUNHAM; MICHAEL K. YOUNG; DOUGLAS P. PETERSON (Conservation Biology, 2009)
Conservation biologists often face the trade‐off that increasing connectivity in fragmented landscapes to reduce extinction risk of native species can foster invasion by non‐native species that enter via the corridors created, which can then increase extinction risk. This dilemma is acute for stream fishes, especially native salmonids, because their populations are frequently relegated to fragments of headwater habitat threatened by invasion from downstream by 3 cosmopolitan non‐native salmonids. Managers often block these upstream invasions with movement barriers, but isolation of native salmonids in small headwater streams can increase the threat of local extinction. We propose a conceptual framework to address this worldwide problem that focuses on 4 main questions. First, are populations of conservation value present (considering evolutionary legacies, ecological functions, and socioeconomic benefits as distinct values)? Second, are populations vulnerable to invasion and displacement by non‐native salmonids? Third, would these populations be threatened with local extinction if isolated with barriers? And, fourth, how should management be prioritized among multiple populations? We also developed a conceptual model of the joint trade‐off of invasion and isolation threats that considers the opportunities for managers to make strategic decisions. We illustrated use of this framework in an analysis of the invasion‐isolation trade‐off for native cutthroat trout (Oncorhynchus clarkii) in 2 contrasting basins in western North America where invasion and isolation are either present and strong or farther away and apparently weak. These cases demonstrate that decisions to install or remove barriers to conserve native salmonids are often complex and depend on conservation values, environmental context (which influences the threat of invasion and isolation), and additional socioeconomic factors. Explicit analysis with tools such as those we propose can help managers make sound decisions in such complex circumstances.

Threat-sensitive generalization of predator recognition by larval amphibians - Maud C. O. Ferrari; Grant E. Brown; François Messier; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2009)

The effect of genetic and environmental variation on metabolic gene expression - CINDA P. SCOTT; DEAN A. WILLIAMS; DOUGLAS L. CRAWFORD (Molecular Ecology, 2009)
What is the relationship between genetic or environmental variation and the variation in messenger RNA (mRNA) expression? To address this, microarrays were used to examine the effect of genetic and environmental variation on cardiac mRNA expression for metabolic genes in three groups of Fundulus heteroclitus : (i) individuals sampled in the field (field), ( ii) field individuals acclimated for 6 months to laboratory conditions (acclimated), or (iii) individuals bred for 10 successive generations in a laboratory environment (G10). The G10 individuals have significantly less genetic variation than individuals obtained in the field and had a significantly lower variation in mRNA expression across all genes in comparison to the other two groups ( P = 0.001). When examining the gene specific variation, 22 genes had variation in expression that was significantly different among groups with lower variation in G10 individuals than in acclimated individuals. Additionally, there were fewer genes with significant differences in expression among G10 individuals vs. either acclimated or field individuals: 66 genes have statistically different levels of expression vs. 107 or 97 for acclimated or field groups. Based on the permutation of the data, these differences in the number of genes with significant differences among individuals within a group are unlikely to occur by chance ( P 0.01). Surprisingly, variation in mRNA expression in field individuals is lower than in acclimated individuals. Relative to the variation among individual within a group, few genes have significant differences in expression among groups (seven, 2.3%) and none of these are different between acclimated and field individuals. The results support the concept that genetic variation affects variation in mRNA expression and also suggests that temporal environmental variation associated with estuarine environments does not increase the variation among individuals or add to the differences among groups.

Trophic linkages between periphyton and grazing macroinvertebrates in rivers with different levels of catchment development - Bruce C. Chessman; Douglas P. Westhorpe; Simon M. Mitrovic; Lorraine Hardwick (Hydrobiologia, 2009)

Cigarette smoking and the risk of Barrett’s esophagus - Ai Kubo; T. R. Levin; Gladys Block; Gregory Rumore; Charles P. Quesenberry; Patricia Buffler; Douglas A. Corley (Cancer Causes & Control, 2009)

Impacts of seabird-derived nutrients on water quality and diatom assemblages from Cape Vera, Devon Island, Canadian High Arctic - Bronwyn E. Keatley; Marianne S. V. Douglas; Jules M. Blais; Mark L. Mallory; John P. Smol (Hydrobiologia, 2009)

Translational Machinery of Senegalese Sole (Solea senegalensis Kaup) and Atlantic Halibut (Hippoglossus hippoglossus L.): Comparative Sequence Analysis of the Complete Set of 60S Ribosomal Proteins and their Expression - Makoto P. Matsuoka; Carlos Infante; Michael Reith; Jose Pedro Cañavate; Susan E. Douglas; Manuel Manchado (Marine Biotechnology, 2008)

Apparent autosomal dominant keratoconus in a large Australian pedigree accounted for by digenic inheritance of two novel loci - Kathryn P. Burdon; Douglas J. Coster; Jac C. Charlesworth; Richard A. Mills; Kate J. Laurie; Cecilia Giunta; Alex W. Hewitt; Paul Latimer; Jamie E. Craig (Human Genetics, 2008)

Sensory complementation and the acquisition of predator recognition by salmonid fishes - Maud C. O. Ferrari; Meaghan A. Vavrek; Chris K. Elvidge; Bryan Fridman; Douglas P. Chivers; Grant E. Brown (Behavioral Ecology and Sociobiology, 2008)

Tolerating castration by hiding flowers in plain sight - David P. Edwards; Douglas W. Yu (Behavioral Ecology and Sociobiology, 2008)

A test of the possible influence of seabird activity on the 210Pb flux in high Arctic ponds at Cape Vera, Devon Island, Nunavut: implications for radiochronology - N. Michelutti; J. M. Blais; H. Liu; B. E. Keatley; M. S. V. Douglas; M. L. Mallory; J. P. Smol (Journal of Paleolimnology, 2008)

Effects of non-native plants on the native insect community of Delaware - Marion E. Zuefle; William P. Brown; Douglas W. Tallamy (Biological Invasions, 2008)

Competitive FRET-Aptamer-Based Detection of Methylphosphonic Acid, a Common Nerve Agent Metabolite - John G. Bruno; Maria P. Carrillo; Taylor Phillips; Neal K. Vail; Douglas Hanson (Journal of Fluorescence, 2008)

Effective population size dynamics reveal impacts of historic climatic events and recent anthropogenic pressure in African elephants - J. B. A. OKELLO; G. WITTEMYER; H. B. RASMUSSEN; P. ARCTANDER; S. NYAKAANA; I. DOUGLAS‐HAMILTON; H. R. SIEGISMUND (Molecular Ecology, 2008)
Two hundred years of elephant hunting for ivory, peaking in 1970–1980s, caused local extirpations and massive population declines across Africa. The resulting genetic impacts on surviving populations have not been studied, despite the importance of understanding the evolutionary repercussions of such human‐mediated events on this keystone species. Using Bayesian coalescent‐based genetic methods to evaluate time‐specific changes in effective population size, we analysed genetic variation in 20 highly polymorphic microsatellite loci from 400 elephants inhabiting the greater Samburu‐Laikipia region of northern Kenya. This area experienced a decline of between 80% and 90% in the last few decades when ivory harvesting was rampant. The most significant change in effective population size, however, occurred approximately 2500 years ago during a mid–Holocene period of climatic drying in tropical Africa. Contrary to expectations, detailed analyses of four contemporary age‐based cohorts showed that the peak poaching epidemic in the 1970s caused detectable temporary genetic impacts, with genetic diversity rebounding as juveniles surviving the poaching era became reproductively mature. This study demonstrates the importance of climatic history in shaping the distribution and genetic history of a keystone species and highlights the utility of coalescent‐based demographic approaches in unravelling ancestral demographic events despite a lack of ancient samples. Unique insights into the genetic signature of mid‐Holocene climatic change in Africa and effects of recent poaching pressure on elephants are discussed.

Molecular mapping of quantitative trait loci for yield and yield components in spring wheat (Triticum aestivum L.) - Janice L. Cuthbert; Daryl J. Somers; Anita L. Brûlé-Babel; P. Douglas Brown; Gary H. Crow (Theoretical and Applied Genetics, 2008)

Removal from the Membrane Affects the Interaction of Rat Osseous Plate Ecto-Nucleosidetriphosphate Diphosphohydrolase-1 with Substrates and Ions - Daniela P. Garçon; Douglas C. Masui; Rosa P. M. Furriel; Francisco A. Leone (The Journal of Membrane Biology, 2008)

Imaging aspects of cardiovascular disease at the cell and molecular level - Douglas J. Taatjes; Marilyn P. Wadsworth; Anthony S. Quinn; Jacob H. Rand; Edwin G. Bovill; Burton E. Sobel (Histochemistry and Cell Biology, 2008)

Adolescent sleep and working memory performance - M GRADISAR; G TERRILL; A JOHNSTON; P DOUGLAS (Sleep and Biological Rhythms, 2008)

Recent environmental changes on Banks Island (N.W.T., Canadian Arctic) quantified using fossil diatom assemblages - Darlene S. S. Lim; John P. Smol; Marianne S. V. Douglas (Journal of Paleolimnology, 2008)

Predator-induced changes in morphology of a prey fish: the effects of food level and temporal frequency of predation risk - Douglas P. Chivers; Xiaoxia Zhao; Grant E. Brown; Tracy A. Marchant; Maud C. O. Ferrari (Evolutionary Ecology, 2008)

Use of chemical tracers to assess diet and persistent organic pollutants in Antarctic Type C killer whales - Margaret M. Krahn; Robert L. Pitman; Douglas G. Burrows; David P. Herman; Ronald W. Pearce (Marine Mammal Science, 2008)
Measuring chemical tracers in tissues of marine predators provides insight into the prey consumed and the predator's contaminant exposure. In this study, samples from Type C killer whales ( Orcinus orca ) biopsied in Antarctica were analyzed for chemical tracers ( i.e. , stable isotopes of carbon and nitrogen, fatty acids, and persistent organic pollutants [POPs]). Profiles of these individual tracers were very different from those of killer whale populations that have been studied in the eastern North and eastern Tropical Pacific. For example, δ 13 C and δ 15 N stable isotope values and most POP concentrations were significantly lower in the Antarctic population. In addition, multivariate statistical analyses of both fatty acid and POP profiles found distinctly different patterns for Antarctic Type C whales compared to those from whales in the other populations. Similar assays were conducted on four species of Antarctic marine fish considered potential prey for Type C killer whales. Results were consistent with a diet of fish for Type C whales, but other species ( e.g. , low trophic‐level marine mammals or penguins) could not be eliminated as supplemental prey.

Threat-sensitive learning of predators by larval mosquitoes Culex restuans - Maud C. O. Ferrari; François Messier; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2008)

Saccade-related remapping of target representations between topographic maps: a neural network study - Gerald P. Keith; J. Douglas Crawford (Journal of Computational Neuroscience, 2008)

Relative Wulst volume is correlated with orbit orientation and binocular visual field in birds - Andrew N. Iwaniuk; Christopher P. Heesy; Margaret I. Hall; Douglas R. W. Wylie (Journal of Comparative Physiology A, 2008)

Influence of Plasma Cholesterol and Triglyceride Concentrations and Eritoran (E5564) Micelle Size on its Plasma Pharmacokinetics and Ex Vivo Activity Following Single Intravenous Bolus Dose Into Healthy Female Rabbits - Kishor M. Wasan; Verica Risovic; Olena Sivak; Stephen D. Lee; Douglas X. Mason; Gregory R. Chiklis; Jim McShane; Melvyn Lynn; Nancy Wong; Daniel P. Rossignol (Pharmaceutical Research, 2008)

The genealogy and genetic viability of reintroduced Yellowstone grey wolves - BRIDGETT M. VONHOLDT; DANIEL R. STAHLER; DOUGLAS W. SMITH; DENT A. EARL; JOHN P. POLLINGER; ROBERT K. WAYNE (Molecular Ecology, 2008)
The recovery of the grey wolf in Yellowstone National Park is an outstanding example of a successful reintroduction. A general question concerning reintroduction is the degree to which genetic variation has been preserved and the specific behavioural mechanisms that enhance the preservation of genetic diversity and reduce inbreeding. We have analysed 200 Yellowstone wolves, including all 31 founders, for variation in 26 microsatellite loci over the 10‐year reintroduction period (1995–2004). The population maintained high levels of variation (1995 H 0 = 0.69; 2004 H 0 = 0.73) with low levels of inbreeding (1995 F IS = –0.063; 2004 F IS = –0.051) and throughout, the population expanded rapidly ( N 1995 = 21; N 2004 = 169). Pedigree‐based effective population size ratios did not vary appreciably over the duration of population expansion (1995 N e / N g = 0.29; 2000 N e / N g = 0.26; 2004 N e / N g = 0.33). We estimated kinship and found only two of 30 natural breeding pairs showed evidence of being related (average r = –0.026, SE = 0.03). We reconstructed the genealogy of 200 wolves based on genetic and field data and discovered that they avoid inbreeding through a wide variety of behavioural mechanisms including absolute avoidance of breeding with related pack members, male‐biased dispersal to packs where they breed with nonrelatives, and female‐biased subordinate breeding. We documented a greater diversity of such population assembly patterns in Yellowstone than previously observed in any other natural wolf population. Inbreeding avoidance is nearly absolute despite the high probability of within‐pack inbreeding opportunities and extensive interpack kinship ties between adjacent packs. Simulations showed that the Yellowstone population has levels of genetic variation similar to that of a population managed for high variation and low inbreeding, and greater than that expected for random breeding within packs or across the entire breeding pool. Although short‐term losses in variation seem minimal, future projections of the population at carrying capacity suggest significant inbreeding depression will occur without connectivity and migratory exchange with other populations.

Temperature and vegetation effects on soil organic carbon quality along a forested mean annual temperature gradient in North America - CINZIA FISSORE; CHRISTIAN P. GIARDINA; RANDALL K. KOLKA; CARL C. TRETTIN; GARY M. KING; MARTIN F. JURGENSEN; CHRISTOPHER D. BARTON; S. DOUGLAS MCDOWELL (Global Change Biology, 2008)
Both climate and plant species are hypothesized to influence soil organic carbon (SOC) quality, but accurate prediction of how SOC process rates respond to global change will require an improved understanding of how SOC quality varies with mean annual temperature (MAT) and forest type. We investigated SOC quality in paired hardwood and pine stands growing in coarse textured soils located along a 22 °C gradient in MAT. To do this, we conducted 80‐day incubation experiments at 10 and 30 °C to quantify SOC decomposition rates, which we used to kinetically define SOC quality. We used these experiments to test the hypotheses that SOC quality decreases with MAT, and that SOC quality is higher under pine than hardwood tree species. We found that both SOC quantity and quality decreased with increasing MAT. During the 30 °C incubation, temperature sensitivity ( Q 10 ) values were strongly and positively related to SOC decomposition rates, indicating that substrate supply can influence temperature responsiveness of SOC decomposition rates. For a limited number of dates, Q 10 was negatively related to MAT. Soil chemical properties could not explain observed patterns in soil quality. Soil pH and cation exchange capacity (CEC) both declined with increasing MAT, and soil C quality was positively related to pH but negatively related to CEC. Clay mineralogy of soils also could not explain patterns of SOC quality as complex (2 : 1), high CEC clay minerals occurred in cold climate soils while warm climate soils were dominated by simpler (1 : 1), low CEC clay minerals. While hardwood sites contained more SOC than pine sites, with differences declining with MAT, clay content was also higher in hardwood soils. In contrast, there was no difference in SOC quality between pine and hardwood soils. Overall, these findings indicate that SOC quantity and quality may both decrease in response to global warming, despite long‐term changes in soil chemistry and mineralogy that favor decomposition.

Integrated Sensing and Processing Acoustic Resonance Spectrometry (ISP-ARS) for Sample Classification - Joseph P. Medendorp; Jason A. Fackler; Craig C. Douglas; Robert A. Lodder (Journal of Pharmaceutical Innovation, 2007)

Delayed response of diatom assemblages to sewage inputs in an Arctic lake - Neal Michelutti; Mark H. Hermanson; John P. Smol; Peter J. Dillon; Marianne S. V. Douglas (Aquatic Sciences, 2007)

Relevance of BAC transgene copy number in mice: transgene copy number variation across multiple transgenic lines and correlations with transgene integrity and expression - Kelly J. Chandler; Ronald L. Chandler; Eva M. Broeckelmann; Yue Hou; E. Michelle Southard-Smith; Douglas P. Mortlock (Mammalian Genome, 2007)

Evaluating diatom community composition in the absence of marked limnological gradients in the high Arctic: a surface sediment calibration set from Cornwallis Island (Nunavut, Canada) - Neal Michelutti; Marianne S. V. Douglas; John P. Smol (Polar Biology, 2007)

Contrasting instruction change with response change in task switching - Ian G. M. Cameron; Masayuki Watanabe; Douglas P. Munoz (Experimental Brain Research, 2007)

A novel dual staining method for identification of apoptotic cells reveals a modest apoptotic response in infarcted mouse myocardium - Douglas J. Taatjes; Marilyn P. Wadsworth; A. K. M. Tarikuz Zaman; David J. Schneider; Burton E. Sobel (Histochemistry and Cell Biology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Influence of Cutting Time on Brush Response: Implications for Herbivory in Linear (Transportation) Corridors - Roy V. Rea; Kenneth N. Child; David P. Spata; Douglas MacDonald (Environmental Management, 2007)

Diatom assemblages and their relationships to lakewater nitrogen levels and other limnological variables from 36 lakes and ponds on Banks Island, N.W.T., Canadian Arctic - Darlene S. S. Lim; John P. Smol; Marianne S. V. Douglas (Hydrobiologia, 2007)

Tropical Pacific – mid-latitude teleconnections in medieval times - Nicholas E. Graham; Malcolm K. Hughes; Caspar M. Ammann; Kim M. Cobb; Martin P. Hoerling; Douglas J. Kennett; James P. Kennett; Bert Rein; Lowell Stott; Peter E. Wigand; Taiyi Xu (Climatic Change, 2007)

The roles of sensory traps in the origin, maintenance, and breakdown of mutualism - David P. Edwards; Douglas W. Yu (Behavioral Ecology and Sociobiology, 2007)

Visual memory capacity in transsaccadic integration - Steven L. Prime; Lia Tsotsos; Gerald P. Keith; J. Douglas Crawford (Experimental Brain Research, 2007)

Computational modeling of factors that modulate the unique FeNO bonding in {FeNO}6 heme–thiolate model complexes - Douglas P. Linder; Kenton R. Rodgers (JBIC Journal of Biological Inorganic Chemistry, 2007)

Somatic embryogenesis from immature peach palm inflorescence explants: towards development of an efficient protocol - Douglas A. Steinmacher; Charles R. Clement; Miguel P. Guerra (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Evolution and the latitudinal diversity gradient: speciation, extinction and biogeography - Gary G. Mittelbach; Douglas W. Schemske; Howard V. Cornell; Andrew P. Allen; Jonathan M. Brown; Mark B. Bush; Susan P. Harrison; Allen H. Hurlbert; Nancy Knowlton; Harilaos A. Lessios; Christy M. McCain; Amy R. McCune; et al. (Ecology Letters, 2007)
A latitudinal gradient in biodiversity has existed since before the time of the dinosaurs, yet how and why this gradient arose remains unresolved. Here we review two major hypotheses for the origin of the latitudinal diversity gradient. The time and area hypothesis holds that tropical climates are older and historically larger, allowing more opportunity for diversification. This hypothesis is supported by observations that temperate taxa are often younger than, and nested within, tropical taxa, and that diversity is positively correlated with the age and area of geographical regions. The diversification rate hypothesis holds that tropical regions diversify faster due to higher rates of speciation (caused by increased opportunities for the evolution of reproductive isolation, or faster molecular evolution, or the increased importance of biotic interactions), or due to lower extinction rates. There is phylogenetic evidence for higher rates of diversification in tropical clades, and palaeontological data demonstrate higher rates of origination for tropical taxa, but mixed evidence for latitudinal differences in extinction rates. Studies of latitudinal variation in incipient speciation also suggest faster speciation in the tropics. Distinguishing the roles of history, speciation and extinction in the origin of the latitudinal gradient represents a major challenge to future research.

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols: Part 2—Evaluation of a method for determining equivalence - David Christopher; Wallace P. Adams; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 1: Background for a statistical method - Wallace P. Adams; David Christopher; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

Functional organization within a neural network trained to update target representations across 3-D saccades - Gerald P. Keith; Michael A. Smith; J. Douglas Crawford (Journal of Computational Neuroscience, 2007)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Policy implications of a pan-tropic assessment of the simultaneous hydrological and biodiversity impacts of deforestation - Ellen M. Douglas; Stanley Wood; Kate Sebastian; Charles J. Vörösmarty; Kenneth M. Chomitz; Thomas P. Tomich (Water Resources Management, 2006)

Characterization of ‘Schizokinen’; a dihydroxamate-type siderophore produced by Rhizobium leguminosarum IARI 917 - E. P. Storey; R. Boghozian; James L. Little; Douglas W. Lowman; R. Chakraborty (BioMetals, 2006)

The dynamic nature of antipredator behavior: prey fish integrate threat-sensitive antipredator responses within background levels of predation risk - Grant E. Brown; Alix C. Rive; Maud C. O. Ferrari; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2006)

The ‘salão’ vegetation of Southwestern Amazonia - Douglas C. Daly; Denise P. Costa; Antônio Willian F. Melo (Biodiversity and Conservation, 2006)

The role of learning in the acquisition of threat-sensitive responses to predator odours - Maud C. O. Ferrari; Terence Capitania-Kwok; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2006)

NONLINEAR DYNAMICS IN MANATEE VOCALIZATIONS - David A. Mann; Thomas J. O'Shea; Douglas P. Nowacek (Marine Mammal Science, 2006)

Clinical patterns of metastasis - Stanley P. L. Leong; Blake Cady; David M. Jablons; Julio Garcia-Aguilar; Douglas Reintgen; J. Jakub; S. Pendas; L. Duhaime; R. Cassell; M. Gardner; R. Giuliano; V. Archie; et al. (Cancer and Metastasis Reviews, 2006)

Molecular mechanisms of metastasis - Dave S. B. Hoon; Minoru Kitago; Joseph Kim; Takuji Mori; Adriano Piris; Katherine Szyfelbein; Martin C. Mihm; S. David Nathanson; Timothy P. Padera; Ann F. Chambers; Sharon A. Vantyghem; Ian C. MacDonald; et al. (Cancer and Metastasis Reviews, 2006)

Src activation of Stat3 is an independent requirement from NF-κB activation for constitutive IL-8 expression in human pancreatic adenocarcinoma cells - Jose G. Trevino; Michael J. Gray; Steffan T. Nawrocki; Justin M. Summy; Donald P. Lesslie; Douglas B. Evans; Tomi K. Sawyer; William C. Shakespeare; Stephanie S. Watowich; Paul J. Chiao; David J. McConkey; Gary E. Gallick (Angiogenesis, 2006)

Use of Ecotilling as an efficient SNP discovery tool to survey genetic variation in wild populations of Populus trichocarpa - ERIN J. GILCHRIST; GEORGE W. HAUGHN; CHENG C. YING; SARAH P. OTTO; JUN ZHUANG; DOROTHY CHEUNG; BJÖRN HAMBERGER; FARIBA ABOUTORABI; TATYANA KALYNYAK; LEE JOHNSON; JOERG BOHLMANN; BRIAN E. ELLIS; et al. (Molecular Ecology, 2006)
Ecotilling was used as a simple nucleotide polymorphism (SNP) discovery tool to examine DNA variation in natural populations of the western black cottonwood, Populus trichocarpa , and was found to be more efficient than sequencing for large‐scale studies of genetic variation in this tree. A publicly available, live reference collection of P. trichocarpa from the University of British Columbia Botanical Garden was used in this study to survey variation in nine different genes among individuals from 41 different populations. A large amount of genetic variation was detected, but the level of variation appears to be less than in the related species, Populus tremula , based on reported statistics for that tree. Genes examined varied considerably in their level of variation, from PoptrTB1 which had a single SNP, to PoptrLFY which had more than 23 in the 1000‐bp region examined. Overall nucleotide diversity, measured as Total , was relatively low at 0.00184. Linkage disequilibrium, on the other hand, was higher than reported for some woody plant species, with mean r 2 equal to 0.34. This study reveals the potential of Ecotilling as a rapid genotype discovery method to explore and utilize the large pool of genetic variation in tree species.

On the utility of data from the International HapMap Project for Australian association studies - Jim Stankovich; Charles J. Cox; Rachel B. Tan; Douglas S. Montgomery; Stewart J. Huxtable; Justin P. Rubio; Margaret G. Ehm; Laura Johnson; Helmut Butzkueven; Trevor J. Kilpatrick; Terence P. Speed; Allen D. Roses; et al. (Human Genetics, 2006)

Neuronal expression of the Ccm2 gene in a new mouse model of cerebral cavernous malformations - Nicholas W. Plummer; Teresa L. Squire; Sudha Srinivasan; Elizabeth Huang; Jon S. Zawistowski; Hiroaki Matsunami; Laura P. Hale; Douglas A. Marchuk (Mammalian Genome, 2006)

A protocol for high-throughput phenotyping, suitable for quantitative trait analysis in mice - Leah C. Solberg; William Valdar; Dominique Gauguier; Graciela Nunez; Amy Taylor; Stephanie Burnett; Carmen Arboledas-Hita; Polinka Hernandez-Pliego; Stuart Davidson; Peter Burns; Shoumo Bhattacharya; Tertius Hough; et al. (Mammalian Genome, 2006)

Dynamics of outgrowth in a continuum model of neurite elongation - Bruce P. Graham; Karen Lauchlan; Douglas R. Mclean (Journal of Computational Neuroscience, 2006)

Early-20th Century Environmental Changes Inferred Using Subfossil Diatoms from a Small Pond on Melville Island, N.W.T., Canadian High Arctic - Bronwyn E. Keatley; Marianne S.V. Douglas; John P. Smol (Hydrobiologia, 2006)

Variations with time in the detection thresholds of P for seismological stations reporting to the ISC - J. B. Young; A. Douglas; P. D. Marshall (Journal of Seismology, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

ACOUSTIC ECOLOGY OF FORAGING BOTTLENOSE DOLPHINS (TURSIOPS TRUNCATUS), HABITAT-SPECIFIC USE OF THREE SOUND TYPES - Douglas P. Nowacek (Marine Mammal Science, 2005)

Limnology of 46 lakes and ponds on Banks Island, N.W.T., Canadian Arctic Archipelago - Darlene S.S. Lim; Marianne S.V. Douglas; John P. Smol (Hydrobiologia, 2005)

Food web changes in arctic ecosystems related to climate warming - Roberto Quinlan; Marianne S.V. Douglas; John P. Smol (Global Change Biology, 2005)
Sedimentary records from three Canadian High Arctic ponds on Ellesmere Island, spanning the last several thousand years, show major shifts in pond communities within the last ∼200 years. These paleolimnological data indicate that aquatic insect (Diptera: Chironomidae) populations rapidly expanded and greatly increased in community diversity beginning in the 19th century. These invertebrate changes coincided with striking shifts in algal (diatom) populations, indicating strong food‐web effects because of climate warming and reduced ice‐cover in ponds. Predicted future warming in the Arctic may produce ecological changes that exceed the large shifts that have already occurred since the 19th century.

Comparison of survey methods for an invasive plant at the subwatershed level - William D. Shuster; Catherine P. Herms; Mark N. Frey; Douglas J. Doohan; John Cardina (Biological Invasions, 2005)

Climate change in lowland Central America during the late deglacial and early Holocene - Michael B. Hillesheim; David A. Hodell; Barbara W. Leyden; Mark Brenner; Jason H. Curtis; Flavio S. Anselmetti; Daniel Ariztegui; David G. Buck; Thomas P. Guilderson; Michael F. Rosenmeier; Douglas W. Schnurrenberger (Journal of Quaternary Science, 2005)
The transition from arid glacial to moist early Holocene conditions represented a profound change in northern lowland Neotropical climate. Here we report a detailed record of changes in moisture availability during the latter part of this transition (∼11 250 to 7500 cal. yr BP) inferred from sediment cores retrieved in Lake Petén Itzá, northern Guatemala. Pollen assemblages demonstrate that a mesic forest had been largely established by ∼11 250 cal. yr BP, but sediment properties indicate that lake level was more than 35 m below modern stage. From 11 250 to 10 350 cal. yr BP, during the Preboreal period, lithologic changes in sediments from deep‐water cores (>50 m below modern water level) indicate several wet–dry cycles that suggest distinct changes in effective moisture. Four dry events (designated PBE1‐4) occurred centred at 11 200, 10 900, 10 700 and 10 400 cal. yr BP and correlate with similar variability observed in the Cariaco Basin titanium record and glacial meltwater pulses into the Gulf of Mexico. After 10 350 cal. yr BP, multiple sediment proxies suggest a shift to a more persistently moist early Holocene climate. Comparison of results from Lake Petén Itzá with other records from the circum‐Caribbean demonstrates a coherent climate response during the entire span of our record. Furthermore, lowland Neotropical climate during the late deglacial and early Holocene period appears to be tightly linked to climate change in the high‐latitude North Atlantic. We speculate that the observed changes in lowland Neotropical precipitation were related to the intensity of the annual cycle and associated displacements in the mean latitudinal position of the Intertropical Convergence Zone and Azores–Bermuda high‐pressure system. This mechanism operated on millennial‐to‐submillennial timescales and may have responded to changes in solar radiation, glacial meltwater, North Atlantic sea ice, and the Atlantic meridional overturning circulation (MOC). Copyright © 2005 John Wiley & Sons, Ltd.

Quantitative estimates of recent environmental changes in the Canadian High Arctic inferred from diatoms in lake and pond sediments - Dermot Antoniades; Marianne S. V. Douglas; John P. Smol (Journal of Paleolimnology, 2005)

Comparing different methods of calculating volume-weighted hypolimnetic oxygen (VWHO) in lakes - Roberto Quinlan; Andrew M. Paterson; John P. Smol; Marianne S. V. Douglas; Bev J. Clark (Aquatic Sciences, 2005)

Functional analysis of a mutant form of the receptor tyrosine kinase Tie2 causing venous malformations - Paul N. Morris; Benjamin J. Dunmore; Amir Tadros; Douglas A. Marchuk; Diane C. Darland; Patricia A. D’Amore; Nicholas P. J. Brindle (Journal of Molecular Medicine, 2005)

Equations for the Estimation of Strong Ground Motions from Shallow Crustal Earthquakes Using Data from Europe and the Middle East: Vertical Peak Ground Acceleration and Spectral Acceleration - N. N. Ambraseys; J. Douglas; S.K. Sarma; P. M. Smit (Bulletin of Earthquake Engineering, 2005)

Equations for the Estimation of Strong Ground Motions from Shallow Crustal Earthquakes Using Data from Europe and the Middle East: Horizontal Peak Ground Acceleration and Spectral Acceleration - N. N. Ambraseys; J. Douglas; S. K. Sarma; P. M. Smit (Bulletin of Earthquake Engineering, 2005)

Diatom species-environment relationships and inference models from Isachsen, Ellef Ringnes Island, Canadian High Arctic - Dermot Antoniades; Marianne S.V. Douglas; John P. Smol (Hydrobiologia, 2004)

PHENYLPYRUVIC ACID DERIVATIVES AS ENZYME INHIBITORS: THERAPEUTIC POTENTIAL ON MACROPHAGE MIGRATION INHIBITORY FACTOR - Alain J.M. Carpy; Petrus P. Haasbroeck; Douglas W. Oliver (Medicinal Chemistry Research, 2004)

RESONANCE AND DISSONANCE: SCIENCE, ETHICS, AND THE SONAR DEBATE - Damon P. Gannon; David W. Johnston; Andrew J. Read; Douglas P. Nowacek (Marine Mammal Science, 2004)

Using Solution-Phase Nanoparticles, Surface-Confined Nanoparticle Arrays and Single Nanoparticles as Biological Sensing Platforms - Amanda J. Haes; Douglas A. Stuart; Shuming Nie; Richard P. Van Duyne (Journal of Fluorescence, 2004)

HIGH PERFORMANCE TURNING CAPABILITIES DURING FORAGING BY BOTTLENOSE DOLPHINS ( TURSIOPS TRUNCATUS ) - Jennifer L. Maresh; Frank E. Fish; Douglas P. Nowacek; Stephanie M. Nowacek; Randall S. Wells (Marine Mammal Science, 2004)
A bstract Large predators should have difficulty catching small prey because small animals demonstrate greater maneuverability and agility compared to large animals. The ability of a predator to capture small prey indicates locomotor strategies to compensate for inequities in maneuverability. Bottlenose dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida feed on fish at least one order of magnitude smaller than themselves. To examine the locomotor strategies involved in prey capture, the foraging movements of these dolphins were videotaped from overhead using a remotely‐controlled camera suspended from a helium‐filled aerostat, which was tethered to an observation vessel. Dolphins were observed to rapidly maneuver during chases of fish in open water or around patches of rooted vegetation. Video analysis of the chase sequences indicated that the dolphins could move the rostrum through small radius turns with a mean value of 0.20 body lengths and with a minimum value of 0.08 body lengths. Mean rate of turn was 561.6°/sec with a maximum rate measured at 1,372.0°/sec. High turning rates with small turning radii were primarily the result of maneuvers in which the dolphin rolled 90° and rapidly flexed its body ventrally. The ability of dolphins to change body orientation in multiple rotational axes provides a mechanism to reduce turning radius and increase turning rate to catch small, elusive prey.

Soxhlet extraction of organic compounds associated with soil water repellency - Christopher T. Llewellyn; Stefan H. Doerr; Peter Douglas; Christopher P. Morley; Kathryn A. Mainwaring (Environmental Chemistry Letters, 2004)

Role of heavy polar organic compounds for water repellency of sandy soils - Kathryn A. Mainwaring; Christopher P. Morley; Stefan H. Doerr; Peter Douglas; Christopher T. Llewellyn; Gareth Llewellyn; Ian Matthews; Bridget K. Stein (Environmental Chemistry Letters, 2004)

Global Warming and Coastal Erosion - Keqi Zhang; Bruce C. Douglas; Stephen P. Leatherman (Climatic Change, 2004)

Late Holocene lake level dynamics inferred from magnetic susceptibility and stable oxygen isotope data: Lake Elsinore, southern California (USA) - Matthew E. Kirby; Christopher J. Poulsen; Steve P. Lund; William P. Patterson; Liam Reidy; Douglas E. Hammond (Journal of Paleolimnology, 2004)

Making sense of predator scents: investigating the sophistication of predator assessment abilities of fathead minnows - Robin C. Kusch; Reehan S. Mirza; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2004)

Cold temperature increases winter fruit removal rate of a bird-dispersed shrub - Charles Kwit; Douglas J. Levey; Cathryn H. Greenberg; Scott F. Pearson; John P. McCarty; Sarah Sargent (Oecologia, 2004)

Urotensin-II: a novel systemic hypertensive factor in the cat - Kristeen Maniscalco; Gerald P. Stankus; Alexandra Wibberley; Robert N. Willette; Stephen A. Douglas; David J. Behm; Christopher P. A. Doe; Douglas G. Johns (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Production of C35 isoprenoids depends on H2 availability during cultivation of the hyperthermophile Methanococcus jannaschii - Brendan P. Manquin; John A. Morgan; Jaeyeong Ju; Thomas Müller-Späth; Douglas S. Clark (Extremophiles, 2004)

On the Incorporation of the Effect of Crustal Structure into Empirical Strong Ground Motion Estimation - J. Douglas; P. Suhadolc; G. Costa (Bulletin of Earthquake Engineering, 2004)

Testing population-level mechanisms of invasion by a mobile vertebrate: a simple conceptual framework for salmonids in streams - Douglas P. Peterson; Kurt D. Fausch (Biological Invasions, 2003)

Synergistic interactions between chemical alarm cues and the presence of conspecific and heterospecific fish shoals - Brian D. Wisenden; Mike S. Pollock; Robyn J. Tremaine; Jeff M. Webb; Monique E. Wismer; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2003)

Diatoms and sockeye salmon (Oncorhynchus nerka) population dynamics: Reconstructions of salmon-derived nutrients over the past 2,200 years in two lakes from Kodiak Island, Alaska - Irene Gregory-Eaves; John P. Smol; Marianne S.V. Douglas; Bruce P. Finney (Journal of Paleolimnology, 2003)

Steady-State and Time-Resolved Spectroscopic Characteristics of Novel Silicon-Containing Organopolymers - S. B. Bushuk; W. E. Douglas; Ju. A. Kalvinkovskaya; L. G. Klapshina; A. N. Rubinov; B. A. Bushuk; A. P. Stupak (Journal of Fluorescence, 2003)

Diversity and distribution of Collembola (Arthropoda: Hexapoda) of Brazil - Mark P. Culik; Douglas Zeppelini Filho (Biodiversity and Conservation, 2003)

Evaluation of Bowhead Whale Status: Reply to Taylor - Kim E. W. Shelden; David J. Rugh; Douglas P. DeMaster; Leah R. Gerber (Conservation Biology, 2003)

Assessment of Predation Risk by Juvenile Yellow Perch, Perca flavescens: Responses to Alarm Cues from Conspecifics and Prey Guild Members - Reehan S. Mirza; Sheri A. Fisher; Douglas P. Chivers (Environmental Biology of Fishes, 2003)

Fathead Minnows, Pimephales promelas, Learn to Recognize Chemical Alarm Cues of Introduced Brook Stickleback, Culaea inconstans - Michael S. Pollock; Douglas P. Chivers; Reehan S. Mirza; Brian D. Wisenden (Environmental Biology of Fishes, 2003)

Temporal and spatial distribution of paramoebae in the water column – a pilot study - G M Douglas‐Helders; D P O'Brien; B E McCorkell; D Zilberg; A Gross; J Carson; B F Nowak (Journal of Fish Diseases, 2003)
Amoebic gill disease is the main disease affecting the salmonid industry in Tasmania, but no information on the distribution of the causative pathogen, Neoparamoeba pemaquidensis , in the aquatic environment is available. This pilot study aimed to determine temporal and spatial distributions of paramoebae species in the water column, using an immuno‐dot blot technique. Water samples were collected from inside fish cages at various depths (0.5, 5.5 and 11.0 m) in both summer and winter, as well as various distances (0, 0.5, 240, 280, 750 and 1100 m) away from the sea cage and farming site. Paramoebae densities were estimated using the most probable number technique (MPN). Temperature, salinity, dissolved oxygen, turbidity, nitrite and nitrates, and bacterial counts were measured for each water sample. Data were analysed using a residual maximum likelihood test and significant associations between paramoebae densities and environmental factors were analysed. Results showed that densities were significantly higher in summer ( P = 0.017), at 5.5 m depth ( P = 0.029), and reduced to the lowest density at 1100 m away from the cage sites ( P = 0.008). Bacterial counts, turbidity and temperature were found to be significantly associated with paramoebae densities.

Nitrogen fixation and nitrogen isotope abundances in zooplankton of the oligotrophic North Atlantic - Joseph P. Montoya; Edward J. Carpenter; Douglas G. Capone (Limnology and Oceanography, 2002)
Deep‐water nitrate is a major reservoir of oceanic combined nitrogen and has long been considered to be the major source of new nitrogen supporting primary production in the oligotrophic ocean. 15 N: 14 N ratios in plankton provide an integrative record of the nitrogen cycle processes at work in the ocean, and near‐surface organic matter in oligotrophic waters like the Sargasso Sea is characterized by an unusually low 15 N content relative to average deep‐water nitrate. Herein we show that the low dΔ 15 N of suspended particles and zooplankton from the tropical North Atlantic cannot arise through isotopic fractionation associated with nutrient uptake and food web processes but are instead consistent with a significant input of new nitrogen to the upper water column by N 2 fixation. These results provide direct, integrative evidence that N 2 fixation makes a major contribution to the nitrogen budget of the oligotrophic North Atlantic Ocean.

On Technological and Immunological Benefits of Multivalent Single-Injection Microsphere Vaccines - Gérard Boehm; Marisa Peyre; Dorothea Sesardic; Rachel J. Huskisson; Fatme Mawas; Alexandra Douglas; Dorothy Xing; Hans P. Merkle; Bruno Gander; Pål Johansen (Pharmaceutical Research, 2002)

Tracking recent recovery from eutrophication in a high arctic lake (Meretta Lake, Cornwallis Island, Nunavut, Canada) using fossil diatom assemblages - Neal Michelutti; Marianne S.V. Douglas; John P. Smol (Journal of Paleolimnology, 2002)

Physical and chemical limnology of 34 ultra-oligotrophic lakes and ponds near Wynniatt Bay, Victoria Island, Arctic Canada - Neal Michelutti; Marianne S.V. Douglas; David R.S. Lean; John P. Smol (Hydrobiologia, 2002)

Delineation of the evolution of compositional changes in atheroma - Marilyn P. Wadsworth; Burton E. Sobel; David J. Schneider; Douglas J. Taatjes (Histochemistry and Cell Biology, 2002)

Cytokine polymorphisms in silicosis and other pneumoconioses - Berran Yucesoy; Val Vallyathan; Douglas P. Landsittel; Petia Simeonova; Michael I. Luster (Molecular and Cellular Biochemistry, 2002)

Effect of Predator Diet on Life History Shifts of Red-Legged Frogs, Rana aurora - Joseph M. Kiesecker; Douglas P. Chivers; Michael Anderson; Andrew R. Blaustein (Journal of Chemical Ecology, 2002)

Brook Char (Salvelinus fontinalis) Can Differentiate Chemical Alarm Cues Produced by Different Age/Size Classes of Conspecifics - Reehan S. Mirza; Douglas P. Chivers (Journal of Chemical Ecology, 2002)

Acquired Predator Recognition by Fathead Minnows: Influence of Habitat Characteristics on Survival - Kyra J. Gazdewich; Douglas P. Chivers (Journal of Chemical Ecology, 2002)

Developing Classification Criteria under the U.S. Endangered Species Act: Bowhead Whales as a Case Study - Kim E. W. Shelden; Douglas P. Demaster; David J. Rugh; Annette M. Olson (Conservation Biology, 2001)

Developing Classification Criteria under the U.S. Endangered Species Act: Bowhead Whales as a Case Study - Kim E. W. Shelden; Douglas P. Demaster; David J. Rugh; Annette M. Olson (Conservation Biology, 2001)
Under the U.S. Endangered Species Act, a species is classified as endangered, threatened, or recovered based on the extent to which its survival is affected by one or more of five subjective factors. A key criticism of the act is that it makes no reference to quantitative or even qualitative parameters of what constitutes “danger of extinction.” Without objective standards to guide decisionmakers, classification decisions fall prey to political and social influences. We recommend the development of species‐specific, status‐determining criteria as a means to rationalize and expedite the listing process and reclassification decisions, independent of the requirement for delisting criteria in recovery plans. Such criteria should (1) clearly define levels of vulnerability, (2) identify gaps in information on life‐history parameters, and (3) address uncertainty in existing data. As a case study, we developed preliminary criteria for bowhead whales ( Balaena mysticetus ). Thresholds for endangered and threatened status were based on World Conservation Union ( IUCN) Red List criteria and population viability analyses. Our analysis indicates that particular attention must be focused on population structure within the species to appropriately classify the degree to which one or more components of a species are vulnerable to extinction. A similar approach could be used in the classification of other species. According to our application of the IUCN criteria and those developed for similar species by , the Bering Sea population of bowhead whales should be delisted, whereas the other four populations of bowheads should continue to be considered endangered.

THREE‐DIMENSIONAL DIVING BEHAVIORS OF RINGED SEALS ( PHOCA HISPIDA ) - Michael A. Simpkins; Brendan P. Kelly; Douglas Wartzok (Marine Mammal Science, 2001)
A bstract Dives of five freely diving ringed seals were classified into three‐dimentional movement types. Horizontally convoluted dives, defined as dives with angular velocity > 15°/sec, appeared to be foraging or social dives. Simple dives that did not include convoluted movements (angular velocity 0.6, on a scale of 0–1) were presumed to be travel dives. Each three‐dimensional dive type was observed with similar frequency in dives with two distinct time‐depth profiles: V‐shaped profiles in which ascent immediately followed descent, and U‐shaped profiles in which >7 sec were spent at depth between descent and ascent. The lack of behavioral differences between dives with distinct time‐depth profiles suggested that time‐depth profiles are not a reliable means of inferring dive behaviors for ringed seals.

Brook Charr Alevins Alter Timing of Nest Emergence in Response to Chemical Cues from Fish Predators - Reehan S. Mirza; Douglas P. Chivers; Jean-Guy J. Godin (Journal of Chemical Ecology, 2001)

Dual targeting properties of the N-terminal signal sequence of Arabidopsis thaliana THI1 protein to mitochondria and chloroplasts - Sabrina M. Chabregas; Douglas D. Luche; Leonardo P. Farias; Alberto F. Ribeiro; Marie-Anne van Sluys; Carlos F.M. Menck; Marcio C. Silva-Filho (Plant Molecular Biology, 2001)

Avoidance Response of Juvenile Pacific Treefrogs to Chemical Cues of Introduced Predatory Bullfrogs - Douglas P. Chivers; Erica L. Wildy; Joseph M. Kiesecker; Andrew R. Blaustein (Journal of Chemical Ecology, 2001)

Are Chemical Alarm Cues Conserved Within Salmonid Fishes? - Reehan S. Mirza; Douglas P. Chivers (Journal of Chemical Ecology, 2001)

The effects of food level and conspecific density on biting and cannibalism in larval long-toed salamanders, Ambystoma macrodactylum - Erica L. Wildy; Douglas P. Chivers; Joseph M. Kiesecker; Andrew R. Blaustein (Oecologia, 2001)

Diatoms and their relationship to environmental variables from lakes and ponds on Bathurst Island, Nunavut, Canadian High Arctic - Darlene S. S. Lim; Marianne S. V. Douglas; John P. Smol (Hydrobiologia, 2001)

Expression of a re-centering bias in saccade regulation by superior colliculus neurons - Martin Par; Douglas P. Munoz (Experimental Brain Research, 2001)

AN ESTIMATION OF CARRYING CAPACITY FOR SEA OTTERS ALONG THE CALIFORNIA COAST - Kristin L. Laidre; Ronald J. Jameson; Douglas P. Demaster (Marine Mammal Science, 2001)
A bstract Carrying capacity (K) for the California sea otter ( Enhydra lutris nereis ) was estimated as a product of the density of sea otters at equilibrium within a portion of their existing range and the total area of available habitat. Equilibrium densities were determined using the number of sea otters observed during spring surveys in 1994, 1995, and 1996 in each of three habitat types where sea otters currently exist. Potential sea otter habitat was defined as from the California coastline to the 40‐m isobath and classified as rocky, sandy, or mixed habitat according to the amount of kelp and rocky substrate in the area. The amount of habitat available to sea otters in California was estimated using a Geographic Information Systems (GIS) program. The estimated mean number of sea otters that could be supported by the marine environment to a depth of 40 m in California was 15,941 (95% CI 13,538–18,577). The GIS‐based approach incorporated detailed bathymetric contours, produced repeatable and accurate estimates, and served as an innovative method of measuring sea otter habitat. We believe the approach described in this paper represents the best available information on how a sea otter population at equilibrium would be distributed along the California coast.

SURVIVORSHIP OF CAPTIVE SOUTHERN SEA OTTERS - Bete A. Jones; Douglas P. Demaster (Marine Mammal Science, 2001)

PINNIPED SURVIVAL IN CAPTIVITY: ANNUAL SURVIVAL RATES OF SIX SPECIES - Simona Perry Roberts; Douglas P. Demaster (Marine Mammal Science, 2001)

Chemosensory Assessment of Predation Risk by Slimy Sculpins (Cottus cognatus): Responses to Alarm, Disturbance, and Predator Cues - Pamela J. Bryer; Reehan S. Mirza; Douglas P. Chivers (Journal of Chemical Ecology, 2001)

Oviposition site selection and embryo mortality in perch - C. Smith; A. Douglas; P. Jurajda (Journal of Fish Biology, 2001)
Egg strands of perch Perca fluviatilis around the margins of a lake were associated significantly with submerged vegetation. The proportion of dead embryos was significantly higher in egg strands deposited directly on the lake bottom than those on submerged vegetation.

Browse yield and nutritive value of two Salix species and Dorycnium rectum in New Zealand - S. K. Oppong; P. D. Kemp; G. B. Douglas; A. G. Foote (Agroforestry Systems, 2001)

Importance of Predator Diet Cues in Responses of Larval Wood Frogs to Fish and Invertebrate Predators - Douglas P. Chivers; Reehan S. Mirza (Journal of Chemical Ecology, 2001)

A PLATFORM FOR CONTINUOUS BEHAVIORAL AND ACOUSTIC OBSERVATION OF FREE‐RANGING MARINE MAMMALS: OVERHEAD VIDEO COMBINED WITH UNDERWATER AUDIO - Douglas P. Nowacek; Peter L. Tyack; Randall S. Wells (Marine Mammal Science, 2001)

Incorporating Uncertainty into Management Models for Marine Mammals - Barbara L. Taylor; Paul R. Wade; Douglas P. De Master; Jay Barlow (Conservation Biology, 2000)
Good management models and good models for understanding biology differ in basic philosophy. Management models must facilitate management decisions despite large amounts of uncertainty about the managed populations. Such models must be based on parameters that can be estimated readily, must explicitly account for uncertainty, and should be simple to understand and implement. In contrast, biological models are designed to elucidate the workings of biology and should not be constrained by management concerns. We illustrate the need to incorporate uncertainty in management models by reviewing the inadequacy of using standard biological models to manage marine mammals in the United States. Past management was based on a simple model that, although it may have represented population dynamics adequately, failed as a management tool because the parameter that triggered management action was extremely difficult to estimate for the majority of populations. Uncertainty in parameter estimation resulted in few conservation actions. We describe a recently adopted management scheme that incorporates uncertainty and its resulting implementation. The approach used in this simple management scheme, which was tested by using simulation models, incorporates uncertainty and mandates monitoring abundance and human‐caused mortality. Although the entire scheme may be suitable for application to some terrestrial and marine problems, two features are broadly applicable: the incorporation of uncertainty through simulations of management and the use of quantitative management criteria to translate verbal objectives into levels of acceptable risk.

Homing and Movement of Yellow-phase American Eels in Freshwater Ponds - Peter J. Lamothe; Merry Gallagher; Douglas P. Chivers; John R. Moring (Environmental Biology of Fishes, 2000)

Eutrophication and recovery in the High Arctic: Meretta Lake (Cornwallis Island, Nunavut, Canada) revisited - Marianne S.V. Douglas; John P. Smol (Hydrobiologia, 2000)

Isolation, genomic organization, and expression analysis of the mouse and rat homologs of MEFV, the gene for familial Mediterranean fever - Jae Jin Chae; Michael Centola; Ivona Aksentijevich; Amalia Dutra; Maiyen Tran; Geryl Wood; Kanneboyina Nagaraju; Douglas William Kingma; P. Paul Liu; Daniel L. Kastner (Mammalian Genome, 2000)

Chemical Alarm Signaling by Reticulate Sculpins, Cottus perplexus - Douglas P. Chivers; Matthew H. Puttlitz; Andrew R. Blaustein (Environmental Biology of Fishes, 2000)

Evolution of N-terminal sequences of the vertebrate HOXA13 protein - Douglas P. Mortlock; Praveen Sateesh; Jeffrey W. Innis (Mammalian Genome, 2000)

Passing of northern pike and common carp through experimental barriers designed for use in wetland restoration - John R. P. French; Douglas A. Wilcox; S. Jerrine Nichols (Wetlands, 1999)

Use of historical and geospatial data to guide the restoration of a Lake Erie coastal marsh - Kurt P. Kowalski; Douglas A. Wilcox (Wetlands, 1999)

Purinergic Modulation of Na + ,K + ,Cl − Cotransport and MAP Kinases is Limited to C11-MDCK Cells Resembling Intercalated Cells from Collecting Ducts - S.N. Orlov; N.O. Dulin; F. Gagnon; M. Gekle; J.G. Douglas; J.H. Schwartz; P. Hamet (The Journal of Membrane Biology, 1999)

Scratching the Skin of Predator—prey Interactions in Fishes: A Tribute to R. Jan F. Smith (1940–1998) - Douglas P. Chivers; Alicia Mathis; Grant E. Brown; Reehan S. Mirza; Brian D. Wisenden (Environmental Biology of Fishes, 1999)

Contrasting Behavioral Responses by Detritivorous and Predatory Mayflies to Chemicals Released by Injured Conspecifics and Their Predators - Alexander D. Huryn; Douglas P. Chivers (Journal of Chemical Ecology, 1999)

Shifts in Life History as a Response to Predation in Western Toads (Bufo boreas) - Douglas P. Chivers; Joseph M. Kiesecker; Adolfo Marco; Erica L. Wildy; Andrew R. Blaustein (Journal of Chemical Ecology, 1999)

Gray Whales and the Value of Monitoring Data in Implementing the U.S. Endangered Species Act - Leah R. Gerber; Douglas P. Demaster; Peter M. Kareiva (Conservation Biology, 1999)
Many scientists lament the absence of data for endangered species and argue that more funds should be spent acquiring basic information about population trends. Using 19 years of abundance estimates for the eastern North Pacific gray whale ( Eschrichtius robustus ), we sampled subsets of the original survey data to identify the number of years of data required to remove the population from the U.S. Endangered Species Act's (ESA) list of endangered and threatened wildlife. For any given duration of monitoring, we selected all possible combinations of consecutive counts. To incorporate variability in growth rates, we extracted a maximum likelihood estimator of growth rate and confidence interval about that growth rate on the assumption that the population changes can be approximated by a simple diffusion process with drift. We then applied a new approach to determine ESA status for each subset of survey data and found that a quantitative decision to delist is unambiguously supported by 11 years of data but is precariously uncertain with fewer than 10 years of data. The data needed to produce an unequivocal decision to delist gray whales cost the National Marine Fisheries Service an estimated U.S. $660,000, a surprisingly modest expense given the fact that delisting can greatly simplify regulatory constraints. This example highlights the value of population monitoring in administering the ESA and provides a compelling example of the utility of such information in identifying both imperiled and recovered species. The economic value of such data is that they provide the foundation for delisting, which could ultimately save much more money than the collection of the data would ever cost.

A Quantitative Approach to Endangered Species Act Classification of Long‐Lived Vertebrates: Application to the North Pacif ic Humpback Whale - Leah R. Gerber; Douglas P. Demaster (Conservation Biology, 1999)
The U.S. Endangered Species Act (ESA) mandates that recovery plans include specific criteria to determine when a species should be removed from the List of Endangered and Threatened Wildlife. To meet this mandate, we developed a new approach to determining classification criteria for long‐lived vertebrates. The key idea is that endangerment depends on two critical aspects of a population: population size and trends in population size due to intrinsic variability in population growth rates. The way to combine these features is to identify a population size and range of population growth rates (where λ denotes the annual multiplicative rate of change of a population) above which there is a negligible probability of extinction. To do so, (1) information on the current population size and its variance is specified; (2) available information on vital rates or changes in abundance over time is used to generate a probability distribution for the population's λ; (3) the lower fifth percentile value for λ (denoted as λ (0.05) ) is obtained from the frequency distribution of λs; and (4) if λ (0.05) is (0.05) is ≥1.0, the threshold for endangerment is set at 500 animals. A similar approach can be used to determine the threshold for listing a species as threatened under the ESA. We applied this approach to North Pacific humpback whales ( Megaptera novaeangliae ) and used Monte Carlo simulations to produce a frequency distribution of λs for the whales under three different scenarios. Using λ (0.05) , it was determined that the best estimates of current abundance for the central population of North Pacific humpback whales were larger than the estimated threshold for endangered status but less than the estimated threshold for threatened status. If accepted by the responsible management agency, this analysis would be consistent with a recommendation to downlist the central stock of humpback whales to a status of threatened, whereas the status of eastern and western stocks would remain endangered.

Shifts in Life-History Traits as a Response to Cannibalism in Larval Long-Toed Salamanders (Ambystoma macrodactylum) - Erica L. Wildy; Douglas P. Chivers; Andrew R. Blaustein (Journal of Chemical Ecology, 1999)

SPERM WHALE SURFACE ACTIVITY FROM TRACKING BY RADIO AND SATELLITE TAGS 1 - William A. Watkins; Mary Ann Daher; Nancy A. Dimarzio; Amy Samuels; Douglas Wartzok; Kurt M. Fristrup; Damon P. Gannon; Paul W. Howey; Romaine R. Maiefski; Trevor R. Spradlin (Marine Mammal Science, 1999)
A bstract Three 12‐m sperm whales ( Physeter catodon ) were tagged and tracked west of Dominica in the southeast Caribbean to follow the surfacing patterns and movements of these presumed subadult males. Whale N was tagged in April 1993 with a 30‐MHz radio tag and tracked for two days. Whale H was tagged in April 1995 with a 30‐MHz radio tag and tracked for 4.6 d. Whale A was tagged in April 1995 with a satellite‐monitored tag tracked by ARGOS for 21.5 d, the first four of which were concurrent with the tracking of Whale H, an associate. The tagged whales remained west of Dominica for at least 2, 5, and 13 d, respectively. Whales N and A then moved southward to waters off Martinique. There were no apparent effects on the whales by tagging or the presence of the tags. The whales averaged speeds of 2.6‐3.5 km/h. Surfacings, indicated by tag signals, were of two types: short surfacings apparently primarily for respiration, averaging 7‐10.5 min between repeated longer dives, occurring day and night; and extended surfacings seemingly for rest and social interactions with conspecifics, occurring mostly in daylight. Whales were near the surface for 20.4%–22.6% of the total time (26.6%–27.1% during the day and 14.9%–17.1% at night). Delayed blowing was observed as Whale N surfaced for 8.3 min between 47‐ and 45‐min dives but delayed the first of its 31 blows for 1.5 min after surfacing.

Fractal geometry of root systems: Field observations of contrasting genotypes of common bean (Phaseolus vulgaris L.) grown under different phosphorus regimes - Kai L. Nielsen; Carter R. Miller; Douglas Beck; Jonathan P. Lynch (Plant and Soil, 1999)

Optical Thin-Film Sensors for the Determination of Aqueous Halide Ions - Chris D. Geddes; Peter Douglas; Christopher P. Moore; Trevor J. Wear; Peter L. Egerton (Journal of Fluorescence, 1999)

Selection, evaluation, and identification of improved Russet Norkotah strains - J. Creighton Miller; Douglas C. Scheuring; Jeannie P. Miller; George C. J. Fernandez (American Journal of Potato Research, 1999)

Do assemblages of Coregonus (Teleostei: Salmoniformes) in the Central Alpine region of Europe represent species flocks? - M. R. Douglas; P. C. Brunner; L. Bernatchez (Molecular Ecology, 1999)
To examine models of evolution for Coregonus from the Central Alpine region of Europe, 20 populations from nine lakes were assessed for variation at six microsatellite DNA loci. Patterns of variation were tested against three evolutionary models: phenotypic plasticity, multiple invasions of lakes by divergent forms, and within‐lake radiation of species flocks. All sympatric and all but one allopatric pairs of populations were significantly divergent in allele frequencies. Pairwise F ‐statistics indicated reduced gene flow among phenotypically divergent sympatric populations. These results reject the hypothesis that within‐lake morphological and ecological diversity reflects phenotypic plasticity within a single gene pool. Genetic similarity was higher among forms within lakes than between populations of the same form in different lakes. Among‐lake divergence was primarily a product of allele size differences. Mantel tests contrasting patterns of genetic divergence against patterns predicted from the multiple invasions and species flocks models indicated that the latter is the best explanation of the observed genetic variation. Thus, reproductively isolated species diverged within lakes, with similar patterns repeatedly emerging among lakes. While this study argues for a particular mode of evolution in Central Alpine Coregonus , the taxonomy of these forms remains unresolved.

Kinetic Model for Integrin-mediated Adhesion Release During Cell Migration - Sean P. Palecek; Alan F. Horwitz; Douglas A. Lauffenburger (Annals of Biomedical Engineering, 1999)

Changes in the distribution of Atlantic cod ( Gadus morhua ) in the southern Gulf of St Lawrence — effects of environmental change or change in environmental preferences? - DOUGLAS P. SWAIN (Fisheries Oceanography, 1999)
Density‐independent redistribution in response to changing temperature conditions and density‐dependent redistribution in response to changing temperature preferences are two contrasting hypotheses to explain changes in the distribution of cod populations. I tested these hypotheses using survey data on the distribution of cod during the feeding season in the southern Gulf of St Lawrence. These tests used indices of cod distribution as the dependent variable and indices of cod abundance and bottom temperature as explanatory variables. Both hypotheses were often supported in univariate tests that ignored confounding between the two explanatory variables. Tests that accounted for this confounding indicated an effect of cod abundance on distribution for ages 4–8 + years, and 3 + , but provided no support for an effect of environmental conditions on distribution except for age 3. Variation in the temperature distribution of cod was consistent with an effect of abundance on interannual variation in distribution and with no effect of environment except for age 3 cod. Age 3 cod were consistently under‐represented in areas of very cold bottom water but older cod were not. As predicted by bioenergetic considerations, cod tended to occupy colder water at high levels of abundance, suggesting a mechanism for density‐dependent shifts in distribution. Shifts in cod distribution during the feeding season in the southern Gulf appear to be more closely linked to density‐dependent changes in environmental preferences than to density‐independent responses to changing environmental conditions.

Differential expression of proliferative, cytoskeletal, and adhesive proteins during postnatal development of the hamster submandibular gland - Rui P. Fernandes; Douglas A. Cotanche; Kelley Lennon-Hopkins; Fatih Erkan; A. Sue Menko; M. A. Kukuruzinska (Histochemistry and Cell Biology, 1999)

A monocot pollen-specific promoter contains separable pollen-specific and quantitative elements - Douglas A. Hamilton; Yuka H. Schwarz; Joseph P. Mascarenhas (Plant Molecular Biology, 1998)

Sequence and Expression in Escherichia coli of the Coat Protein Gene of the Dwarfing Strain of Soybean Dwarf Luteovirus - Oney P. Smith; Scott A. Durkin; Douglas G. Luster; Larry L. McDaniel; Anthony J. Russo; Vernon D. Damsteegt (Virus Genes, 1998)

The ruminant parasite Haemonchus contortus expresses an α1,3-fucosyltransferase capable of synthesizing the Lewis x and sialyl Lewis x antigens - Russell A DeBose-Boyd; A. Kwame Nyame; Douglas P Jasmer; Richard D Cummings (Glycoconjugate Journal, 1998)

CXC chemokines mechanism of action in regulating tumor angiogenesis - Bethany B. Moore; Douglas A. Arenberg; Christina L. Addison; Michael P. Keane; Peter J. Polverini; Robert M. Strieter (Angiogenesis, 1998)

Time and dose dependency of the suppression of pulmonary metastases of rat mammary cancer by amiloride - Douglas M. Evans; Kimberly Sloan-Stakleff; Michael Arvan; Daniel P. Guyton (Clinical & Experimental Metastasis, 1998)

Movements and behavior of satellite-tagged spotted seals ( Phoca largha ) in the Bering and Chukchi Seas - Lloyd F. Lowry; Kathryn J. Frost; Randall Davis; Douglas P. DeMaster; Robert S. Suydam (Polar Biology, 1998)

Forest Ecosystems, Forest Management and the Global Carbon Cycle, edited by M. J. Apps and D. T. Price, NATO Series, Series 1: Global Environmental Change, Vol. 40 - Douglas P. Ormrod (Water, Air, & Soil Pollution, 1998)

Microsatellite and mitochondrial DNA assessment of population structure and stocking effects in Arctic charr Salvelinus alpinus (Teleostei: Salmonidae) from central Alpine lakes - P. C. BRUNNER; M. R. DOUGLAS; L. BERNATCHEZ (Molecular Ecology, 1998)
Despite geographical isolation and widespread phenotypic polymorphism, previous population genetic studies of Arctic charr, Salvelinus alpinus , have detected low levels of intra‐ and interpopulation variation. In this study, two approaches were used to test the generality of low genetic diversity among 15 Arctic charr populations from three major drainages of the central Alpine region of Europe. First, a representative subsample of each drainage was screened by PCR–RFLP analysis of mtDNA using 31 restriction enzymes. All individuals but one shared an identical haplotype. In contrast, microsatellite DNA variation revealed high levels of genetic diversity within and among populations. The number of alleles per locus ranged from six to 49, resulting in an overall expected heterozygosity from 0.72 ± 0.09 to 0.87 ± 0.04 depending on the locus. Despite evidence for fish transfers among Alpine charr populations over centuries, genetic diversity was substantially structured, as revealed by hierarchical Φ statistics. Eighteen per cent of total genetic variance was apportioned to substructuring among Rhône, Rhine, and Danube river systems, whereas 19% was due to partitioning among populations within each drainage. Cluster analyses corroborated these results by drainage‐specific grouping of nonstocked populations, but also revealed damaging effects of stocking practices in others. However, these results suggest that long‐term stocking practices did not generally alter natural genetic partitioning, and stress the importance of considering genetic diversity of Arctic charr in the Alpine region for sound management. The results also refute the general view of Arctic charr being a genetically depauperate species and show the potential usefulness of microsatellite DNAs in addressing evolutionary and conservation issues in this species.

Interactive effects of subanesthetic ketamine and subhypnotic lorazepam in humans - John H. Krystal; Laurence P. Karper; Alexandre Bennett; D. Cyril D'Souza; Anissa Abi-Dargham; Kristen Morrissey; Danielle Abi-Saab; J. Douglas Bremner; M. B. Bowers Jr.; Raymond F. Suckow; Philip Stetson; George R. Heninger; et al. (Psychopharmacology, 1998)

Mapping sediment acoustic impedance using remote sensing acoustic techniques in a shallow-water carbonate environment - Donald J. Walter; Douglas N. Lambert; David C. Young; Kevin P. Stephens (Geo-Marine Letters, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Differential learning rates of chemical versus visual cues of a northern pike by fathead minnows in a natural habitat - Grant E. Brown; Douglas P. Chivers; R. Jan F. Smith (Environmental Biology of Fishes, 1997)

Reactions of Gammarus lacustris to Chemical Stimuli from Natural Predators and Injured Conspecifics - Karen Wudkevich; Brian D. Wisenden; Douglas P. Chivers; R. Jan F. Smith (Journal of Chemical Ecology, 1997)

Chemical contamination and associated liver diseases in two species of fish from San Francisco Bay and Bodega Bay - CARLA M. Stehr; MARK S. Myers; DOUGLAS G. BURROWS; MARGARET M. Krahn; JAMES P. Meador; BRUCE B. McCAIN; USHA Varanasi (Ecotoxicology, 1997)

Learned Recognition of Predation Risk by Enallagma Damselfly Larvae (Odonata, Zygoptera) on the Basis of Chemical Cues - Brian D. Wisenden; Douglas P. Chivers; R. Jan. F. Smith (Journal of Chemical Ecology, 1997)

Norgold Russet and Norgold Russet strain M — additional evidence for genetic dissimilarity - J. Creighton Miller; Douglas G. Smallwood; Jeannie P. Miller; George C. J. Fernandez (American Journal of Potato Research, 1995)

Localized defecation by pike: a response to labelling by cyprinid alarm pheromone? - Grant E. Brown; Douglas P. Chivers; R. Jan F. Smith (Behavioral Ecology and Sociobiology, 1995)

Localized defecation by pike: a response to labelling by cyprinid alarm pheromone? - G. E. Brown; Douglas P. Chivers; R. Jan F. Smith (Behavioral Ecology and Sociobiology, 1995)

Comparative acute sensitivities of early life stages of atherinid fishes to chlorpyrifos and thiobencarb - Patrick W. Borthwick; James M. Patrick; Douglas P. Middaugh (Archives of Environmental Contamination and Toxicology, 1985)

The interface zone of inorganic implantsIn vivo: Titanium implants in bone - Tomas Albrektsson; P-I. Brånemark; Hans-Arne Hansson; Bengt Kasemo; Kåre Larsson; Ingmar Lundström; Douglas H. McQueen; Richard Skalak (Annals of Biomedical Engineering, 1983)

Isolation and characterization of an anaerobic syntrophic benzoate-degrading bacterium from sewage sludge - Douglas O. Mountfort; Marvin P. Bryant (Archives of Microbiology, 1982)

Temperature-sensitive mutants of influenza A virus: Evaluation of the Alaska/77-ts-1 A 2 temperature-sensitive recombinant virus in seronegative adult volunteers - B. R. Murphy; R. M. Chanock; R. G. Douglas; R. F. Betts; D. H. Waterman; H. P. Holley; D. L. Hoover; S. Suwanagool; D. R. Nalin; M. M. Levine (Archives of Virology, 1980)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

The influence of genetic background on expression of mutations at the diabetes locus in the mouse. I. C57BL/KsJ and C57BL/6J strains - Katharine P. Hummel; Douglas L. Coleman; Priscilla W. Lane (Biochemical Genetics, 1972)